The response of organic matter in Pennsylvanian coals in the North China Basin to rapid heating by magmatic intrusion - Bangjun Liu; Jiazhong Huang; James C. Hower; Achim Bechtel; Vivian A. Edwards; Wenmu Guo; Zeqi Tian; Shiming Liu; Lin Xiao; Cunliang Zhao (Organic Geochemistry, 2026)

Late Cretaceous large-scale melting of the Neo-Tethyan oceanic slab in southern Tibet - Cheng Li; Lin Ma; Andrew C. Kerr; Qiang Wang; Zhiwei Yu; Wei Qiao (Lithos, 2026)

Insights from stratigraphic reconfiguration induced by the South Pole-Aitken massive impact - Sheng Gou; Zongyu Yue; Yangting Lin; Bin Su; Zhanchuan Cai; Roberto Bugiolacchi; Kaichang Di; Patrick C. Pinet; Yuyang He; Honglei Lin; Hengci Tian; Sen Hu; et al. (Icarus, 2026)

C–N–H chemistry, PAH growth and soot formation in non-premixed flames of ethylene/ammonia/hydrogen: A CFD study - Anurag Dahiya; Zi-Jia Wang; Kuang C. Lin (Fuel, 2026)

Characterizing effects of tree mortality from wildfire and bark beetles using satellite observations of solar-induced chlorophyll fluorescence - Lewis Kunik; David R. Bowling; Brett Raczka; Jeffrey A. Hicke; Christian Frankenberg; Rui Cheng; Michèle R. Slaton; John C. Lin (Remote Sensing of Environment, 2026)

Mechanistic insights into the selective recovery of aqueous scandium using iron-based metal–organic frameworks - Ping-Xian Lin; Eduardo C. Atayde; Ping-Huan Wu; Yi-Pei Li; Kevin C.-W. Wu; Pei-Jen Chen (Journal of Environmental Chemical Engineering, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Triazine and other herbicides in sediments of lower Laurentian Great Lakes – pre- and post-depositional mobility and in-situ degradation - Shanshan Zhou; Huan He; Tian Lin; Jiehong Guo; Xiusen Yang; Xinyue Jia; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Environmental Pollution, 2026)

Straw pyrolysis reverses forest soil N2O emissions from stimulation to suppression by altering organic C quality and N cycling pathways - Yanfei Dong; Dafeng Hui; Jiashu Zhou; Tida Ge; Junjie Lin; Yu Luo; Yuxue Liu; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Chemical Engineering Journal, 2026)

Effects of Lactobacillus- and Bacillus-based probiotics on growth performance, intestinal barrier function, and microbiota modulation in nursery pigs: A meta-analysis - K. Sahatsanon; A. Jayanegara; S.W. Kim; Y. Ruangpanit; C.-S. Lin; P. Sivapirunthep; C. Chaosap (Animal Feed Science and Technology, 2026)

Genetic dissection of grain yield and correlated proxy traits under suboptimal conditions - Yan-Cheng Lin; Claude Urbany; Antonina Shlykova; Armin C. Hölker; Milena Ouzunova; Thomas Presterl; Torsten Pook; Manfred Mayer; Sebastian Urzinger; Chris-Carolin Schön (Theoretical and Applied Genetics, 2026)
Key message This eight-founder MAGIC population represents a powerful resource for dissecting complex traits in maize, assessing the utility of drought proxy traits, and optimizing low-coverage whole-genome sequencing approaches. Abstract Securing sustainable crop production requires the genetic improvement of abiotic stress tolerance. Due to the broad range of environmental factors causing abiotic stress and complex genotype-by-environment interactions, it is crucial to understand the genetic basis of crop yield under suboptimal conditions. Here, we developed a dent maize Multi-parent Advanced Generation Inter-Cross (MAGIC) population comprising 388 doubled-haploid (DH) lines. The population was derived from eight founders with varying stress tolerance, selected from a dent diversity panel evaluated for yield performance across a wide range of European environments. The MAGIC DH lines were genotyped via whole-genome sequencing (~ 5× coverage) and evaluated in seven testcross and 14 line per se trials, for grain yield, leaf senescence, leaf rolling, anthesis-silking interval, and six additional agronomic traits. Genetic dissection identified 22 grain yield QTL, explaining 45% of the genetic variance. Under heat and drought stress, testcross grain yield correlated significantly with leaf senescence and leaf rolling measured in line per se trials. Bivariate multi-trait analysis showed that alleles for delayed senescence and reduced rolling at detected QTL generally exhibited positive effects on grain yield, suggesting that accumulating these favorable alleles could enhance yield performance. Incorporating these proxies into multi-trait genomic prediction models improved yield prediction accuracy, although gains were constrained by modest trait correlations. Given the comprehensive data, we also provide recommendations for optimizing sequencing depth and QTL mapping strategies in experimental maize populations.

Balancing climate and biodiversity: Assessing the socioeconomic impacts of the 30-by-30 target with climate warming constraints - Kevin Lin Yang; C. Adam Schlosser; Angelo Gurgel (Land Use Policy, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Storage timescales and the crystal growth history recorded in the layered reservoir of the Unit 3 Kulanaokuaiki Tephra Member of the Uēkahuna Ash from Kīlauea volcano - Abigail R. Nalesnik; Kendra J. Lynn; Timothy R. Rose; Jessica M. Warren; Dawn C. S. Ruth; Kuan-Yu Lin; Donald A. Swanson (Contributions to Mineralogy and Petrology, 2026)
The Kulanaokuaiki Tephra Unit 3 (900 C.E.) was a subplinian basaltic scoria eruption, the largest known to have occurred at Kīlauea’s summit. The initiation mechanism and cause(s) of this highly hazardous eruption remain poorly understood, particularly as this style of activity has not been observed in the modern period. We use olivine diffusion timescales from Fe-Mg and lithium zoning to assess magma storage timescales and evaluate evidence for mixing prior to eruption. Of the 200 crystals assessed, 55% are normally zoned for forsterite and 45% are non-zoned. Zoned crystals (> 1 mm) ( n = 96) have average compositions of Fo 89 cores and Fo 81 rims, while small crystals 0.5–1 mm ( n = 14) have Fo 85 cores and Fo 82 rims. Modeled Fo diffusion timescales range from n = 17), reflecting growth processes and precluding their use for diffusion studies. Overall, our Unit 3 olivine dataset displays no evidence of magmatic priming shortly prior to eruption, unlike prior observations for the basaltic subplinian eruption of the Keanakāko‘i Tephra Unit E (1650 C.E.). Thus, explosive eruption magmas may be stored for considerably longer than previously thought, and magmatic priming is not a necessary precursor for Kīlauea’s explosive eruptions. We hypothesize that gas-driven filter pressing from crystallization of microlites and macrocrysts in the reservoir slurry contributed to the explosivity of the Unit 3 eruption.

Contributions of previous whole-brain radiation therapy, cumulative intracranial tumor volume, and repeat radiosurgery to adverse radiation effects following stereotactic radiosurgery for brain metastasis - Ali A. Alattar; Jiri Bartek; Alice Lin; Carlin Chuck; Hsien-Chung Chen; Giovanni Kozel; Sharona Ben-Haim; Clark C. Chen (Clinical & Experimental Metastasis, 2026)

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Industrial waste salt pyrolysis toward zero liquid discharge: Enabling efficient organic removal and resource recovery - Zhi-Bo Li; Xiang-Lin Chang; Juan Xie; Rong Chen; Xiaochang C. Wang; Bao-Shan Xing (Journal of Water Process Engineering, 2026)

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Simultaneous multi-biomarker detection: streptavidin-biotin mediated high-quality quantum dot immunosensor with signal amplification - Huanhuan Xing; Ruixue Zhang; Ning Li; Xiaoquan Li; Zoi G. Lada; Theocharis C. Stamatatos; Xinxin Chen; Huaibin Shen; Dangdang Xu; Xiaojing Xing; Ruili Wu; Lin Song Li (Analytica Chimica Acta, 2026)

Why Was the Official Australian Monsoon Onset Unusually Late in 2024/25? - Tim Cowan; Rajashree Naha; Hanh Nguyen; Hanna Heidemann; Sugata Narsey; Matthew C. Wheeler; Corey Robinson; Chris Lucas; Andrew G. Marshall; Lin Wang (Advances in Atmospheric Sciences, 2026)
The official 2024/25 Australian summer monsoon (ASM) onset occurred on 7 February, more than two weeks later than the previous record. Defined using Darwin winds, the official ASM typically arrives between mid-December and mid-January. Here, we investigate (1) why the ASM onset was record late, despite La Niña-like conditions, and (2) if the late ASM onset was consistent with other unofficial monsoon and rainy season onset definitions. Our results show earlier onsets when using wind and rainfall-based definitions, mainly due to strong synoptic-to-intraseasonal variability. Two onset definitions were triggered in December 2024 when the Madden–Julian Oscillation (MJO) contributed to deep convection and above-average rain over northern Australia. In late January, a monsoon trough formed over northeast and northwest Australia, but not over Darwin. With the MJO in a suppressed state, the Darwin region experienced record-breaking January temperatures. The ASM eventually arrived in early February, with the reason behind its historically late onset likely a result of weather noise and variability. Another location, ∼1200 km east of Darwin, did not experience such a late onset, using similar definitions. Relevant to monsoon systems globally, our study highlights the limitations of local onset or wind-only definitions, which may not necessarily capture the large-scale monsoonal conditions, and be amplified by short-term weather variability.

Arbuscular mycorrhizal fungi orchestrate belowground microbiomes in plant holobionts - Letian Wang; Lin Zhang; Matthias C. Rillig; Marcel G.A. van der Heijden; Nancy C. Johnson; Gu Feng (Trends in Plant Science, 2026)

Proteomic insights into intestinal immune modulation in Atlantic salmon (Salmo salar) fed fucoidan from brown seaweed (Saccharina latissima) - Kathiresan Purushothaman; Byron Morales-Lange; SérgioD.C. Rocha; Lin Qingsong; Luis Mercado; Margareth Øverland; Charles McLean Press (Fish & Shellfish Immunology, 2026)

A comprehensive review of phage immobilization and encapsulation for the application in food safety - Pankaj Koirala; Yen-Te Liao; Meng-Wei Lin; Shyam S. Sablani; Vivian C. H. Wu (Critical Reviews in Food Science and Nutrition, 2026)

Correction: The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta‑Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2026)

Impact of polystyrene nanoplastics on soil microbial biomass - Chunyang Li; Heping Shang; Zeyu Cai; Weili Jia; Yini Cao; Xiupei Zhou; Jie Zhang; Sixiang Zhuang; Ziqin Lin; Anqi Liang; Lanfang Han; Jason C. White; et al. (Environmental Chemistry Letters, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Interrelationships among PM2.5/O3 concentrations, polluted weather patterns, and meteorological conditions over Taiwan based on 2006–2024 observations - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Meng-Hsuan Lee; Ja-Huai Lee; Chih-Chung Chang; Wei-Nai Chen; Chian-Yi Liu (Atmospheric Research, 2026)

Long-term urban emission trends in Salt Lake City: Examining CO, CO2, and NOX enhancements - Haley Humble; J.C. Lin; D.V. Mallia; C. Harkins; B.C. McDonald; M.A. Garcia; M. Ostlie (Atmospheric Environment, 2026)

Molting disruption in fall armyworm by an ankyrin-based Bracovirus factor from the parasitoid wasp Microplitis prodeniae Rao and Chandry - Yaru Wang; Farman Ullah; Liuying Lin; Xiangyun Cai; Ge Gao; Limin Chen; Zhiming Chen; Raul Narciso C. Guedes; Yaobin Lu; Jinda Wang; Youming Hou (Journal of Pest Science, 2026)

The learning efficiency of the ant Anoplolepis gracilipes (Hymenoptera: Formicidae) varies with temperature - C.-H. Chan; T.-S. Lin; H.-D. Lin; C.-I. Chiu (Insectes Sociaux, 2026)

Influence of surgical intervention on pre- and post-surgery patient specific muscle synergies in children with cerebral palsy - Tiana Breust; Jiayin Lin; Vincent C. K. Cheung; Firooz Salami; Sebastian I. Wolf; Gursel Alici; Manish Sreenivasa (Experimental Brain Research, 2026)
Muscle synergy analysis has been explored as means to better understand changes in motor control, with the aim to improve treatment outcomes after Single Event Multilevel Surgery (SEMLS) for children with cerebral palsy (CP). In this single-group study, we assess changes between pre- and post-surgery muscle synergies at both patient specific, and cohort levels after surgical intervention for children with CP. We analysed the walking data of 11 patients between the ages of 7–18 years old, including surface electromyography, joint angles and ground reaction forces, recorded before and after surgery. Muscle synergies were extracted and assessed for changes in dimensionality and sparseness between pre- and post-surgery. Our results show that at a patient specific level, pre- and post-surgery muscle synergies were not highly similar, with only 41% of paired synergies showing high correlation ( $$r$$ $$>$$ 0.8) after surgery, and an overall mean correlation of 0.53 $$±$$ 0.25. On the other hand, synergies obtained at the cohort level were highly similar post-surgery ( $$r$$ $$>$$ 0.87). These findings suggest that at an individual level, pre-surgery motor control cannot be assumed to be preserved post-surgery. CP synergies obtained at the cohort level from pre-surgery data can demonstrate more reliable preservation in post-surgery motor control. We also observed sparseness increasing with the number of synergies, which provides an interesting future research direction exploring the link with more complex motor control and a more typical gait pattern.

Partial sympatry of two interspersed Uroteuthis edulis (Loliginidae) clades reveals cryptic stock structure in the southern Taiwan Strait - Rui-Yi Hong; Lorenzo C. Halasan; Ke-Yang Chang; Chia-Hui Wang; Hsiu-Chin Lin (Fisheries Research, 2026)

Genetic connectivity of Uroteuthis sibogae (Cephalopoda: Loliginidae) in the Sulu Sea with notes on morphology and statolith microchemistry - Jessica M. Legaspi; Lorenzo C. Halasan; Kris Angeli Sanchez-DelosReyes; Tomoyo Okumura; Hsiu-Chin Lin (Regional Studies in Marine Science, 2026)

Enterobacter hormaechei S27 is a potential biocontrol agent against Camellia oleifera seed mildew - Shanni Lin; Xiaojun Deng; Shiping Xu; Xiyu Su; Chunqian Leng; He Li; Richard C. Hamelin; Guoying Zhou; Yuanhao He (Journal of Stored Products Research, 2026)

Microplastic pollution enhances methane emissions from remote mountainous lakes via plastisphere-mediated microbial processes - Naying Li; Bo Zhong; Wei-Min Wu; Xintong Mei; Ruixi Liu; Xin Liu; Xianxiang Li; Rehman Abdul; Shaoliang Yi; Li Zhou; Honghui Lin; Xiaofeng Wang; et al. (Journal of Environmental Sciences, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Stable yet hydrophilic graphene oxide nanomembranes by zwitterionic reduction for dye desalination - Sagnik Das; Ziwen Zhang; Erda Deng; Emmanuel M. Nsengiyumva; Ruveen Dias; Shixian Ha; Xiao Tong; Gbassey S.A. Oteme; Shweta Singh; Kai Chen; Prathima C. Nalam; Chang-Yong Nam; et al. (Chemical Engineering Journal, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Improved wetlands analytics for achieving the goals of both the Ramsar Convention and the Kunming-Montreal Global Biodiversity Framework for wetlands monitoring - Elena A. Mikhailova; Hamdi A. Zurqani; Lili Lin; Zhenbang Hao; Christopher J. Post; Mark A. Schlautman; Gregory C. Post; George B. Shepherd (Wetlands Ecology and Management, 2026)
Wetlands are an important part of the Ramsar Convention (RC) and Kunming-Montreal Global Biodiversity Framework (KM-GBF), which is a significant agreement committing 196 countries (the United States is not a participant of KM-GBF) to a reduction and halting of the loss of biodiversity by 2030. In comparison to the broadly focused KM-GBF, goals of RC (172 contracting parties) are wetlands-focused such as “wise use” and protection of wetlands, selection of wetlands of “international importance”, and international collaboration. The goal of this study is to explore how improved wetlands analytics can help achieve the goals of both the RC and KM-GBF using the state of North Carolina (NC) in the United States of America (USA) as an example. Several goals and targets of KM-GBF are applicable to wetlands, with only a handful of indicators (e.g., wetland extent trends (WET) index) to monitor them. The WET index is only relevant at the global or continental scale because it relies on a limited database of wetland sites over time. Unfortunately, the WET index does not allow tracking of smaller spatial extents and new methods are needed to understand how wetlands are changing over time. Geospatial analysis results and recommendations are presented for both RC and KM-GBF. Loss of wetlands can result in transboundary damage, harming biodiversity and ecosystem functions and services (ES). A case study of NC showed that almost 49% of the wetland area was lost between 1780 and 1980 in the state. Wetlands loss in NC continued between 2001 and 2021. Future RC and KM-GBF refinements could use sea level rise analysis to evaluate changes in wetlands.

Prior antibiotic exposure is associated with worse outcomes in adults with COVID-19 - Finlay A. McAlister; Meng Lin; Erik Youngson; Brendan C. Lethebe; Myles Leslie (Infectious Diseases, 2026)

Can 3D printed food affect consumer self-expressiveness and sharing intention? The lens from the value-attitude-behavior model - Zhengan Zhu; C. Michael Hall; Runze Mao; Feifei Lin (International Journal of Gastronomy and Food Science, 2026)

Boosting ammonia-fed solid oxide fuel cell performance via high-entropy alloy anode surface modification - Nasima Khatun; Cheng-Ju Lin; Jia-You Lin; Sridharan Balu; Shi-Shin Yang; Sea-Fue Wang; Thomas C.-K. Yang (Fuel, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Prenatal exposure to extreme heat and autism in children - David G. Luglio; Xin Yu; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Nathan Pavlovic; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Combining hydrologic, chemical, and geophysical deep learning-based inversion for heterogeneous aquifer structure identification - Yuzhou Xia; Chuanjun Zhan; Zhenxue Dai; Jichun Wu; Xiaoying Zhang; Huichao Yin; Lin Zhu; Jiahe Yan; Zihao Wang; Mohamad Reza Soltanian; Kenneth C. Carroll (Journal of Hydrology, 2026)

Active site-rich MIL-101(Fe) derived P-doped iron sulfide/carbon octahedra for oxygen evolution electrocatalysis - Ying-Jun Jhang Jian; Pin-Yan Lee; Subbiramaniyan Kubendhiran; Lu-Yin Lin; Kevin C.-W. Wu; Kuo-Chuan Ho (Journal of Environmental Chemical Engineering, 2026)

Phenol exposure promotes tumor-related signaling and blood vessel formation through the extracellular signal-regulated kinase/p38/hypoxia-inducible factor-1α pathway in cellular and zebrafish models - Chung-Yu Lin; Wangta Liu; Pei-Hsuan Chen; Chia C. Wang; Che-Hsin Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Feasibility of a Multi-Laboratory Model of Middle Cerebral Artery Thromboembolic Stroke with Thrombolysis: TE-MCAo - Michelle Lin; Mozammel Bhuiyan; Carly McCurry; Jessica Lamb; Marcio A. Diniz; Karni Bedirian; Anil K. Chauhan; Abhishek Jha; Aditi Jain; Enrique C. Leira; Rakeshkumar Patel; Mohammad B. Khan; et al. (Translational Stroke Research, 2026)
No single animal stroke model satisfies all needs of translational stroke investigation. While the nylon filament model is widely accepted in preclinical translational stroke research, thromboembolic models have more physiological relevance. Thromboembolic models are technically difficult, time consuming, and show variable results, making them problematic for multi-laboratory preclinical network use. We sought to develop and validate a multi-laboratory thromboembolic middle cerebral artery occlusion model that encompasses vessel occlusion and subsequent thrombolysis. To reduce the numbers of donor animals used, we developed a method to store donor blood for later use. Using prefabricated microcatheters, we simplified thrombus preparation and handling. Emboli were prepared in microcatheters and injected directly into the middle cerebral artery from the internal carotid artery. For thrombolysis we used intravenous Tenecteplase dosing at 1.5 mg/kg. To demonstrate feasibility and ease-of-use, the model was implemented at six research laboratories. We wrote and field-tested standard operating procedures, training videos, and hands-on surgical training workshops. We enrolled 170 Sprague Dawley rats of both sexes at six laboratories who performed 4 to 6 thrombus embolizations per week. All sites could achieve reproducible occlusion and thrombolysis. Thromboemboli prepared from stored blood served as well as emboli from freshly drawn blood. Of 135 rats who received one embolus, 33 (24%) died before 48-hour MRI scan. In survivors, stroke volume was 13 ± 16% of the ipsilateral hemisphere. Occlusions were seen in the MCA in 15%, distal ICA in 19%, both (T-occlusions) in 2% and in the MCA/ACA in 1%. Corner test, neurobehavioral battery, and MRI showed reasonably consistent stroke injury. We established the feasibility and reproducibility of a multi-laboratory rodent thromboembolic model but further development is needed to improve the success rate and lower the mortality rate before this model can be accepted widely.

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

A New Dayongaspid Galeaspid from the Silurian of the Lower Yangtze Region: Implications for Biogeography and the Evolution of Key Adaptations in Galeaspids - Yumeng Zhang; Xianren Shan; Xianghong Lin; Zhikun Gai; Philip C. J. Donoghue (Journal of Earth Science, 2026)

Carbon mineralization and temperature sensitivity of particulate versus mineral associated organic matter in a 56-year long-term no-till Vertisol - Cong He; Ram C. Dalal; Tong Li; Hai-Lin Zhang; Yash Pal Dang (Agriculture, Ecosystems & Environment, 2026)

An in vitro-in silico workflow for predicting renal clearance of environmental chemicals and drugs - Courtney Sakolish; Hsing-Chieh Lin; Haley L. Moyer; Lucie C. Ford; Charles H. Christen; Barbara A. Wetmore; Michael J. DeVito; Philip Hewitt; Stephen S. Ferguson; Farah Raad; Ivan Rusyn; Weihsueh A. Chiu (Toxicology, 2026)

Effect of cold plasma-activated water generated by piezoelectric direct discharge on the quality of diced onions during storage - Peeraphat Prempree; Loraine C. Bainto-Ancheta; Lin Wang; Yukiharu Ogawa (Postharvest Biology and Technology, 2026)

Carbon source and temperature effects on nitrogen removal performance in a novel adaptive activated sludge process - Qionghua Zhang; Lin Wu; Yadong Xie; Haijun Mi; Mawuli Dzakpasu; Xiaochang C. Wang (Environmental Research, 2026)

Associations between concurrent neonicotinoid, pyrethroid, and organophosphate insecticide metabolites and neurocognitive performance in Ecuadorian adolescents - Jessica Yen; Kun Yang; Tuo Lin; Xin M. Tu; Georgia Kayser; Rajendra P. Parajuli; Ana Skomal; Sheila Gahagan; Jose Suarez-Torres; Suzi Hong; Raeanne C. Moore; Jose R. Suarez-Lopez (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

The in-flight cooling of ballistic pyroclasts during mafic explosive eruptions: a numerical model - Chiedozie C. Ogbuagu; Kuang C. Lin; Thomas J. Jones; Silvio De Angelis (Journal of Volcanology and Geothermal Research, 2025)

Air toxics and late-life dementia and cognitive impairment in Mexican Americans - Yu Yu; Jason Su; Sanjali Mitra; Yufan Gong; Shiwen Li; Yuyuan Lin; Karl O'Sharkey; Kimberly C. Paul; Beate Ritz (Environmental Research, 2025)

Subcellular localization of the P2X4 receptor in sensory hair cells of Wistar rat cochlea - Ziyin Huang; Jacqueline M. Ross; Shelly C. Y. Lin; Prakansha N. Kumar; Kevin Roy; Srdjan M. Vlajkovic; Peter R. Thorne; Haruna Suzuki-Kerr (Histochemistry and Cell Biology, 2025)
Our sense of hearing starts in the inner ear organ, the cochlea, which contains two types of auditory hair cells for signal transduction. Earlier research showed that the complex cochlear physiology is regulated in part by purinergic signalling through activation of purine-mediated P2X, P2Y and adenosine receptors expressed in the cochlea. This study aims to extend our knowledge of purinergic signalling in the cochlea by comprehensively characterising the expression of the P2X4 receptor subtype. Wistar rat cochlea (embryonic day 20.5–6 weeks, both sexes) were collected, and the P2X4 expression was examined by immunohistochemistry. Robust P2X4 expression was found in the organ of Corti (OoC) in the inner hair cells (IHCs) and outer hair cells (OHCs), confirmed by double-labelling with hair cells (HCs) marker myosin VIIa. In IHCs, a robust cytoplasmic P2X4 expression occurred throughout the cell body, with the most intense signal at the medial side. In OHCs, P2X4 formed puncta near the apical and basal ends of the cell body. Using markers for subcellular organelles, P2X4 immunoreactivity was predominately associated with the trans-Golgi network apparatus and early endosomes in IHC and with early endosomes and lysosomes in OHC in the mature cochlea. In both cell types, some co-localisation of P2X4 with presynaptic marker was also observed. Taken together, these observations suggest unique roles for P2X4 in mature IHCs and OHCs as a purinergic receptor subtype responsible for the homeostatic regulation of hair cells and auditory sensory transduction.

An effective ECG signal classification method based on a minimalistic memristive reservoir computing system - Xiaoyuan Wang; Meng Yang; Yuji Zeng; Zhuosheng Lin; Herbert H. C. Iu (Cognitive Neurodynamics, 2025)

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Analysis of source regions and transport pathways of sub-micron aerosol components in Europe - Michelle Y. Schneider; Jianhui Jiang; Ying Chen; Wenche Aas; Samira Atabakhsh; Minna Aurela; Claudio Belis; Aikaterini Bougiatioti; Michael Bressi; Francesco Canonaco; Benjamin Chazeau; Hasna Chebaicheb; et al. (Environmental Pollution, 2025)

Mesoporous MOFs unlock concurrent gains in efficiency and stability of perovskite solar cells - Xisheng Zhang; Yongqi Yin; Yu Jiang; Yingji Zhao; Xiangyang Liu; Norman C.-R. Chen; Lin Li; Yusuke Asakura; Yusuke Yamauchi (Chemical Engineering Journal, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

The Interplay of Traits, Phylogeny and Abundance Shapes Spatial Mammal Diversity Patterns - Kay Zin Than; Alice C. Hughes; Lin Wang; Zaw Zaw; Rui‐Chang Quan (Global Ecology and Biogeography, 2025)
Aim Terrestrial mammal communities are crucial indicators of tropical ecosystem health and sustainability. However, the role of shared species responses driven by functional traits and phylogenetic relatedness in shaping community assembly remains underexplored for identifying conservation hotspots. Spatial predictions of species diversity also remain limited by approaches that fail to jointly account for species occupancy and abundance. This study evaluates trait‐ and phylogeny‐informed environmental filtering in structuring mammal communities and maps spatial diversity patterns by integrating species occupancy and abundance across spatial–temporal scales. Ultimately, areas of high mammal diversity reflecting underlying assembly processes are identified to guide regional conservation planning. Location Myanmar and China. Time Period 2015–2021. Major Taxa Studied Terrestrial mammals. Methods We deployed 936 camera traps over 6 years across Upper Myanmar and Xishuangbanna, China, using a nested sampling design that ensured robust spatial–temporal replication, and analysed the data using community hierarchical models. Results Climate and habitat factors predominantly drive species richness, while traits and phylogenetic relatedness jointly shape distinct community patterns. Seasonal variation in local diversity underscores the role of environmental filtering in structuring mammal communities across space and time. Large‐bodied omnivores favour stable temperature niches, whereas reduced precipitation filters communities towards wide‐ranging mammals. Anthropogenic disturbances and forest cover loss alter community structure, diminishing the prevalence of carnivorous traits. Predictive community maps with uncertainty estimates guide future survey efforts through a more integrative, data‐informed approach to regional planning. Main Conclusions This study presents a novel framework for improving climate‐ and habitat‐based biodiversity models by integrating trait‐ and phylogeny‐informed assembly processes with abundance‐based predictions across suitable habitats. The findings, including phylogenetically clustered niches in Cervidae and Felidae, suggest that shared evolutionary adaptations, such as temperature tolerance in ungulates and disturbance tolerance in carnivores, shape community assembly under varying environmental pressures and can inform spatial conservation prioritisation.

Halogenated flame retardants in the sediments of the lower Great Lakes and region-wide discoveries - Tian Lin; Shanshan Zhou; Huan He; Jiehong Guo; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Journal of Hazardous Materials, 2025)

Corticotropin-releasing factor (CRF) as a biomarker for agonal stress in feline forensic cases - W. Huang; C. Lin (Journal of Comparative Pathology, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

Exploring PFRs, ROS, PAHs, nitro-PAHs, and health risks of the nonthermal plasma intervention size-segregated smoldering incense and mosquito coils aerosols - Yu-Chieh Wang; Chia C. Wang; Chon-Lin Lee; Wei-Min Ching (Environmental Pollution, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Humidity-dependent ammonium formation and enhanced light scattering in agricultural aerosols - Chien-Hao Lin; Ling-Ya Chen; Ting-Yu Chiang; Sally C. W. Tai; Shih-Yu Chang (Environmental Geochemistry and Health, 2025)

Population genomics of rainforest mountain frogs (Anura: Limnodynastidae: Philoria) severely impacted by the Australian megafires - Shengyao Lin; David Newell; Nicola J. Mitchell; Stephen C. Donnellan; Michael Mahony; Liam J. Bolitho; Renee A. Catullo (Conservation Genetics, 2025)
The 2019/20 Australian megafires impacted numerous species, including six of the seven montane frog species from the genus Philoria , which are restricted to the top of mountain habitats across eastern Australian Gondwana Rainforest. Using single nucleotide polymorphisms, we examined the population structure and genetic diversity of the six Philoria species to inform conservation management and assess their capacity for post-fire recovery. Narrow-range species were confirmed as a single population for management purposes, while P. kundagungan , P. loveridgei , and P. sphagnicolus exhibit marked genetic differentiation between populations, indicating strong allopatric differentiation among populations isolated on separate mountaintops, suggesting limited natural dispersal ability. We further identify high-value genetic populations in these structured species. Populations that were heavily impacted by the fires, such as P. pughi and P. knowlesi , may face longer-term threats due to potential declines in adaptive capacity. We recommend prioritising in situ management, genetic rescue, and translocation efforts to bolster resilience in isolated populations. Updated conservation planning and targeted fire buffer management are crucial for the survival of these ancient, regionally endemic frogs in a rapidly changing climate.

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

Impact of conventional extraction methods on the nutritional, functional, and structural properties of alfalfa sprout protein as an alternative protein source - Loraine C. Bainto-Ancheta; Nasuha Bunyameen; Feifei Hu; Lin Wang; Yukiharu Ogawa (Food Bioscience, 2025)

Adsorption of phosphorus on different substrates of constructed wetlands - X. Liu; M. Tang; C. Lin; H. Zhu; Z. Xu; H. Zhai; X. Tan (International Journal of Environmental Science and Technology, 2025)

Metrics of Urbanicity and Rurality in US-Based Epidemiologic Studies of Ambient Temperature and Health: A Scoping Review - Nicholaus P. Johnson; Alexandra Del Favero-Campbell; Amruta Nori-Sarma; Audrey Amezcua-Smith; Brandon Lewis; Chen Chen; Chengyi Lin; Damien Foo; Garam Byun; Hayon Michelle Choi; Honghyok Kim; Jesse D. Berman; et al. (Current Environmental Health Reports, 2025)

SMART-assisted discovery of butenolides from the marine-derived Aspergillus sp. NBU4698 with multidrug resistance reversing and anti-inflammatory activity - Hang Zhao; Zhiyan Zhou; Fangjian Feng; Wei Yuan; Lixin Chen; C. Benjamin Naman; Zhiran Ju; Ziyi Zhou; Wenhan Lin; Shan He; Lijian Ding (Phytochemistry, 2025)

Celebrating the fifth edition of the International Symposium on Fungal Stress – ISFUS, a decade after its 2014 debut - Alene Alder-Rangel; Amanda E.A. Rangel; Arturo Casadevall; Asiya Gusa; Chaoyang Xue; Charles M. Boone; Chris Todd Hittinger; Claudio A. Masuda; Consuelo Olivares-Yañez; Deborah Bell-Pedersen; Erica J. Washington; Gerhard Braus; et al. (Fungal Biology, 2025)

Body size rather than reflectivity explains thermal constraints on colour variation in an aposematic jewel bug - Kei-Lin M. Ooi; Iliana Medina; Fabian C. Salgado-Roa; Devi Stuart-Fox (Evolutionary Ecology, 2025)
Theory posits that warning signals should converge phenotypically to reinforce predator memory, yet many aposematic species show substantial variation in warning signals within and between populations. This could be explained by alternative selective pressures on phenotype beyond predation such as thermoregulation, but empirical tests are scarce and do not consider the full spectrum of sunlight. To examine whether trade-offs with thermoregulation could explain variation in warning colouration, we examined thermal properties of colour variants of the aposematic cotton harlequin bug ( Tectocoris diophthalmus ). This species shows striking variation in warning signals: it is sexually dichromatic, varies within sexes, and shows clinal variation in colour frequencies, with iridescent blue-green colouration prevalent in cooler climates and non-iridescent red–orange colouration prevalent in warmer climates. We quantified reflectivity between colour variants over the full solar spectrum and investigated the contribution of ultraviolet and visible (UV–visible, 300–700 nm) and near infrared (NIR, 700–1700 nm) light on heating. Differences in reflectivity of iridescent and non-iridescent colour patches were greater in NIR than UV–visible wavelengths but did not result in significant differences in heating. However, we found a tight link between body size and reflectivity, with smaller males having lower reflectivity and heating faster. Due to the strong correlation between body size and colouration, thermal constraints related to body size may help to explain the observed clinal variation in colour frequencies.

Speciation of coral-associated barnacles: generalists versus specialists in the Indo-West Pacific - Hsiu-Chin Lin; Lorenzo C. Halasan; Yoko Nozawa; Benny K. K. Chan (Coral Reefs, 2025)

Metabolite‐Mediated Trophic Interactions: Long‐Term Responses of Thalassiosira weissflogii to High CO 2 and Warming Have Cascading Effects on Consumer Metabolism - Fenghuang Wu; Hao Zhang; John Beardall; C. Elisa Schaum; Xuejia He; Xiao Liang; Mengcheng Ye; Jiamin Lin; Jingyao Li; Baoyi Peng; Leyao Xu; Yuan Jia; et al. (Global Change Biology, 2025)
Rising CO 2 and warming are key components of climate change that are reshaping ecosystems by altering trophic interactions. Although a large body of literature describes changes in biomass in response to these drivers, the biochemical mechanisms driving these shifts remain unclear. This study investigated the long‐term response of the marine diatom Thalassiosira weissflogii to high CO 2 , warming, and their combinations (3.5 years, ~2000 generations) and examined how these changes affect its metabolomic profile and influence a primary consumer (a clam), using metabolomics and biochemical analysis. Our results reveal significant metabolomic shifts in diatoms after 2000 generations, including increased glutaric acid and gluconolactone, reflecting enhanced carbon metabolism and biosynthesis. Warming induces higher pyruvic acid levels and decreased propionic acid, indicating metabolic reprogramming to maintain energy production and redox balance. These biochemical alterations cascade to consumers, creating alterations in metabolite profiles and affecting their energy metabolism, with implications for similar effects on other consumers. These findings highlight the critical role of metabolite‐mediated interactions in shaping food web dynamics under global change. By integrating molecular and ecological perspectives, our study advances the understanding of how environmental drivers affect ecosystem processes such as nutrient cycling, energy flow, and trophic efficiency. We emphasized the need to incorporate metabolomic data into ecological models to predict ecosystem responses to global change.

Deepening and narrowing impacts on circulation, stratification, and sediment transport in the Changjiang Estuary - Jianliang Lin; Bram C. van Prooijen; Chunyan Zhu; Leicheng Guo; Qing He; Zheng Bing Wang; Qingshu Yang (Frontiers in Marine Science, 2025)
Channel deepening and narrowing are common anthropogenic modifications in estuaries, but their combined effects on estuarine circulation, stratification, and sediment transport remain insufficiently understood. This study investigates these combined impacts in the North Passage of the Changjiang Estuary, where large-scale deepening and narrowing have significantly altered hydrodynamic and sediment processes. Our analysis demonstrates that channel deepening intensifies estuarine circulation by strengthening the landward near-bed flow, thereby enhancing sediment import. Contrary to initial expectations that narrowing would promote sediment flushing, our results indicate that narrowing increases stratification, steepens along-estuary salinity gradients, and suppresses vertical mixing. Intensified stratification further reinforces estuarine circulation, promoting sediment trapping at the saltwater intrusion limit. Additionally, enhanced tidal pumping driven by increased velocity and suspended sediment concentration gradients extends the estuarine turbidity maximum both upstream and downstream, a process often overlooked in engineered estuaries. These findings challenge conventional assumptions regarding the sedimentary impacts of narrowing, emphasizing instead its critical role in amplifying estuarine circulation and sediment trapping. Our results provide new insights into sediment dynamics in river-dominated estuaries, with significant implications for estuarine management, dredging operations, water quality control, and long-term morphological stability.

Discordant sibling analysis of autism risk associated with prenatal exposure to tailpipe and non-tailpipe particulate matter pollution - Anny H. Xiang; Jane C. Lin; Ting Chow; Xin Yu; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Michael J. Kleeman; Rob McConnell; Md. Mostafijur Rahman (Environmental Research, 2025)

Temperature effects on the reduction of Se(VI) by natural pyrite - Wujian Jin; Mingliang Kang; Danwen Qin; Jingye She; Zeyue Huang; Lewen Sun; Qiaoya Lin; Hanyu Wu; Andreas C. Scheinost; Damien Prieur (Chemical Geology, 2025)

Diaporthe manilkarae sp. nov. ( Diaporthaceae ) on Manilkara zapota (Sapotaceae) from Guangdong Province, China - Yanhong Lin; Indunil C. Senanayake; Ishara S. Manawasinghe; Yunxia Zhang (New Zealand Journal of Botany, 2025)
Manilkara zapota (L.) P. Royen is an evergreen ornamental and fruit tree distributed in tropical and subtropical regions. In 2022, a leaf spot disease was observed on M . zapota plants in Guangdong Province, China. The putative pathogen was isolated and identified based on morphology and multi‐locus phylogenetic analyses of tub2 , ITS, tef1‐α , cal and his3 . Based on morphology and phylogenetic analyses, the causal agent was identified as a novel species namely Diaporthe manilkarae . Furthermore, pathogenicity essays were conducted using potted seedlings to confirm the pathogenicity. The results revealed that this fungus was able to infect wounded M. zapota leaves and develop typical symptoms similar to field symptoms whereas control and non‐wounded leaves remained asymptomatic. This study will contribute to the knowledge of fungi associated with M. zapota . Further studies are required to understand the pathogenicity of this fungi on other fruit crops.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Targeting sustainable desalination solutions: A techno-economic and life cycle approach to guiding zero liquid discharge desalination - Brandi M. Grauberger; Garrett M. Cole; Tiezheng Tong; Shihong Lin; Jason C. Quinn; Todd Bandhauer (Journal of Cleaner Production, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

The Deep Space Radiation Probe: Development of a first lunar science payload for space environment studies and capacity building - Loren C. Chang; Wei-Yi Lin; Yi-Hsuan Chou; Jen-Siang Lin; Chieh Lung; I. Chen; Kai-Jie Hou; Glenn Franco Gacal; Yi-Chung Chiu; Yushun Wang; Hui-Hui Chou; Chi-Kuang Chao; et al. (Advances in Space Research, 2025)

The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta-Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2025)
A large number of drugs and compounds produced by the chemical and agrochemical industry, often referred to as ‘non-genotoxic carcinogens’ (NGC), score as tumour promotors in rodent models. It is unclear whether these compounds act similarly in humans. The most extensively investigated compounds have been the anti-convulsive drugs, phenobarbital (PB), and phenytoin. Liver tumours induced by PB are dependent upon the activation of the constitutive androstane receptor (CAR). However, marked species differences in CAR activation by exogenous chemicals exist with some being much more potent activators of human CAR, e.g., 6-(4-chlorophenyl)imidazo[2,1-β][1,3]thiazole-5-carbaldehyde-O-(3,4-dichlorobenzyl)oxime (CITCO). We have compared CITCO-induced tumour formation in the livers of mice in which murine CAR has been replaced with its human counterpart. Our findings reveal that CITCO-dependent liver tumours are only formed in mice-expressing human CAR and not in wild-type animals. In addition, contrary to one of the proposed mechanisms of NGC carcinogenicity, we show that CITCO did not induce a hyperplastic response in the liver of the humanised mice. These data raise some key questions about the mechanism of action of NGCs and identify the limitations of current rodent carcinogenicity test systems in relation to risk assessment.

Controlling Levallois: the effect of hammer angle of blow on Levallois flake morphology and fracture trajectory - Sam C. Lin; Matthew McNaughton; Amy Innes; Cecilia Barroso-Medina; Chris Clarkson (Archaeological and Anthropological Sciences, 2025)
Discussions of the Levallois method typically focus on the preparation of the core surface geometry as the primary factor in determining the characteristics of Levallois products. While some studies have acknowledged the role of knapping gestures, there is still limited empirical investigation into how different force application parameters influence the formation of these flakes. This study presents the results from a set of controlled experiments designed to assess the effect of hammer striking angle on the morphology and fracture trajectory of preferential Levallois flakes. By using standardised glass cores with surface morphologies that replicate those of a flintknapped Levallois core, the findings show that variations in the hammer angle of blow significantly alter the direction of fracture propagation through the core. These changes affect how fractures intersect with the core surface convexities, ultimately impacting the size and shape of the detached flakes. The results challenge existing models of conchoidal fracture and highlight the key role that force application variables play in controlling Levallois flaking outcomes. This study has important implications for interpreting the Levallois method in the archaeological record, emphasising the need for further research on the variability of hammer angle of blow in Levallois flake assemblages.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Constraints of the paleowind directions on the paleogeography of the North China, South China and Tarim cratons during the Ediacaran Period - C. L. Hu; Z. Q. Lin; J. A. Quaye; X. B. Fu (Australian Journal of Earth Sciences, 2025)

Mantle metasomatism by subducted Indian continental crust: Evidence from post-collisional basaltic ultrapotassic rocks in southern Tibetan plateau - Miao-Yan Zhang; Lu-Lu Hao; Yue Qi; Qiang Wang; Andrew C. Kerr; Lin Ma; Cheng-Cheng Huang; Gang-Jian Wei; Jie Li; Jin-Long Ma; Qi-Wei Li; Zi-Long Wang; et al. (Lithos, 2025)

Fered-Fenton enhanced boron-doped diamond electrochemical oxidation for wastewater treatment: Antibiotic degradation, kinetics, and environmental effects - C. Chokejaroenrat; K. Poomipuen; K. Techauay; P. Weaoseng; U. Jermnak; H. Chokthaweepanich; N. Suriyachai; Y.-T. Lin; K. Imsilp; C. Sakulthaew (Journal of Water Process Engineering, 2025)

Nutrient recovery from high-salinity dairy wastewater through the cultivation of acclimatized microalgae - Rui Xiao; Erika Carter; Austin Allen; Pei-Lin Tan; Yu-Hua Zheng; Qian Chen; Shun-Ni Zhu; Sudeep C. Popat; Allan Knopf; Clinton F. Williams; Howard H. Chou; Huan Chen (Journal of Water Process Engineering, 2025)

Thin basaltic regolith at the Chang'e-6 landing site - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Wei Yang; Yuyang He; Yi Chen; Roberto Bugiolacchi; Hengci Tian; Honglei Lin; Sen Hu (Earth and Planetary Science Letters, 2025)

Retraction notice to “Production of biochar from tropical fruit tree residues and ecofriendly applications – A review” [Bioresour. Technol. 376 (2023) 128903] - Zheli Ding; Yu Ge; Sarath C. Gowd; Ekta Singh; Vinay Kumar; Deepshi Chaurasia; Vikas Kumar; Karthik Rajendran; Preeti Chaturvedi Bhargava; Peicong Wu; Fei Lin; Sharareh Harirchi; et al. (Bioresource Technology, 2025)

The novel Bacillus thuringiensis HSY204 as a potential bioinsecticide with efficacy against Aedes aegypti larvae - Qi Lin; Jiangyu Wu; Xiao Feng; Pan Yang; Coline C. Jaworski; Shakil Ahmad; Wenfei Zhang (Pesticide Biochemistry and Physiology, 2025)

Combustion of micron-sized iron particles in a drop tube reactor - Ruru Chen; Leon C. Thijs; Brian Brun Hansen; Weigang Lin; Hao Wu; Peter Glarborg; Aki Fujinawa; Xiaocheng Mi (Fuel, 2025)

Exploring the mechanism of flavonoids modification by dimerization strategies and their potential to enhance biological activity - Pengren Zou; Paz Otero; Juan C. Mejuto; Jesus Simal-Gandara; Jianbo Xiao; Carla Cameselle; Shengxiong Chen; Shiye Lin; Hui Cao (Food Chemistry, 2025)

Interactive effects of air pollutants and viral exposure on daily influenza hospital visits in Mongolia - Yihui Ge; Yan Lin; Oyu Tsogtbayar; Ser-Od Khuyagaa; Eelin Khurelbaatar; Jargalsaikhan Galsuren; Lauren Prox; Shiyu Zhang; Robert M. Tighe; Gregory C. Gray; Junfeng Zhang; Daramragchaa Ulziimaa; et al. (Environmental Research, 2025)

Functionality of the MYB1 Transcription Factor in the Transactivation of Leucoanthocyanidin Reductase (LAR) Promoters of Fragaria × Ananassa and Fragaria Chiloensis - Claudia Gómez-Parada; Carlos R. Figueroa; Kui Lin-Wang; Alejandra Moya-León; Richard V. Espley; Andrew C. Allan; Raul Herrera (Journal of Plant Growth Regulation, 2025)

Downregulation of A20 Expression Related to T Cells by Staphylococcal Enterotoxin A Treatment - X. Chen; Y. Yan; C. Lin; J. Yang; H. Qiu (Bulletin of Experimental Biology and Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Policy impact on economic and environmental sustainability of anaerobic digestion: Industrial case study Insights - Tony C Li; Yingqian Lin; Ling Ding; Steve Smith; April Z. Gu (Bioresource Technology, 2025)

Early Postnatal Pharmacological Intervention Rescues the Disruption of Developmental Connectivity in MAO-A KO Mice - Qian Xue; Hanpeng Xu; Muye Zhu; Bin Qian; Lei Gao; Lin Gou; Houri Hintiryan; Jean C. Shih; Hong-Wei Dong (Neuroscience Bulletin, 2025)

Relational characteristics and dynamics between high-tech firms in the Pearl River Delta and the empowerment for technological innovation by Hong Kong - Jili Xu; Anthony G. O. Yeh; George C. S. Lin; Xingjian Liu; Fan Fiona Yang; Zixin Luo (Journal of Geographical Sciences, 2025)

Better objective sleep quality is associated with higher gut microbiota richness in older adults - Maria Teresa Wijaya; Ji-Tseng Fang; Geng-Hao Liu; Yuan-Ming Yeh; Ning-Hung Chen; Chih-Ming Lin; Kuain-Yi Wu; Chih-Mao Huang; Shwu-Hua Lee; Tatia M. C. Lee (GeroScience, 2025)
Aging is associated with disrupted sleep patterns, such as fragmented sleep and reduced efficiency, leading to negative health outcomes. There is evidence of a bidirectional relationship between sleep and gut microbiota, which plays a key role in the gut-brain axis and overall health. However, studies on this relationship in older adults have limited generalizability and show conflicting results, highlighting the need for further research. This study aimed to investigate the associations between sleep quality and gut microbiota composition in healthy Chinese older adults using subjective and objective sleep measures to capture various aspects of sleep quality and explore potential impacts on emotional well-being and cognitive performance. Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while objective sleep quality was measured with actigraphy. Gut microbiota sequencing was performed on stool samples. The results show a robust positive association between gut microbiota richness and objective sleep quality in older adults, independent of subjective sleep quality and demographics, lifestyle, and health covariates. However, no significant link was found between gut microbiota richness and subjective sleep quality. Specific taxa like Bacteroidetes, Ruminococcus , Collinsella , Veillonella , and Holdemania were tentatively linked to sleep quality. These findings emphasize the connection between sleep quality and gut microbiota composition in older adults with potential research and clinical implications, improving our understanding of the mechanisms underlying the sleep-gut microbiota relationship and guiding the development of interventions for improving both sleep quality and gut health in older adults.

Bioactivities, preparation, and bioavailability of food-derived proline-containing peptides - Chenyang Wang; Chibuike C. Udenigwe; Lin Zheng; Mouming Zhao (Trends in Food Science & Technology, 2025)

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

Efficient activation of UV-driven ozonation using ultrasonics for LDPE decomposition - A. Pattanateeradetch; C. Sakulthaew; Y.-T. Lin; A. Watcharenwong; A. Žgajnar Gotvajn; Y.-C. Chen; Q. Xu; C. Chokejaroenrat (Journal of Water Process Engineering, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Evaluation of passive samplers as a cost-effective method to predict the impact of wildfire smoke in grapes and wines - Arran C. Rumbaugh; Chen Liang; Yan Wen; Andrey Khlystov; Dave Campbell; Christopher Wallis; Hao-Lin Fang; Anthony Wexler; Yeongkwon Son (Food Chemistry, 2025)

Development of an electrochemical oxidation processes model: Revelation of process mechanisms and impact of operational parameters on process performance - Xinqing Liao; Zefang Chen; Lin Du; Jiawei Chen; Shaohua Chen; John C. Crittenden; Xiaojun Wang (Chemical Engineering Journal, 2025)

Ground ozone rise during the 2022 shanghai lockdown caused by the unfavorable emission reduction ratio of nitrogen oxides and volatile organic compounds - Qian Wang; Yuewu Li; Fangqian Zhong; Wanqi Wu; Hongliang Zhang; Rong Wang; Yusen Duan; Qingyan Fu; Qing Li; Lin Wang; Shaocai Yu; Abdewahid Mellouki; et al. (Atmospheric Environment, 2025)

Recovery of terephthalic acid from alkali-decrement wastewater by zinc salt-based coagulation - H. Zhu; C. Guo; C. Xu; Y. He; M. Huang; G. Zhou; Y. Lin (International Journal of Environmental Science and Technology, 2025)

Development and use of DJ-1 affinity microcolumns to screen and study small drug candidates for Parkinson's disease - Jacob C. Jones; Jiusheng Lin; Sadia Sharmeen; Md Masudur Rahman; Ha H. Truong; Ting-Rong Chern; Mark A. Wilson; David S. Hage (Analytica Chimica Acta, 2025)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Energy burden and mental health: A national study in the United States - Soojin Han; Ming Hu; Xue Gao; Youqin Huang; Fei Guo; Gordon C. Shen; Donggen Wang; Shao Lin; Kai Zhang (Science of The Total Environment, 2024)

Decomposing the variance: The unique and shared associations of fine and ultrafine particulate matter exposed during pregnancy with child autism spectrum disorder - Xin Yu; Michael J. Kleeman; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Jiu-Chiuan Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Complex basalt evolution in the Chang'e-6 landing area - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Roberto Bugiolacchi; Yuyang He; Wei Yang; Honglei Lin; Hengci Tian; Sen Hu (Earth and Planetary Science Letters, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Imaged capillary isoelectric focusing method development for charge variants of high DAR ADCs - Chuan Leng; Shuwen Sun; Wei Lin; Jorge Alexander Pavon; Lynn Gennaro; Rico C. Gunawan; Xiaodong Bu; Tong Yang; Senwu Li (Analytica Chimica Acta, 2024)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Bimetallic MIL-68(InFe) MOF nanorods for biomimetic photocatalytic N2 fixation - Cheng Liu; Mengning Chen; Yueling Chen; Qi Chen; Jionghua Wu; Sen Lin; Ling Wu; Jimmy C. Yu (Chemical Engineering Journal, 2024)

Examining the sensitivity of ozone to NOx and VOCs in the Salt Lake City urban region from spatiotemporal patterns observed using stationary and mobile observations collected from a light-rail public transit platform - Andres Gonzalez; Derek Mallia; John C. Lin; Logan Mitchell; Taylor Y. Wilmot; Nancy Daher; Mark Sghiatti; Colin Harkins (Atmospheric Environment, 2024)

Population Pharmacokinetics of Casirivimab and Imdevimab in Pediatric and Adult Non-Infected Individuals, Pediatric and Adult Ambulatory or Hospitalized Patients or Household Contacts of Patients Infected with SARS-COV-2 - Kuan-Ju Lin; Kenneth C. Turner; Maria Rosario; Lutz O. Harnisch; John D. Davis; A. Thomas DiCioccio (Pharmaceutical Research, 2024)
Introduction Casirivimab (CAS) and imdevimab (IMD) are two fully human monoclonal antibodies that bind different epitopes on the receptor binding domain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and block host receptor interactions. CAS + IMD and was developed for the treatment and prevention of SARS-CoV-2 infections. Methods A population pharmacokinetic (PopPK) analysis was conducted using pooled data from 7598 individuals from seven clinical studies to simultaneously fit concentration–time data of CAS and IMD and investigate selected covariates as sources of variability in PK parameters. The dataset comprised CAS + IMD-treated pediatric and adult non-infected individuals, ambulatory or hospitalized patients infected with SARS-CoV-2, or household contacts of patients infected with SARS-CoV-2. Results CAS and IMD concentration–time data were both appropriately described simultaneously by a two-compartment model with first-order absorption following subcutaneous dose administration and first-order elimination. Clearance estimates of CAS and IMD were 0.193 and 0.236 L/day, respectively. Central volume of distribution estimates were 3.92 and 3.82 L, respectively. Among the covariates identified as significant, body weight and serum albumin had the largest impact (20–34%, and ~ 7–31% change in exposures at extremes, respectively), while all other covariates resulted in small differences in exposures. Application of the PopPK model included simulations to support dose recommendations in pediatrics based on comparable exposures of CAS and IMD between different weight groups in pediatrics and adults following weight-based dosing regimens. Conclusions This analysis provided important insights to characterize CAS and IMD PK simultaneously in a diverse patient population and informed pediatric dose selection.

Correction to: Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Diagnostic applicability of mitogenomics in uncovering intraspecific carangid diversifications: insights into phylogeny, divergence time, and characterization of two cryptic Selaroides leptolepis mitogenomes - Lorenzo C. Halasan; Hsiu-Chin Lin (Organisms Diversity & Evolution, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

The different adsorption-degradation behaviors of SARS-CoV-2 by bioactive chemicals in wastewater: The suppression kinetics and their implications for wastewater-based epidemiology - Mohamed Bayati; Hsin-Yeh Hsieh; Shu-Yu Hsu; Sally Qasim; Chenhui Li; Anthony Belenchia; Jessica Klutts; Sally A. Zemmer; Kristen Sibley; Melissa Reynolds; Elizabeth Semkiw; Hwei-Yiing Johnson; et al. (Science of The Total Environment, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Computationally efficient Watershed-Scale hydrological Modeling: Integrating HYDRUS-1D and KINEROS2 for coupled Surface-Subsurface analysis - Menberu B. Meles; Lin Chen; Carl Unkrich; Hoori Ajami; Scott A. Bradford; Jiří Šimůnek; Dave C. Goodrich (Journal of Hydrology, 2024)

Enzymatic characterization and synergistic effects of protease combinations on DPP-IV inhibitory peptide release from bovine casein - Chenyang Wang; Lin Zheng; Chibuike C. Udenigwe; Lianzhu Lin; Mouming Zhao (Food Bioscience, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Etiology and treatment of cancer-related secondary lymphedema - Michael Bernas; Sara Al-Ghadban; Saskia R. J. Thiadens; Karen Ashforth; Walter C. Lin; Bauback Safa; Rudolf Buntic; Michael Paukshto; Alexandra Rovnaya; Margaret L. McNeely (Clinical & Experimental Metastasis, 2024)

Themes, Rates, and Risk of Adverse Events of the Artificial Pancreas in the United States Using MAUDE - Andrew M. Ferguson; Alex C. Lin (Annals of Biomedical Engineering, 2024)
Three manufacturers sell artificial pancreas systems in the United States for management of Type 1 Diabetes. Given the life-saving task required of an artificial pancreas there needs to be a high level of trust and safety in the devices. This evaluation sought to find the adjusted safety event reporting rate and themes along with device-associated risk in events reported utilizing the MAUDE database. We searched device names in the MAUDE database over the period from 2016 until August 2023 (the date of retrieval). Thematic analysis was performed using dual-reviewer examination with a 96% concurrence. Relative risk (RR) was calculated for injury, malfunction, and overall, for each manufacturer, as well as adjusted event rate per manufacturer. Most events reported related to defects in the manufacturing of the casing materials which resulted in non-delivery of therapy. Tandem Diabetes Care, Inc. had an adjusted event rate of 50 per 100,000 units and RR of 0.0225. Insulet had an adjusted event rate of 300 per 100,000 units and RR of 0.1684. Medtronic has an adjusted event rate of 2771.43 per 100,000 units and RR of 20.7857. The newer Medtronic devices show improvements in likely event rate. While the artificial pancreas is still in its infancy, these event rates are not at an acceptable level for a device which can precipitate death from malfunctions. Further exploration into safety events and much more research and development is needed for devices to reduce the event rates. Improved manufacturing practices, especially the casing materials, are highly recommended. The artificial pancreas holds promise for millions but must be improved before it becomes a true life-saving device that it has the potential to become.

Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Challenges in assessing and managing multi-hazard risks: A European stakeholders perspective - Robert Šakić Trogrlić; Karina Reiter; Roxana L. Ciurean; Stefania Gottardo; Silvia Torresan; Anne Sophie Daloz; Lin Ma; Noemi Padrón Fumero; Sharon Tatman; Stefan Hochrainer-Stigler; Marleen C. de Ruiter; Julius Schlumberger; et al. (Environmental Science & Policy, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Decoding the influence of low temperature on biofilm development: The hidden roles of c-di-GMP - Yu-Ting Lin; Yong-Chao Wang; Yi-Mei Xue; Zhen Tong; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden; Can Wang (Science of The Total Environment, 2024)

Stochastic processes shape microbial community assembly in biofilters: Hidden role of rare taxa - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Ye Deng; Yu-Ting Lin; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden (Bioresource Technology, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Future changes in intense tropical cyclone hazards in the Pearl River Delta region: an air-wave-ocean coupled model study - Zhenning Li; Jimmy C. H. Fung; Mau Fung Wong; Shangfei Lin; Fenying Cai; Wenfeng Lai; Alexis K. H. Lau (Natural Hazards, 2024)
The Pearl River Delta (PRD) region is highly vulnerable to tropical cyclone (TC)-caused coastal hazards due to its long and meandering shoreline and well-developed economy. With global warming expected to continue or worsen in the rest of the twenty-first century, this study examines the TC impact on the PRD coastal regions by reproducing three intense landfalling TCs, namely Vicente (2012), Hato (2017), Mangkhut (2018), using a sophisticated air-wave-ocean coupled model of high spatial resolution (1-km atmosphere and 500-m wave and ocean). The simulations are conducted using present-day reanalysis data and the same TCs occurring in a pseudo-global warming scenario projected for the 2090s. Results indicate that the coupled model accurately reproduces the air-wave-ocean status during the TC episodes. The 2090s thermodynamic status effectively increases the intensity of intense TCs, leading to more severe coastal hazards including gale, rainstorm, and storm surges and waves. On average, the maximum surface wind speed within 50–200 km to the right of the TC center can increase by 4.3 m/s (+22%). The 99th and the 99.9th percentile of accumulated rainfall will increase from 405 to 475 mm (+17.3%), and from 619 to 735 mm (+18.6%), respectively. The maximum significant wave height at the ocean is lifted by an average of 57 cm (+13.8%), and the coastline typically faces a 40–80 cm increase. The maximum storm surges are lifted by 30–80 cm over the open sea but aggravate much higher along the coastline, especially for narrowing estuaries. For Typhoon Vicente (2012), there is more than a 200 cm wave height increase observed both at open sea and along the coastline. In the 2090s context, a combination of mean sea level rise, storm surge, and wave height can reach more than 300 cm increase in total water level at certain hot-spot coastlines, without considering the superposition of spring tides.

Hysteresis area at the canopy level during and after a drought event in the Central Amazon - Bruno O. Gimenez; Daisy C. Souza; Niro Higuchi; Robinson I. Negrón-Juárez; Israel de Jesus Sampaio-Filho; Alessandro C. Araújo; Adriano J.N. Lima; Clarissa G. Fontes; Kolby J. Jardine; Charles D. Koven; Lin Meng; Gilberto Pastorello; et al. (Agricultural and Forest Meteorology, 2024)

Characteristics and impacts of fine particulates from the largest power plant plume in Taiwan - Ming-Tung Chuang; Charles C.-K Chou; Chung-Te Lee; Ja-Huai Lee; Wei-Che Lin; Chuan-Yao Lin; Wei-Nai Chen; Yi-Ying Chen; Kai-Hsien Chi (Atmospheric Pollution Research, 2024)

Enhanced removal of rare earth elements from aqueous media: exploring the potential of AM-3 and AM-4 titanosilicates - Joana C. Almeida; Cátia Sousa; Daniela S. Tavares; João Pinto; Bruno Henriques; Zhi Lin; João Rocha; Eduarda Pereira (Environmental Science and Pollution Research, 2024)
This study investigates the impact of three key variables on the performance of nanoporous AM-3 and layered AM-4 titanosilicates in removing nine REEs (Y, La, Ce, Pr, Nd, Eu, Gd, Tb, and Dy) from natural mineral water and identifies optimal operational conditions using Response Surface Methodology (RSM). The experimental conditions were determined by a Box-Behnken Design of 3 factors-3 levels (pH 4, 6, and 8; sorbent dose 20, 100, and 180 mg/L; and element concentration 1, 3, and 5 μmol/L). Three-dimensional response surfaces were used to assess the linear, quadratic, and interaction influences of each factor on the REEs’ removal percentage. The pH was the most significant factor in the removal process using AM-3, while the sorbent dose was more important for AM-4. The results highlighted the sorbents’ strong capacity for REE removal. The optimal operating conditions obtained by RSM were applied to aqueous solutions with salinity 10 (common in coastal and transitional systems) and 30 (average seawater salinity). The results showed that AM-3 has a strong potential for removing REEs in solutions with salinity 10 and 30, while AM-4 was less efficient due to competition between REEs and other ions present in the solution.

Atmospheric CO2 and 14CO2 observations at the northern foot of the Qinling Mountains in China: Temporal characteristics and source quantification - Wanyu Liu; Zhenchuan Niu; Xue Feng; Weijian Zhou; Dan Liang; Mengni Lyu; Guowei Wang; Xuefeng Lu; Lin Liu; Jocelyn C. Turnbull (Science of The Total Environment, 2024)

Observing glacial isostatic adjustment by PSInSAR in southern Hudson Bay - Chong-You Wang; Yunung Nina Lin; Cheinway Hwang; C K Shum (Remote Sensing of Environment, 2024)

KOH-activated biochar and chitosan composites for efficient adsorption of industrial dye pollutants - Xu Su; Xuanming Wang; Ziyi Ge; Zhengrong Bao; Li Lin; Yixuan Chen; Wanning Dai; Yuanyuan Sun; Hechong Yuan; Wen Yang; Jun Meng; Hailong Wang; et al. (Chemical Engineering Journal, 2024)

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Evaluating the Educational Value of Cancer Registries — a Systematic Review and Thematic Analysis - James Lin; Hugo C. Temperley; Kirsten Larkins; Caitlin Waters; Kit Loong Chong; Jack Maida; David Proud; Adele Burgess; Alexander Heriot; Philip Smart; Helen Mohan (Journal of Cancer Education, 2024)

Effect of trigger system on experimental dispersion characteristics of active surface wave testing - Shibin Lin; Jeramy C. Ashlock; Liming Zhu; Zexiang Qin; Bo Li; Xingji Zhu; Changhai Zhai (Earthquake Engineering and Engineering Vibration, 2024)

Variability and distribution of nighttime equatorial to mid latitude ionospheric irregularities and vertical plasma drift observed by FORMOSAT-5 Advanced Ionospheric Probe in-situ measurements from 2017 – 2020 - Loren C. Chang; Yueh-Chun Hsieh; Chi-Kuang Chao; Yi Duann; Cornelius Csar Jude H. Salinas; Jann-Yenq Liu; Charles C.H. Lin (Advances in Space Research, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Population parameters and heterogeneity in survival rates of Indo-Pacific humpback dolphins in a heavily urbanized coastal region of southeast China: implications for conservation - Wenzhi Lin; Leszek Karczmarski; Stephen C. Y. Chan; Ruiqiang Zheng; Yuen-Wa Ho; Yaqian Mo (Frontiers in Marine Science, 2024)
The Pearl River Delta (PRD) region on the southeast coast of China is among the largest and most populated metropolitan regions of the world, subjecting the Indo-Pacific humpback dolphins ( Sousa chinensis ) inhabiting coastal waters of this region – apparently the largest population of this species – to intense anthropogenic pressure. In this 5-year study (2011-2015), we applied mark-recapture techniques to quantify population parameters of humpback dolphins in the main body of the extensive estuarine system of the Pearl River, the Lingding Bay (LB), the most urbanized and industrialized part of PRD. The super-population size was estimated at 928 individuals (95% CI=823-1046), which however over-represents the latest number of extant animals. Annual estimates fluctuated between 708 and 750 dolphins, and likely reflect most accurately the latest/current number of humpback dolphins in waters of LB. Both the overall and annual estimates generated by our study are considerably lower than previously published abundance estimates. Apparent survival rates were generally low, estimated at 0.943 (SE = 0.008, 95% CI = 0.929-0.958) and 0.815 (SE = 0.025, 95% CI = 0.766-0.866) for adults and juveniles, respectively. In conjunction with limited recruitment, they may have led to a substantial decline in population numbers over the past two decades. Notably, dolphins exhibited heterogeneous apparent survival rates across the complex anthropogenic seascape of LB. Adult individuals that use Hong Kong waters as their primary habitat exhibited 6.2% higher survival rates than those in other parts of LB. This difference tripled (19.2%) for juveniles, a likely expression of their susceptibility to environmental and/or anthropogenic stresses. We suggest that the difference in survival is largely due to heterogeneous anthropogenic stressors that vary spatially across the estuary, among which habitat loss, pollution, and declining prey resources appear to be the primary threats. Based on our latest findings, we call for a strategic conservation planning with the highest priority given to preserve the remaining key dolphin habitats in Hong Kong waters, and to quantify and mitigate the impacts of major stressor(s) in Guangdong (mainland China) waters. Given the encroachment of ever-more-intense human activities on the coastal habitats of humpback dolphins, understanding their demographic response and the underlying mechanisms of the population processes may prove instrumental in the formulation of a conservation management strategy that can secure their continuous survival.

Hazard and risk characterization of 56 structurally diverse PFAS using a targeted battery of broad coverage assays using six human cell types - Lucie C. Ford; Hsing-Chieh Lin; Han-Hsuan D. Tsai; Yi-Hui Zhou; Fred A. Wright; Alexander Sedykh; Ruchir R. Shah; Weihsueh A. Chiu; Ivan Rusyn (Toxicology, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Climate-driven changes to the spatial–temporal pattern of endangered tree Toona ciliata Roem. in China - Chunping Xie; Meng Li; Lin Chen; C. Y. Jim (Theoretical and Applied Climatology, 2024)

Contaminants of emerging concern reduction and microbial community characterization across a three-barrier advanced water treatment system - Tatiana C. Guarin; Lin Li; Laura Haak; Lydia Teel; Krishna R. Pagilla (Science of The Total Environment, 2024)

Cost-effectiveness analysis of insecticide ban aimed at preventing Parkinson's disease in Central California - Shiwen Li; Roch A. Nianogo; Yuyuan Lin; Hanwen Wang; Yu Yu; Kimberly C. Paul; Beate Ritz (Science of The Total Environment, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Microbial metabolic flexibility guarantees function resilience in response to starvation disturbance - Yong-Chao Wang; Ya-Hui Lv; Xu-Rui Hu; Yu-Ting Lin; John C. Crittenden; Can Wang (Bioresource Technology, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Impacts of sights and sounds on anxiety relief in the high-density city - Wenyan XU; Huaqing WANG; Hua SU; William C. SULLIVAN; Guangsi LIN; Mathew PRYOR; Bin JIANG (Landscape and Urban Planning, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Inclusive simulation game development to enhance Florida research and management: Cedar Key oyster fishery - Chad R. Palmer; Denis Valle; Edward V. Camp; Wendy-Lin Bartels; Martha C. Monroe (Environmental Modelling & Software, 2024)

Exposure to phenols reduces melanogenesis in B16F10 cells and zebrafish - Chung-Yu Lin; Chang-Yi Wu; Chia C. Wang; Che-Hsin Lee (Aquatic Toxicology, 2024)

Investigation of the Artificial Saliva and Saline Droplet Size Measurement Accuracy for COVID-19 Infection Control - Thomas Y. Wu; Yi-Hung Liu; Fang-hsin Lin; Yue Liu; Junjie Liu; Jinsang Jung; Wesley Zongrong Yu; Qinde Liu; Richard Y. C. Shin; Tang Lin Teo (Aerosol Science and Engineering, 2023)

On the harmonic correction in the gravity field determination - Meng Yang; Xiaopeng Li; Miao Lin; Xiao-Le Deng; Wei Feng; Min Zhong; C. K. Shum; Daniel R. Roman (Journal of Geodesy, 2023)

Are associations between obesity and prostate cancer outcomes following radical prostatectomy the same in smokers and non-smokers? Results from the SEARCH Cohort - Ivy T. Liu; Lin Gu; Amanda M. De Hoedt; Matthew R. Cooperberg; Christopher L. Amling; Christopher J. Kane; Zachary Klaassen; Martha K. Terris; Lourdes Guerrios-Rivera; Adriana C. Vidal; William J. Aronson; Stephen J. Freedland; et al. (Cancer Causes & Control, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Recycling of subducted Indian continental crust constrained by late Cretaceous mafic dykes in Central Lhasa block of the Tibetan plateau - Lu-Lu Hao; Andrew C. Kerr; Qiang Wang; Lin Ma; Yue Qi; Ming Xiao; Quan Ou (Lithos, 2023)

Did Early Pleistocene hominins control hammer strike angles when making stone tools? - Li Li; Jonathan S. Reeves; Sam C. Lin; David R. Braun; Shannon P. McPherron (Journal of Human Evolution, 2023)

Remediation of arsenic contaminated water and soil using mechanically (ball milling) activated and pyrite-amended electrolytic manganese slag - Zhihao Ha; Mengyu Ma; Xiaohan Tan; Yanxin Lan; Yanmin Lin; Tian C. Zhang; Dongyun Du (Environmental Research, 2023)

Cellulose supported and strengthened shear stiffening gel with enhanced impact-resistant performance - Zhen Zhang; Xiaoming Lin; Junyi Lin; Nana Liu; Bolin Wan; Xiong Fang; Lingling Shui; Yingzhan Li; Kam C. Tam; Jin Huang; Guofu Zhou (Chemical Engineering Journal, 2023)

Towards hyperlocal source identification of pollutants in cities by combining mobile measurements with atmospheric modeling - John C. Lin; Ben Fasoli; Logan Mitchell; Ryan Bares; Francesca Hopkins; Tammy M. Thompson; Ramón A. Alvarez (Atmospheric Environment, 2023)

Field reconnaissance and observations from the February 6, 2023, Turkey earthquake sequence - Gulen Ozkula; Robert K. Dowell; Tugce Baser; Jui-Liang Lin; Ozgun A. Numanoglu; Okan Ilhan; C. Guney Olgun; Cheng-Wei Huang; Tunc Deniz Uludag (Natural Hazards, 2023)

Characterization of fouled ultrafiltration membranes from a full-scale wastewater reclamation plant in iron and steel industry - P.-H. Lin; Y.-C. Su; C.-L. Chen; I.-Y. Tsao (International Journal of Environmental Science and Technology, 2023)

Supplement use and gastric cancer risk in the Southern Community Cohort Study - Jessica C. Goodwin; Qichen Wang; Pao-Hwa Lin; Martha J. Shrubsole; Meira Epplein (Cancer Causes & Control, 2023)

Caterpillar Salivary Glucose Oxidase Decreases Green Leaf Volatile Emission and Increases Terpene Emission from Maize - Anne C. Jones; Po-An Lin; Michelle Peiffer; Gary Felton (Journal of Chemical Ecology, 2023)

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Jansen Smith; Marina C. Rillo; Ádám T. Kocsis; Maria Dornelas; David Fastovich; Huai‐Hsuan M. Huang; Lukas Jonkers; Wolfgang Kiessling; Qijian Li; Lee Hsiang Liow; Miranda Margulis‐Ohnuma; Stephen Meyers; et al. (Global Ecology and Biogeography, 2023)
Motivation We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present‐day to millions of years ago. Main Types of Variables Included BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm 2 to grid cells of ~100 km 2 . Time Period and Grain BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format SQLite, Comma‐separated values.

Metal sulfide-based Z-scheme heterojunctions in photocatalytic removal of contaminants, H2 evolution and CO2 reduction: Current status and future perspectives - Fang Deng; Junlong Peng; Xibao Li; Xubiao Luo; Priyanka Ganguly; Suresh C. Pillai; Bangxing Ren; Lin Ding; Dionysios D. Dionysiou (Journal of Cleaner Production, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Development of a 10-m resolution maize and soybean map over China: Matching satellite-based crop classification with sample-based area estimation - Haijun Li; Xiao-Peng Song; Matthew C. Hansen; Inbal Becker-Reshef; Bernard Adusei; Jeffrey Pickering; Li Wang; Lei Wang; Zhengyang Lin; Viviana Zalles; Peter Potapov; Stephen V. Stehman; et al. (Remote Sensing of Environment, 2023)

Genetic-simulated annealing optimization for surface wave inversion of shear-wave velocity profiles of geotechnical sites - Shibin Lin; Jeramy C. Ashlock; Guochen Zhao; Qinghui Lai; Longjun Xu; Changhai Zhai (Computers and Geotechnics, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Carbon distribution and multi-criteria decision analysis of flexible waste biomass smouldering processing technologies - Yuying Chen; Shaorun Lin; Yunzhu Qin; Nicholas C. Surawski; Xinyan Huang (Waste Management, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Identification of Heterotopic Mineralization and Adjacent Pathology in the Equine Fetlock Region by Low-Field Magnetic Resonance Imaging, Cone-Beam and Fan-Beam Computed Tomography - Szu-Ting Lin; Vanessa G. Peter; Stefano Schiavo; Rachel Pokora; Hayley Patrick; Nick Bolas; Alastair K. Foote; David R. Sargan; Rachel C. Murray (Journal of Equine Veterinary Science, 2023)

Cost-effective and accurate monitoring of flowering across multiple tropical tree species over two years with a time series of high-resolution drone imagery and deep learning - Calvin Ka Fai Lee; Guangqin Song; Helene C. Muller-Landau; Shengbiao Wu; S. Joseph Wright; K.C. Cushman; Raquel Fernandes Araujo; Stephanie Bohlman; Yingyi Zhao; Ziyu Lin; Zounachuan Sun; Peter Chuen Yan Cheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

Efficient adsorption and photocatalytic degradation of water emerging contaminants through nanoarchitectonics of pore sizes and optical properties of zirconium-based MOFs - Jia-Xuan Tan; Zih-Yu Chen; Celine H. Chen; Ming-Feng Hsieh; Angela Yu-Chen Lin; Season S. Chen; Kevin C.-W. Wu (Journal of Hazardous Materials, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

A Letter to Your Care Providers: Implementation and Analysis of a Letter-based Advance Care Planning Initiative for Gynecologic Oncology Patients - Catherine N. Zivanov; Anne Coogan; Robin R. Lane; Sara G. Lin; Sarah C. Reed; Marc A. Robinson; Mohana Karlekar; Lauren S. Prescott; Alaina J. Brown (Journal of Cancer Education, 2023)

Differences in the occurrence of leg glands between the social parasite S. mutica (Brown, 1949) and other Strumigenys ants - C. Wang; F.-Y. Chung; C.-C. Lin; J. Billen (Insectes Sociaux, 2023)

Solubility controls on plutonium and americium release in subsurface environments exposed to acidic processing wastes - Hilary P. Emerson; Sergey I. Sinkov; Carolyn I. Pearce; Kirk J. Cantrell; Calvin H. Delegard; Michelle M.V. Snyder; May-Lin Thomas; Dallas D. Reilly; Edgar C. Buck; Lucas E. Sweet; Amanda J. Casella; Jennifer C. Carter; et al. (Applied Geochemistry, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Impact of Organ Impairment on the Pharmacokinetics of Therapeutic Peptides and Proteins - Elimika Pfuma Fletcher; Martina Sahre; Yuen Yi Hon; Anand Balakrishnan; Lin Zhou; Qin Sun; Jie Wang; Kimberly Maxfield; Raajan Naik; Shiew Mei Huang; Yow-Ming C. Wang (The AAPS Journal, 2023)

Material flow analysis of commercial fishing gears in Taiwan - Ching-Tuan Su; Falk Schneider; Paritosh C. Deshpande; Hui-Ya Xiao; Tien-An Su; Ning Yen; Hsin-Tien Lin (Marine Pollution Bulletin, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Inactivation of Microcystis aeruginosa by H2O2 generated from a carbon black polytetrafluoroethylene gas diffusion electrode in electrolysis by low-amperage electric current - Yuting Zhang; Li Lin; Di Jia; Lei Dong; Xiong Pan; Min Liu; Huawei Huang; Yuan Hu; John C. Crittenden (Environmental Pollution, 2023)

RETRACTED: Production of biochar from tropical fruit tree residues and ecofriendly applications – A review - Zheli Ding; Yu Ge; Sarath C. Gowd; Ekta Singh; Vinay Kumar; Deepshi Chaurasia; Vikas Kumar; Karthik Rajendran; Preeti Chaturvedi Bhargava; Peicong Wu; Fei Lin; Sharareh Harirchi; et al. (Bioresource Technology, 2023)

Probing air pollution in the Taichung metropolitan area, Taiwan.Part 1: Comprehensive model evaluation and the spatial-temporal evolution of a PM2.5 pollution event - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Wei-Nai Chen; Chian-Yi Liu; Chih-Chung Chang (Atmospheric Research, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Embedded information of aerosol type, hygroscopicity and scattering enhancement factor revealed by the relationship between PM2.5 and aerosol optical depth - Kuo-En Chang; Ta-Chih Hsiao; Si-Chee Tsay; Tang-Huang Lin; Stephen M. Griffith; Chian-Yi Liu; Charles C.-K. Chou (Science of The Total Environment, 2023)

Incongruities in recently revised radiofrequency exposure guidelines and standards - James C. Lin (Environmental Research, 2023)

Evolvement of carbamazepine under solar irradiation in the presence of chlorine: Efficiency, influences, degradation pathways and ecotoxicity - Haixiang Jia; Xiaoyan Y. Ma; Yu Lin; Shengjiong Yang; Yali An; Yihan Chen; Xiaochang C. Wang (Chemical Engineering Journal, 2023)

Historical biomonitoring of pollution trends in the North Pacific using archived samples from the Continuous Plankton Recorder Survey - Kefeng Li; Jane C. Naviaux; Sai Sachin Lingampelly; Lin Wang; Jonathan M. Monk; Claire M. Taylor; Clare Ostle; Sonia Batten; Robert K. Naviaux (Science of The Total Environment, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

The spongiform tissue in Strumigenys ants contains exocrine glands - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Joshua C. Gibson; Sara McGuire; Andrew V. Suarez; Johan Billen (Arthropod Structure & Development, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Efficient degradation of triclosan by aluminium acetylacetonate doped polymeric carbon nitride photocatalyst under visible light - Danyan Sun; Xiaohu Lin; Jingcheng Xu; Zhibo Lu; Juwen Huang; Shiyi Li; Luiza C. Campos (Journal of Environmental Chemical Engineering, 2023)

Tire wear particles: An emerging threat to soil health - Jing Ding; Min Lv; Dong Zhu; Eva F. Leifheit; Qing-Lin Chen; Yun-Qing Wang; Ling-Xin Chen; Matthias C. Rillig; Yong-Guan Zhu (Critical Reviews in Environmental Science and Technology, 2023)

Relative sensitivity of hydrodynamic, thermodynamic, and chemical processes for simulating the buoyant multiphase plume and surfacing flows of an oil and gas blowout - Anusha L. Dissanayake; Scott A. Socolofsky; Jonas Gros; Inok Jun; Lin Zhao; Michel C. Boufadel; J. Samuel Arey (Marine Pollution Bulletin, 2023)

Phase-velocity and intercept-time scanning (PIS) technique for extracting experimental dispersion characteristics of surface waves - Shibin Lin; Jeramy C. Ashlock; Li-Li Xie (Soil Dynamics and Earthquake Engineering, 2023)

Hemoglobin normalization outperforms other methods for standardizing dried blood spot metabolomics: A comparative study - Abhishek Jain; Montana Morris; Elizabeth Z. Lin; Sajid A. Khan; Xiaomei Ma; Nicole C. Deziel; Krystal J. Godri Pollitt; Caroline H. Johnson (Science of The Total Environment, 2023)

Pollen in the Baltic Sea as viewed from space - Chuanmin Hu; Lin Qi; David C. English; Menghua Wang; Karlis Mikelsons; Brian B. Barnes; Magdalena M. Pawlik; Dariusz Ficek (Remote Sensing of Environment, 2023)

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Activated peroxydisulfate by sorghum straw-based biochar for enhanced tartrazine degradation: Roles of adsorption and radical/nonradical processes - Xiaojuan Chen; Yu Zhou; Jiesen Li; Suresh C. Pillai; Nanthi Bolan; Juhua He; Ning Li; Song Xu; Xin Chen; Qinghua Lin; Hailong Wang (Environmental Pollution, 2023)

Spatial and seasonal variations in the carbon and lead isotopes of PM2.5 in air of residential buildings and their applications for source identification - Chien-Cheng Jung; Yang-Hsueh Chen; Charles C.-K. Chou; Yi-Tang Huang; Kuan-Ting Lin (Environmental Pollution, 2023)

Associations between DNA methylation and genotoxicity among lead-exposed workers in China - Tuanwei Wang; Yu Meng; Yuting Tu; Guanghui Zhang; Kan Wang; Shiyang Gong; Yunxia Zhang; Tongshuai Wang; Anqi Li; David C. Christiani; William Au; Zhao-lin Xia (Environmental Pollution, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Cover Image - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)

Exogenous polyunsaturated fatty acids ( PUFAs ) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A ‐layer strain of Aeromonas salmonicida - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)
Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore the ability of non‐A‐layer and A‐layer A. salmonicida strains to incorporate polyunsaturated fatty acids (PUFAs) into their lipid profile and test the phenotypic effects thereof. Lipids were extracted from PUFA‐exposed cultures and analysed for lipid modification by thin‐layer chromatography and ultraperformance liquid chromatography‐mass spectrometry, showing A. salmonicida , regardless of A‐layer, capable of incorporating all seven of the PUFAs studied. Phenotypic effects were determined through the use of assays that tested for biofilm formation, membrane permeability and cyclic peptide susceptibility. Temperature‐dependent effects on biofilm formation were observed, and PUFA exposure showed significant ( p

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

BCL11B Upregulates the Expression of RelA in T Cells Stimulated with Staphylococcal Enterotoxin A - Y. Yan; S. Wang; C. Lin (Bulletin of Experimental Biology and Medicine, 2022)

Megameter propagation and correlation of T-waves from Kermadec Trench and Islands - Tiago C. A. Oliveira; Peter Nielsen; Ying-Tsong Lin; Noriyuki Kushida; Sérgio M. Jesus (Frontiers in Marine Science, 2022)
On 18 June 2020 and 4 March 2021, very energetic low-frequency underwater T-wave signals (2 to 25 Hz) were recorded at the Comprehensive Nuclear-Test-Ban Treaty (CTBT) International Monitoring System (IMS) hydrophone stations in the Pacific Ocean (Stations HA11 and HA03) and the South Atlantic Ocean (Station HA10). This work investigates the long-range (megameters) propagation of these T-waves. Their sources were three powerful submarine earthquakes in the Kermadec Trench and Islands, located at approximately 6000, 8800, and 15100 km from Stations HA11, HA03, and HA10, respectively. Arrival time and back azimuth of the recorded T-waves were estimated using the Progressive Multi-Channel Correlation algorithm installed on the CTBT Organization (CTBTO) virtual Data Exploitation Centre (vDEC). Different arrivals within the duration of the earthquake signals were identified, and their correlations were also analyzed. The data analysis at HA03 and HA10 revealed intriguing T-wave propagation paths reflecting, refracting, or even transmitting through continents, as well as T-wave excitation along a chain of seamounts. The analysis also showed much higher transmission loss (TL) in the propagation paths to HA11 than to HA03 and HA10. Moreover, strong discrepancies between expected and measured back azimuths were observed for HA11, and a three-dimensional (3D) parabolic equation model was utilized to identify the cause of these differences. Numerical results revealed the importance of 3D effects induced by the Kermadec Ridge, Fiji archipelago, and Marshall Islands on T-wave propagation to HA11. This analysis can guide future improvements in underwater event localization using the CTBT-IMS hydroacoustic sensor network.

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Acanthopagrus oconnorae , a new species of seabream (Sparidae) from the Red Sea - Lucía Pombo‐Ayora; Viktor N. Peinemann; Collin T. Williams; Song He; Yu Jia Lin; Yukio Iwatsuki; Donal D. C. Bradley; Michael L. Berumen (Journal of Fish Biology, 2022)
A new species of sparid fish, Acanthopagrus oconnorae , is described based on 11 specimens collected in the shallow (0–1 m depth) mangrove‐adjacent sandflats of Thuwal, Saudi Arabia. The new species is distinguished from its congeners by the following combination of characters: second anal‐fin spine 12.8%–16.6% of standard length (SL); 3½ scale rows between the fifth dorsal‐fin spine and lateral line; suborbital width 5.7%–6.7% of SL; eyes positioned at the anterior edge of the head, often forming a weakly convex break in an otherwise gently curved head profile, when viewed laterally; caudal fin light yellow with black posterior margin (approximately half of fin); anal fin dusky grey, with posterior one‐fifth of the fin light yellow; black streaks on inter‐radial membranes of anal fin absent. The most similar species to A. oconnorae is Acanthopagrus vagus , which differs by the presence of a w‐shaped anterior edge of the scaled predorsal area, a more acute snout and black streaks on the inter‐radial membranes of the anal fin. Phylogenetic placement and species delimitation of A. oconnorae are discussed based on COI, CytB and 16S sequences. It is hypothesized that ecology and behaviour explain how this species avoided detection despite its likely occurrence in coastal areas of the Red Sea with historically high fishing pressure.

Performance of Semi-passive Systems for the Biological Treatment of High-As Acid Mine Drainage: Results from a Year of Monitoring at the Carnoulès Mine (Southern France) - C. Diaz-Vanegas; C. Casiot; L. Lin; L. De Windt; M. Héry; A. Desoeuvre; O. Bruneel; F. Battaglia-Brunet; J. Jacob (Mine Water and the Environment, 2022)

Spatial patterns and driving factors of carbon stocks in mangrove forests on Hainan Island, China - Yuchen Meng; Ruikun Gou; Jiankun Bai; David Moreno‐Mateos; Charles C. Davis; Luoma Wan; Shanshan Song; Hongsheng Zhang; Xiaoshan Zhu; Guanghui Lin (Global Ecology and Biogeography, 2022)
Aim Mangrove forests are important coastal wetlands for the blue carbon budget and play a significant role in mitigating global climate change. However, spatial patterns of carbon stocks in mangrove forests on an island scale have not been quantified owing to methodological limitations and lack of understanding of controlling factors. We took the entire Hainan Island as a case study and aimed to carry out a comprehensive investigation of the spatial patterns and driving factors of carbon stocks in mangrove forests. Location Southern China. Time period 2017–2020. Major taxa studied Mangrove forest. Methods The upscaling method combined with field surveys and Sentinel‐2 imagery analysis were used to compare different models for optimization of mangrove ecosystem carbon stock estimations. We also used structural equation modelling (SEM) to evaluate the factors driving the distributional patterns of mangrove carbon stocks on an island scale. Results The current total mangrove carbon stock of the entire Hainan Island was estimated to be 703,181 Mg C (with a mean density of 192 Mg C/ha), with the above‐ and below‐ground carbon stocks averaging at 44.7 and 147.3 Mg C/ha, respectively. The mangrove carbon storage in the north‐eastern region of the island was the highest and in the west region the lowest. Sediment nitrogen content and plant species diversity had the most positive driving effects on the distribution of total carbon stock for Hainan Island mangroves. Main conclusions The combination of field surveys and Sentinel‐2 imagery analysis can be applied to regional‐scale estimations of carbon stocks for mangrove forests. Spatial pattens of mangrove carbon stocks vary among locations on Hainan Island, and soil nutrient (especially nitrogen) availability is the dominant factor regulating carbon stock variations along the land‐to‐sea gradient. Our findings have significant implications for better understanding the distribution of mangrove carbon stocks and quantification of the global blue carbon budget.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Extended Middle Cerebral Artery Occlusion (MCAO) Model to Mirror Stroke Patients Undergoing Thrombectomy - Sarah J. Messmer; Kathleen E. Salmeron; Jacqueline A. Frank; Christopher J. McLouth; Douglas E. Lukins; Tyler C. Hammond; Ai-Ling Lin; Justin F. Fraser; Keith R. Pennypacker (Translational Stroke Research, 2022)

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Quantifying knapping actions: a method for measuring the angle of blow on flakes - Li Li; Jonathan S. Reeves; Sam C. Lin; Claudio Tennie; Shannon P. McPherron (Archaeological and Anthropological Sciences, 2022)
Stone artifacts are critical for investigating the evolution of hominin behavior—they are among our only proxies for hominin behavior in deep time. Hominin cognition and skill are often inferred by reconstructing the technical decisions hominins made throughout the knapping process. However, despite many advancements in understanding how hominins knapped, some of the key factors involved in past flake production cannot be easily/readily derived from stone artifacts. In particular, the angle at which the knapper strikes the hammer against the core to remove the flake, or the angle of blow, is a key component of the knapping process that has up to now remained unmeasurable on archeological assemblages. In this study, we introduce a new method for estimating the angle of blow from the ventral surface of flakes. This method was derived from a controlled experiment that explicitly connects fracture mechanics to flake variability. We find that a feature of the flake’s bulb of percussion, what we call the bulb angle, is a measurable indicator of the angle of blow. Our experimental finding is further validated in two additional datasets from controlled and replicative knapping experiments. These results demonstrate the utility of continuing to link flake variation with technical decision-making to fracture mechanics. In addition, they also provide a useful and relatively simple means to capture a currently invisible aspect of hominin stone tool production behavior.

The effect of edge serration on the performance of stone-tip projectiles: an experimental case study of the Maros Point from Holocene South Sulawesi - Anton Ferdianto; Suryatman; Fakhri; Budianto Hakim; Thomas Sutikna; Sam C. Lin (Archaeological and Anthropological Sciences, 2022)
Serrated stone points have been documented in a variety of archaeological settings worldwide. In Indonesia, serrated points known as Maros point began to appear during the mid-Holocene as part of the Toalean techno-complex in southern South Sulawesi. Researchers have speculated functional and cultural reason behind the emergence of these distinctive artefact as projectile points, an assumption that has yet to be verified by archaeological data. In particular, the edge serration has been suggested to allow for deeper penetration and/or act as barbs to prevent the easy withdrawal of the points from the target. In this study, we experimentally test these functional hypotheses regarding the effect of edge serration on stone arrowheads resembling Maros points when fired using different bow draw weights. We also investigate variation in breakage and impact fracture pattern between serrated and non-serrated points. Our result show that, compared to the non-serrated points, the serrated arrows not only deliver deeper penetrations, but also require less force to withdraw from the ballistic gel target. However, these relationships are complicated by the inclusion of skin and bone in the ballistic target. The findings demonstrate that the effect of serrated stone points on projectile performance depends on factors such as the projectile delivery system and prey type. Moreover, under identical firing settings, the serrated points develop more variable macrofracture patterns than the non-serrated points, likely owing the irregular edge morphologies. Taking these results together, we discuss the implications of our experimental study on the appearance of Maros points and the Toalean techno-complex in South Sulawesi during the mid-Holocene.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

P75 neurotrophin receptor controls subventricular zone neural stem cell migration after stroke - Sachin S. Deshpande; Subash C. Malik; Pasquale Conforti; Jia-di Lin; Yu-Hsuan Chu; Suvra Nath; Franziska Greulich; Meike-Ast Dumbach; N. Henriette Uhlenhaut; Christian Schachtrup (Cell and Tissue Research, 2022)
Stroke is the leading cause of adult disability. Endogenous neural stem/progenitor cells (NSPCs) originating from the subventricular zone (SVZ) contribute to the brain repair process. However, molecular mechanisms underlying CNS disease-induced SVZ NSPC-redirected migration to the lesion area are poorly understood. Here, we show that genetic depletion of the p75 neurotrophin receptor ( p75 NTR−/− ) in mice reduced SVZ NSPC migration towards the lesion area after cortical injury and that p75 NTR−/− NSPCs failed to migrate upon BDNF stimulation in vitro. Cortical injury rapidly increased p75 NTR abundance in SVZ NSPCs via bone morphogenetic protein (BMP) receptor signaling. SVZ-derived p75 NTR−/− NSPCs revealed an altered cytoskeletal network- and small GTPase family-related gene and protein expression. In accordance, BMP-treated non-migrating p75 NTR−/− NSPCs revealed an altered morphology and α-tubulin expression compared to BMP-treated migrating wild-type NSPCs. We propose that BMP-induced p75 NTR abundance in NSPCs is a regulator of SVZ NSPC migration to the lesion area via regulation of the cytoskeleton following cortical injury.

miR-146a-5p modulates cellular senescence and apoptosis in visceral adipose tissue of long-lived Ames dwarf mice and in cultured pre-adipocytes - Allancer D. C. Nunes; Moritz Weigl; Augusto Schneider; Sarah Noureddine; Lin Yu; Collin Lahde; Tatiana Dandolini Saccon; Kunal Mitra; Esther Beltran; Johannes Grillari; James L. Kirkland; Tamara Tchkonia; et al. (GeroScience, 2022)

Current management of melanoma patients with nodal metastases - Dale Han; Alexander C. J. van Akkooi; Richard J. Straker; Adrienne B. Shannon; Giorgos C. Karakousis; Lin Wang; Kevin B. Kim; Douglas Reintgen (Clinical & Experimental Metastasis, 2022)

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

2D-GolgiTrack—a semi-automated tracking system to quantify morphological changes and dynamics of the Golgi apparatus and Golgi-derived membrane tubules - Jindaporn Yaothak; Jeremy C. Simpson; Linda F. Heffernan; Yuh-Show Tsai; Chung-Chih Lin (Medical & Biological Engineering & Computing, 2022)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Development of a 2D Automated Tracking System to Characterize Golgi-Derived Membrane Tubule Fission and Fusion Dynamics - Jindaporn Yaothak; Jeremy C. Simpson; Linda F. Heffernan; Yuh-Show Tsai; Chung-Chih Lin (Journal of Medical and Biological Engineering, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Bacterial communities in cascade reservoirs along a large river - Qiuwen Chen; Yuchen Chen; Jun Yang; Stephen C. Maberly; Jianyun Zhang; Jinren Ni; Gangsheng Wang; Daniele Tonina; Lin Xiao; Honghai Ma (Limnology and Oceanography, 2021)
Dam construction is widespread, changing the hydrological and biogeochemical conditions and thereby the bacterial communities in the rivers of the earth. To date, knowledge is lacking about bacterial communities in cascade reservoirs. Here, we investigated the bacterial communities and potential functions of nine cascade hydropower reservoirs in 1290 km of the upper Mekong River (Lancang River in China). Along the reservoir cascade, the water temperature, rather than the presence of dams, was the main cause for the geographical patterns of bacterial community composition. Within a reservoir, significant spatial differences in sediment bacterial communities were observed between the tail, middle, and head of a reservoir. The differences in sediment properties resulted by flow velocity‐sieved sedimentation from the tail to head of a reservoir caused the spatial variation in sediment bacteria communities, forming potential hotspots for biogeochemical cycling in the middle of the reservoir. In contrast, unlike in deep lakes and deep single reservoirs, the bacterioplankton community composition had no distinctly layered features in the deep cascade reservoirs, because density‐induced underwater currents and convection resulting from hydropower production reduced the vertical hydro‐environmental gradients. This study provides a novel perspective on the processes affecting the distribution and function of bacterial communities in river‐reservoir cascades, and is a first step toward forecasting the consequences of microbially mediated biogeochemical cycling in existing and future reservoirs worldwide.

First Evidence of Cryptic Species Diversity and Population Structuring of Selaroides leptolepis in the Tropical Western Pacific - Lorenzo C. Halasan; Paul John L. Geraldino; Hsiu-Chin Lin (Frontiers in Marine Science, 2021)
The yellowstripe scad, Selaroides leptolepis (Carangidae), is an important fish commodity in the Tropical Western Pacific (TWP). It has a latitudinal Pacific range from south of Japan down to northern Australia, with the highest concentration in Southeast Asia. However, its TWP fishing grounds have long been a hotspot of unsustainable exploitations, thus threatening the remaining wild populations. Despite the species’ commercial significance, there is limited understanding of its genetic structure and diversity. Herein, the genetic structure of S. leptolepis was examined using mitochondrial COI and CytB sequences. Both markers denoted significant genetic structuring based on high overall F ST values. Hierarchical analysis of molecular variance (AMOVA), maximum likelihood (ML) phylogenetic trees, and median-joining (MJ) haplotype networks strongly supported the occurrence of two allopatrically distributed lineages. These comprised of a widespread Asian lineage and an isolated Australian lineage. Within-lineage distances were low (K2P < 1%) whereas across-lineage distances were remarkably high (K2P > 6%), already comparable to that of interspecific carangid divergences. Haplotype sequence memberships, high genetic variations, and the geographic correlation suggested that the Australian lineage was a putative cryptic species. Historical demographic inferences also revealed that the species experienced rapid expansion commencing on the late Pleistocene, most likely during the end of the Last Glacial Maximum (∼20,000 years ago). The present study encouraged the application of lineage-specific management efforts, as the lineages are experiencing different evolutionary pressures. Overall, accurate knowledge of the species’ genetic distribution is fundamental in protecting its diversity and assuring stock sustainability.

Underwater Sound Propagation Modeling in a Complex Shallow Water Environment - Tiago C. A. Oliveira; Ying-Tsong Lin; Michael B. Porter (Frontiers in Marine Science, 2021)
Three-dimensional (3D) effects can profoundly influence underwater sound propagation in shallow-water environments, hence, affecting the underwater soundscape. Various geological features and coastal oceanographic processes can cause horizontal reflection, refraction, and diffraction of underwater sound. In this work, the ability of a parabolic equation (PE) model to simulate sound propagation in the extremely complicated shallow water environment of Long Island Sound (United States east coast) is investigated. First, the 2D and 3D versions of the PE model are compared with state-of-the-art normal mode and beam tracing models for two idealized cases representing the local environment in the Sound: (i) a 2D 50-m flat bottom and (ii) a 3D shallow water wedge. After that, the PE model is utilized to model sound propagation in three realistic local scenarios in the Sound. Frequencies of 500 and 1500 Hz are considered in all the simulations. In general, transmission loss (TL) results provided by the PE, normal mode and beam tracing models tend to agree with each other. Differences found emerge with (1) increasing the bathymetry complexity, (2) expanding the propagation range, and (3) approaching the limits of model applicability. The TL results from 3D PE simulations indicate that sound propagating along sand bars can experience significant 3D effects. Indeed, for the complex shallow bathymetry found in some areas of Long Island Sound, it is challenging for the models to track the interference effects in the sound pattern. Results emphasize that when choosing an underwater sound propagation model for practical applications in a complex shallow-water environment, a compromise will be made between the numerical model accuracy, computational time, and validity.

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

Safety and tolerability of chronic intranasal oxytocin in older men: results from a randomized controlled trial - Jillian M. Rung; Marilyn Horta; Erin M. Tammi; Eliany Perez; Marite C. Ojeda; Tian Lin; Griffin Harris; Jessie Somerville; Dinia Salmeron; Susan E. Beltz; Bhanuprasad Sandesara; David Feifel; et al. (Psychopharmacology, 2021)

Dosimetric evaluation of a patient-specific 3D-printed oral positioning stent for head-and-neck radiotherapy - Susannah Cleland; Philip Chan; Benjamin Chua; Scott B. Crowe; Jodi Dawes; Lizbeth Kenny; Charles Lin; Elise Obereigner; Samuel C. Peet; Jamie V. Trapp; Tania Poroa; Tanya Kairn (Physical and Engineering Sciences in Medicine, 2021)

Dating deformation using sheared leucogranite: temporal constraints by 40Ar/39Ar thermochronology for the Mae Ping shear zone, NW Thailand - Yu-Ling Lin; Tung-Yi Lee; Ching-Hua Lo; Sarah C. Sherlock; Yoshiyuki Iizuka; Tadashi Usuki; Long Xiang Quek; Punya Charusiri (Contributions to Mineralogy and Petrology, 2021)

A geochemical and isotopic assessment of hydraulic connectivity of a stacked aquifer system in the Lisbon Valley, Utah (USA), and critical evaluation of environmental tracers - Chandler Noyes; Jihyun Kim; Mark Person; Lin Ma; Grant Ferguson; Jennifer C. McIntosh (Hydrogeology Journal, 2021)

Effect of water regime and harvest stage on essential oil accumulation in basil plant growing in sandy soil - João V. R. S. Souza; Lin Chau Ming; Marcos A. L. Santos; James E. Simon; Hector R. Juliani; João C. C. Saad (Irrigation Science, 2021)

Multi‐decade tree mortality in temperate old‐growth forests of Europe and North America: Non‐equilibrial dynamics and species‐individualistic response to disturbance - Kerry D. Woods; Thomas A. Nagel; Bogdan Brzeziecki; C. Mark Cowell; Dejan Firm; Peter Jaloviar; Stanislav Kucbel; Yiching Lin; Zbigniew Maciejewski; Jerzy Szwagrzyk; Jaroslav Vencurik (Global Ecology and Biogeography, 2021)
Aim Old‐growth, mesic temperate forests are often assumed to be structured by gap‐phase processes, resulting in quasi‐equilibrial long‐term dynamics. This assumption influences management focused on simulation of natural disturbance dynamics and is embedded in most models of forest successional dynamics. We use multi‐decade monitoring of permanent plots in old‐growth forests to assess demographic assumptions directly with respect to tree mortality rates. Location Sixteen sites in mesic, temperate old‐growth forests in eastern North America and Europe with multi‐decade monitoring. Time period Variable across sites, spanning c . 20–78 years from 1936 to 2014. Major taxa studied Tree species of late‐successional, cool‐temperate forests of Europe and eastern North America. Methods We calculated and compared the annualized mortality rates ( m ), with confidence intervals, by species, size class and measurement interval, for tree species of sufficient abundance. Results Retrospective analysis shows dynamic and diverse demographic properties across populations and sites. Stand‐scale mortality rates of 0.7–2.5%/year average higher than previous estimates for old‐growth temperate forests. Variations among species, over time and among size classes, suggest that gap‐phase models are inadequate to explain stand dynamics, implying instead that rare disturbance events of moderate severity have long‐lasting effects in old‐growth forests and that indirect anthropogenic influences affect old‐growth, unlogged forests. Main conclusions Multi‐decade baseline data, essential for understanding community assembly and long‐term dynamics in these “slow systems,” are rare and poorly integrated. Our analysis demonstrates the value of the few long‐term, “legacy” data sets. Results suggest that differences in life history interact with complex disturbance histories, resulting in non‐equilibrial dynamics in old‐growth temperate tree communities, and that changes in disturbance patterns through anthropogenic climate change might, therefore, be an important driver of ecosystem change.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Pomc Plays an Important Role in Sexual Size Dimorphism in Tilapia - Z. Y. Wan; V. C. L. Lin; Yue Gen Hua (Marine Biotechnology, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Glutathione and the intracellular labile heme pool - Rosemary O’Keeffe; Gladys Oluyemisi Latunde-Dada; Yu-Lin Chen; Xiaole L. Kong; Agostino Cilibrizzi; Robert C. Hider (BioMetals, 2021)
One candidate for the cytosolic labile iron pool is iron(II)glutathione. There is also a widely held opinion that an equivalent cytosolic labile heme pool exists and that this pool is important for the intracellular transfer of heme. Here we describe a study designed to characterise conjugates that form between heme and glutathione. In contrast to hydrated iron(II), heme reacts with glutathione, under aerobic conditions, to form the stable hematin–glutathione complex, which contains iron(III). Thus, glutathione is clearly not the cytosolic ligand for heme, indeed we demonstrate that the rate of heme degradation is enhanced in the presence of glutathione. We suggest that the concentration of heme in the cytosol is extremely low and that intracellular heme transfer occurs via intracellular membrane structures. Should any heme inadvertently escape into the cytosol, it would be rapidly conjugated to glutathione thereby protecting the cell from the toxic effects of heme.

Tracing the origins of recent Queensland fruit fly incursions into South Australia, Tasmania and New Zealand - Ángel-David Popa-Báez; Siu Fai Lee; Heng Lin Yeap; Guy Westmore; Peter Crisp; Dongmei Li; Renee Catullo; Emilie C. Cameron; Owain R. Edwards; Phillip W. Taylor; John G. Oakeshott (Biological Invasions, 2021)

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Impacts of sea level rise on future storm-induced coastal inundations over massachusetts coast - Changsheng Chen; Zhaolin Lin; Robert C. Beardsley; Tom Shyka; Yu Zhang; Qichun Xu; Jianhua Qi; Huichan Lin; Danya Xu (Natural Hazards, 2021)

Characterization and validation of QTLs for adult plant stripe rust resistance in Chinese wheat landrace Dabaimai - M. Y. Wang; M. R. Xu; F. T. Wang; S. J. A. Shah; J. Feng; R. M. Lin; S. C. Xu (Cereal Research Communications, 2021)

Preformulation Characterization of Griffithsin, a Biopharmaceutical Candidate for HIV Prevention - Lindsay F. Kramzer; Krystal T. Hamorsky; Phillip W. Graebing; Lin Wang; Joshua L. Fuqua; Nobuyuki Matoba; Amanda B. Lasnik; Bernard J. Moncla; Junmei Zhang; Kenneth E. Palmer; Lisa C. Rohan (AAPS PharmSciTech, 2021)

The stratigraphic significance of early Cambrian (Series 2, Stage 4) trilobites from the Smith Bay Shale near Freestone Creek, Kangaroo Island - J. B. Jago; C. J. Bentley; J. R. Paterson; J. D. Holmes; T. R. Lin; X. W. Sun (Australian Journal of Earth Sciences, 2021)

Fracture Propagation of Rock like Material with a Fluid-Infiltrated Pre-existing Flaw Under Uniaxial Compression - C. Wei; B. Zhang; W. Zhu; S. Wang; J. Li; ·L. Yang; C. Lin (Rock Mechanics and Rock Engineering, 2021)

Hydrochemical composition, distribution, and sources of typical organic pollutants and metals in Lake Bangong Co, Tibet - Li Lin; Lei Dong; Zhen Wang; Chao Li; Min Liu; Qingyun Li; John C. Crittenden (Environmental Science and Pollution Research, 2021)

Patterns of chronic disease management and health outcomes in a population-based cohort of Black women with breast cancer - Michelle Doose; Jennifer Tsui; Michael B. Steinberg; Cathleen Y. Xing; Yong Lin; Joel C. Cantor; Chi-Chen Hong; Kitaw Demissie; Elisa V. Bandera (Cancer Causes & Control, 2021)

Dietary exposure assessment of cadmium, arsenic, and lead in market rice from Sri Lanka - Lin Liu; Jialiang Han; Xiaohang Xu; Zhidong Xu; Kasun S. Abeysinghe; Anjana J. Atapattu; P. Mangala C. S. De Silva; Qinhui Lu; Guangle Qiu (Environmental Science and Pollution Research, 2020)

Modeling oil dispersion under breaking waves. Part II: Coupling Lagrangian particle tracking with population balance model - Fangda Cui; Lin Zhao; Cosan Daskiran; Thomas King; Kenneth Lee; Joseph Katz; Michel C. Boufadel (Environmental Fluid Mechanics, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Hyperphosphorylation Renders Tau Prone to Aggregate and to Cause Cell Death - Mengyu Liu; Dexin Sui; Thomas Dexheimer; Stacy Hovde; Xiexiong Deng; Kuang-Wei Wang; Hsin Lian Lin; Hsiao-Tien Chien; Hye Kyong Kweon; Nora Sheen Kuo; Christopher A. Ayoub; Daniela Jimenez-Harrison; et al. (Molecular Neurobiology, 2020)

Suitable plant combinations for ecological floating beds in eutrophic subtropical coastal wetlands under different salinities: experimental evidences - J. C. Lyu; G. H. Lin; Z. Y. Fan; W. X. Lin; Z. Dai (International Journal of Environmental Science and Technology, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Peripheral ProBDNF Delivered by an AAV Vector to the Muscle Triggers Depression-Like Behaviours in Mice - L. Y. Lin; S. Kelliny; L. C. Liu; M. Al-Hawwas; X. F. Zhou; L. Bobrovskaya (Neurotoxicity Research, 2020)

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Analysis of peptide antibiotic residues in milk using liquid chromatography-high resolution mass spectrometry (LC-HRMS) - I-Lin Wu; Sherri B. Turnipseed; Wendy C. Andersen; Mark R. Madson (Food Additives & Contaminants: Part A, 2020)

Propagation of spontaneous electrical activity in the ex vivo human uterus - Nienke P.M. Kuijsters; Federica Sammali; Xin Ye; Celine Blank; Lin Xu; Massimo Mischi; Benedictus C. Schoot; Chiara Rabotti (Pflügers Archiv - European Journal of Physiology, 2020)
Contractions of the non-pregnant uterus play a key role in fertility. Yet, the electrophysiology underlying these contractions is poorly understood. In this paper, we investigate the presence of uterine electrical activity and characterize its propagation in unstimulated ex vivo human uteri. Multichannel electrohysterographic measurements were performed in five freshly resected human uteri starting immediately after hysterectomy. Using an electrode grid externally and an electrode array internally, measurements were performed up to 24 h after hysterectomy and compared with control. Up to 2 h after hysterectomy, we measured biopotentials in all included uteri. The median root mean squared (RMS) values of the external measurements ranged between 3.95 μV (interquartile range (IQR) 2.41–14.18 μV) and 39.4 μV (interquartile range (IQR) 10.84–105.64 μV) and were all significantly higher than control (median RMS of 1.69 μV, IQR 1.13–3.11 μV), consisting of chicken breast meat. The RMS values decreased significantly over time. After 24 h, the median RMS (1.27 μV, IQR 0.86–3.04 μV) was comparable with the control (1.69 μV, IQR 1.13–3.11 μV, p = 0.125). The internal measurements showed a comparable pattern over time, but overall lower amplitude. The measured biopotentials propagated over the uterine surface, following both a plane-wave as well as an erratic pattern. No clear pacemaker location nor a preferred propagation direction could be identified. These results show that ex vivo uteri can spontaneously generate propagating biopotentials and provide novel insight contributing to improving our understanding of the electrophysiology of the human non-pregnant uterus.

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

Testicular cancer in Hispanics: incidence of subtypes over time according to neighborhood sociodemographic factors in California - Mindy C. DeRouen; Meg McKinley; Sumit Anil Shah; Hala T. Borno; Rhonda Aoki; Daphne Y. Lichtensztajn; John T. Leppert; James D. Brooks; Benjamin I. Chung; Scarlett Lin Gomez; Iona Cheng (Cancer Causes & Control, 2020)

Correction to: Soil biochemical properties and bacteria community in a repeatedly fumigated-incubated soil - Xiaoyu Zhou; Lin Chen; Jianming Xu; Philip C. Brookes (Biology and Fertility of Soils, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

A novel hydrogel for highly efficient adsorption of Cu(II): synthesis, characterization, and mechanisms - Jun Wan; Lin Chen; Qiang Li; Yuxuan Ye; Xiaonan Feng; Aijiao Zhou; Xuejun Long; Dongsheng Xia; Tian C. Zhang (Environmental Science and Pollution Research, 2020)

Pyrolysis of fatty acids derived from hydrolysis of brown grease with biosolids - Mehdi Omidghane; Mattia Bartoli; Justice Asomaning; Lin Xia; Michael Chae; David C. Bressler (Environmental Science and Pollution Research, 2020)
The escalating generation of biosolids and increasing regulations regarding their safe handling and disposal have created a great environmental challenge. Recently, biosolids have been incorporated into the hydrolysis step of a two-step thermal lipid conversion process to act as water replacement in the production of renewable chemicals and fuels. Here, the hexane extract recovered from hydrolysis of biosolids, lipids from brown grease hydrolyzed using either water (control) or biosolids as a water replacement, was pyrolyzed at 410–450 °C for 2 h. The product distribution and composition were not significantly different when biosolids were used to hydrolyze brown grease instead of water. The liquid product consisted mainly of alkanes, alkenes, aromatics, and cyclic compounds similar to those in petroleum-derived liquid fuels. However, the use of biosolids as a water substitute resulted in a significant increase in sulphur content of the pyrolysate, which will necessitate processes to reduce the sulphur content before or after pyrolysis. Nevertheless, the pathways proposed in this paper are considered as potentially economically viable approaches to not only resolve the issues associated with disposal of biosolids but also to produce renewable hydrocarbons for fuel and chemical applications.

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Soil biochemical properties and bacteria community in a repeatedly fumigated-incubated soil - Xiaoyu Zhou; Lin Chen; Jianming Xu; Philip C. Brookes (Biology and Fertility of Soils, 2020)

An Engineered Biomimetic MPER Peptide Vaccine Induces Weakly HIV Neutralizing Antibodies in Mice - Shuai Shao; Wei-Chiao Huang; Cuiyan Lin; Mark D. Hicar; Celia C. LaBranche; David C. Montefiori; Jonathan F. Lovell (Annals of Biomedical Engineering, 2020)

A Major Hydrothermal Reservoir Underneath the Tatun Volcano Group of Taiwan: Clues from a Dense Linear Geophone Array - C. H. Lin; Y. C. Lai; M. H. Shih; C. J. Lin; J. S. Ku; Y. C. Huang (Pure and Applied Geophysics, 2020)
A dense linear geophone array is deployed across the Tatun volcano group (TVG) at the northern tip of Taiwan, where more than 7 million residents live in the Taipei metropolis. The array is composed of 50 geophones with a station spacing of ~ 200 m in average, and it is designed for striking in the NW–SE direction to record the many earthquakes in eastern Taiwan, where the Philippine Sea plate subducted beneath the Eurasia plate. The detailed examination of felt earthquakes shows consistent P-wave delays are recorded at particular stations of the array. The further forward modeling indicates there is a low-velocity zone (LVZ) at depths between ~ 0.5 and ~ 2.5 km beneath the major fumarole sites. Combining this preliminary result with previous studies including clustering seismicity, volcanic earthquakes, low-resistivity zone, strong degassing processes and shallow velocity structures, we suggest that the LVZ might be associated with the major hydrothermal reservoir at the TVG. The identification of the hydrothermal reservoir by the LVZ not only implies a potential volcanic threat, such as phreatic eruptions, in the future, but also provides the possibility of sustainable geothermal resources for replacing traditional nuclear and fossil fuel power plants. Detailed images of the LVZ and other volcanic structures will be obtained soon when dense geophone arrays with more than 600 geophones are deployed from 2020 to 2022.

Transgenic Overexpression of the Disordered Prion Protein N1 Fragment in Mice Does Not Protect Against Neurodegenerative Diseases Due to Impaired ER Translocation - Behnam Mohammadi; Luise Linsenmeier; Mohsin Shafiq; Berta Puig; Giovanna Galliciotti; Camilla Giudici; Michael Willem; Thomas Eden; Friedrich Koch-Nolte; Yu-Hsuan Lin; Jörg Tatzelt; Markus Glatzel; et al. (Molecular Neurobiology, 2020)
The structurally disordered N-terminal half of the prion protein (PrP C ) is constitutively released into the extracellular space by an endogenous proteolytic cleavage event. Once liberated, this N1 fragment acts neuroprotective in ischemic conditions and interferes with toxic peptides associated with neurodegenerative diseases, such as amyloid-beta (Aβ) in Alzheimer’s disease. Since analog protective effects of N1 in prion diseases, such as Creutzfeldt-Jakob disease, have not been studied, and given that the protease releasing N1 has not been identified to date, we have generated and characterized transgenic mice overexpressing N1 (TgN1). Upon intracerebral inoculation of TgN1 mice with prions, no protective effects were observed at the levels of survival, clinical course, neuropathological, or molecular assessment. Likewise, primary neurons of these mice did not show protection against Aβ toxicity. Our biochemical and morphological analyses revealed that this lack of protective effects is seemingly due to an impaired ER translocation of the disordered N1 resulting in its cytosolic retention with an uncleaved signal peptide. Thus, TgN1 mice represent the first animal model to prove the inefficient ER translocation of intrinsically disordered domains (IDD). In contrast to earlier studies, our data challenge roles of cytoplasmic N1 as a cell penetrating peptide or as a potent “anti-prion” agent. Lastly, our study highlights both the importance of structured domains in the nascent chain for proteins to be translocated and aspects to be considered when devising novel N1-based therapeutic approaches against neurodegenerative diseases.

Alternative designs and tropical tree seedling growth performance landscapes - Samantha J. Worthy; Daniel C. Laughlin; Jenny Zambrano; María N. Umaña; Caicai Zhang; Luxiang Lin; Min Cao; Nathan G. Swenson (Ecology, 2020)
The functional trait values that constitute a whole‐plant phenotype interact with the environment to determine demographic rates. Current approaches often fail to explicitly consider trait × trait and trait × environment interactions, which may lead to missed information that is valuable for understanding and predicting the drivers of demographic rates and functional diversity. Here, we consider these interactions by modeling growth performance landscapes that span multidimensional trait spaces along environmental gradients. We utilize individual‐level leaf, stem, and root trait data combined with growth data from tree seedlings along soil nutrient and light gradients in a hyper‐diverse tropical rainforest. We find that multiple trait combinations in phenotypic space (i.e., alternative designs) lead to multiple growth performance peaks that shift along light and soil axes such that no single or set of interacting traits consistently results in peak growth performance. Evidence from these growth performance peaks also generally indicates frequent independence of above‐ and belowground resource acquisition strategies. These results help explain how functional diversity is maintained in ecological communities and question the practice of utilizing a single trait or environmental variable, in isolation, to predict the growth performance of individual trees.

Spectral and spatial kernel water quality mapping - Hone-Jay Chu; Lalu Muhamad Jaelani; Manh Van Nguyen; Chao-Hung Lin; Ariel C. Blanco (Environmental Monitoring and Assessment, 2020)

Gut microbial diversity across a contact zone for California voles: Implications for lineage divergence of hosts and mitonuclear mismatch in the assembly of the mammalian gut microbiome - Dana Lin; Eileen A. Lacey; Bryan H. Bach; Ke Bi; Christopher J. Conroy; Anton Suvorov; Rauri C. K. Bowie (Molecular Ecology, 2020)
Gut microbial diversity is thought to reflect the co‐evolution of microbes and their hosts as well as current host‐specific attributes such as genetic background and environmental setting. To explore interactions among these parameters, we characterized variation in gut microbiome composition of California voles ( Microtus californicus ) across a contact zone between two recently diverged lineages of this species. Because this contact zone contains individuals with mismatched mitochondrial‐nuclear genomes (cybrids), it provides an important opportunity to explore how different components of the genotype contribute to gut microbial diversity. Analyses of bacterial 16S rRNA sequences and joint species distribution modelling revealed that host genotypes and genetic differentiation among host populations together explained more than 50% of microbial community variation across our sampling transect. The ranked importance (most to least) of factors contributing to gut microbial diversity in our study populations were: genome‐wide population differentiation, local environmental conditions, and host genotypes. However, differences in microbial communities among vole populations (β‐diversity) did not follow patterns of lineage divergence (i.e., phylosymbiosis). Instead, among‐population variation was best explained by the spatial distribution of hosts, as expected if the environment is a primary source of gut microbial diversity (i.e., dispersal limitation hypothesis). Across the contact zone, several bacterial taxa differed in relative abundance between the two parental lineages as well as among individuals with mismatched mitochondrial and nuclear genomes. Thus, genetic divergence among host lineages and mitonuclear genomic mismatches may also contribute to microbial diversity by altering interactions between host genomes and gut microbiota (i.e., hologenome speciation hypothesis).

Sedimentary environment and facies of the Huagang Formation in the northern central Xihu Depression, East China Sea Basin, China - Z. X. Zhao; C. M. Dong; C. Y. Lin; X. G. Zhang; X. Huang; B. J. Li; W. Guo; Z. Q. Zhu (Australian Journal of Earth Sciences, 2020)

A deep-level region-based visual representation architecture for detecting strawberry flowers in an outdoor field - P. Lin; W. S. Lee; Y. M. Chen; N. Peres; C. Fraisse (Precision Agriculture, 2020)

The emission of volatile halocarbons by seaweeds and their response towards environmental changes - Fiona Seh-Lin Keng; Siew-Moi Phang; Noorsaadah Abd Rahman; Emma C. Leedham Elvidge; Gill Malin; William T. Sturges (Journal of Applied Phycology, 2020)

Evidence of widespread metabolite abnormalities in Myalgic encephalomyelitis/chronic fatigue syndrome: assessment with whole-brain magnetic resonance spectroscopy - Christina Mueller; Joanne C. Lin; Sulaiman Sheriff; Andrew A. Maudsley; Jarred W. Younger (Brain Imaging and Behavior, 2020)

A new slice-based method for calculating the minimum safe thickness for a filled-type karst cave - Z. H. Xu; X. Huang; S. C. Li; P. Lin; X. S. Shi; J. Wu (Bulletin of Engineering Geology and the Environment, 2020)

Managing water quality in a river basin with uncertainty - H.-W. Chen; W.-Y. Chen; C.-T. Wang; Y.-H. Lin; M.-J. Deng; C.-Y. Chiang (International Journal of Environmental Science and Technology, 2020)

Changes in abundance and composition of nitrifying communities in barley (Hordeum vulgare L.) rhizosphere and bulk soils over the growth period following combined biochar and urea amendment - Lu Yu; Peter M. Homyak; Xiaoxi Kang; Philip C. Brookes; Yikai Ye; Yeneng Lin; Afzal Muhammad; Jianming Xu (Biology and Fertility of Soils, 2020)

Cold treatment for guava fruits infested with oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) - Kao W. Lin; Huey L. Lin; Ching C. Shiesh; Yu. L. Hsu; Chih. H. Lin; Su. C. Chen; Wen B. Yeh (Applied Entomology and Zoology, 2020)

The acclimation of leaf photosynthesis of wheat and rice to seasonal temperature changes in T‐FACE environments - Chuang Cai; Gang Li; Lijun Di; Yunjie Ding; Lin Fu; Xuanhe Guo; Paul C. Struik; Genxing Pan; Haozheng Li; Weiping Chen; Weihong Luo; Xinyou Yin (Global Change Biology, 2020)
Crops show considerable capacity to adjust their photosynthetic characteristics to seasonal changes in temperature. However, how photosynthesis acclimates to changes in seasonal temperature under future climate conditions has not been revealed. We measured leaf photosynthesis ( A n ) of wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) grown under four combinations of two levels of CO 2 (ambient and enriched up to 500 µmol/mol) and two levels of canopy temperature (ambient and increased by 1.5–2.0°C) in temperature by free‐air CO 2 enrichment (T‐FACE) systems. Parameters of a biochemical C 3 ‐photosynthesis model and of a stomatal conductance ( g s ) model were estimated for the four conditions and for several crop stages. Some biochemical parameters related to electron transport and most g s parameters showed acclimation to seasonal growth temperature in both crops. The acclimation response did not differ much between wheat and rice, nor among the four treatments of the T‐FACE systems, when the difference in the seasonal growth temperature was accounted for. The relationships between biochemical parameters and leaf nitrogen content were consistent across leaf ranks, developmental stages, and treatment conditions. The acclimation had a strong impact on g s model parameters: when parameter values of a particular stage were used, the model failed to correctly estimate g s values of other stages. Further analysis using the coupled g s –biochemical photosynthesis model showed that ignoring the acclimation effect did not result in critical errors in estimating leaf photosynthesis under future climate, as long as parameter values were measured or derived from data obtained before flowering.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Characteristics and distribution of clay minerals and their effects on reservoir quality: Huagang Formation in the Xihu Sag, East China Sea Basin - X. L. Sun; C. Y. Lin; X. G. Zhang; J. L. Lin; Z. X. Zhao; D. W. Huang; D. P. Duan (Australian Journal of Earth Sciences, 2019)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Laminar specificity of oscillatory coherence in the auditory cortex - Francisco García-Rosales; Dennis Röhrig; Kristin Weineck; Mira Röhm; Yi-Hsuan Lin; Yuranny Cabral-Calderin; Manfred Kössl; Julio C. Hechavarria (Brain Structure and Function, 2019)

Variance in the response of silcrete to rapid heating complicates assumptions about past heat treatment methods - Alex Mackay; Sam C. Lin; Lachlan S. Kenna; Alex F. Blackwood (Archaeological and Anthropological Sciences, 2019)

The Contributions of Individual Muscle–Tendon Units to the Plantarflexor Group Force–Length Properties - Mehrdad Javidi; Craig P. McGowan; David C. Lin (Annals of Biomedical Engineering, 2019)

Extended liquid chromatography high resolution mass spectrometry screening method for veterinary drug, pesticide and human pharmaceutical residues in aquaculture fish - Sherri B. Turnipseed; Joseph M. Storey; I-Lin Wu; Wendy C. Andersen; Mark R. Madson (Food Additives & Contaminants: Part A, 2019)

Spatial patterns and effects of air pollution and meteorological factors on hospitalization for chronic lung diseases in Beijing, China - Lin Tian; Chuan Yang; Zijun Zhou; Ziting Wu; Xiaochuan Pan; Archie C. A. Clements (Science China Life Sciences, 2019)

The neural correlates of perceived energy levels in older adults with late-life depression - Charlene L. M. Lam; Ho-Ling Liu; Chih-Mao Huang; Yau-Yau Wai; Shwu-Hua Lee; Jenny Yiend; Chemin Lin; Tatia M. C. Lee (Brain Imaging and Behavior, 2019)

Bismuth(III) interactions with Desulfovibrio desulfuricans: inhibition of cell energetics and nanocrystal formation of Bi2S3 and Bi0 - Larry L. Barton; Alex S. Granat; Seungyeol Lee; Huifang Xu; Nathaniel L. Ritz; Robert Hider; Henry C. Lin (BioMetals, 2019)

Rapamycin Removes Damaged Mitochondria and Protects Human Trabecular Meshwork (TM-1) Cells from Chronic Oxidative Stress - Jing Na He; Shao Dan Zhang; Yang Qu; Hai Lin Wang; Clement C. Tham; Chi Pui Pang; Wai Kit Chu (Molecular Neurobiology, 2019)

Seasonal climatic effects and feedbacks of anthropogenic heat release due to global energy consumption with CAM5 - Bing Chen; C. Wu; X. Liu; L. Chen; Jian Wu; H. Yang; Tao Luo; Xue Wu; Yiquan Jiang; Lei Jiang; H. Y. Brown; Z. Lu; et al. (Climate Dynamics, 2019)

Cr-induced disturbance on expression of six COX genes in rice seedlings - X.-Z. Yu; C.-J. Lu; Y.-J. Lin; Y.-H. Li (International Journal of Environmental Science and Technology, 2019)

The role of heterogeneous environment and docetaxel gradient in the emergence of polyploid, mesenchymal and resistant prostate cancer cells - Ke-Chih Lin; Gonzalo Torga; Yusha Sun; Robert Axelrod; Kenneth J. Pienta; James C. Sturm; Robert H. Austin (Clinical & Experimental Metastasis, 2019)

Cloning, Expression and Characterization of Two Beta Carbonic Anhydrases from a Newly Isolated CO2 Fixer, Serratia marcescens Wy064 - Fanbing Chen; Wensong Jin; Huifang Gao; Zewang Guo; Hui Lin; Jiahuan Li; Kaihui Hu; Xiong Guan; Vipin C. Kalia; Jung-Kul Lee; Liaoyuan Zhang; Yongyu Li (Indian Journal of Microbiology, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Identification of Genes Involved in Flavonoid Biosynthesis of Chinese Narcissus (Narcissus tazetta L. var. chinensis) - Guiqing Wang; Biyun Yang; Jiacheng Wu; Peng Luo; Muhammad Anwar; Andrew C. Allan; Kui Lin-Wang; Richard V. Espley; Lihui Zeng (Plant Molecular Biology Reporter, 2018)

Illustrating the Impact of Uneven Saline Distribution on Thermal Lesion During Radiofrequency Ablation Using Computer Simulation for Smarter Healthcare Treatment Planning - Huang-Wen Huang; Lin Hui; Jason C. Hung; Kuei Min Wang (Journal of Medical and Biological Engineering, 2018)

A geometric morphometric relationship predicts stone flake shape and size variability - Will Archer; Cornel M. Pop; Zeljko Rezek; Stefan Schlager; Sam C. Lin; Marcel Weiss; Tamara Dogandžić; Dawit Desta; Shannon P. McPherron (Archaeological and Anthropological Sciences, 2018)

Two key features influencing community assembly processes at regional scale: Initial state and degree of change in environmental conditions - Youzhi Feng; Ruirui Chen; James C. Stegen; Zhiying Guo; Jianwei Zhang; Zhongpei Li; Xiangui Lin (Molecular Ecology, 2018)
Belowground microbial communities strongly influence ecosystem function such that predicting function may rely on understanding ecological processes that assemble communities. Uncertainty remains, however, in what governs the relative contributions of different ecological processes. To help fill this knowledge gap, we test the general hypothesis that both initial state and degree of change in environmental conditions govern the relative contributions of different ecological assembly processes. To do so, we leveraged regional‐scale nutrient and organic matter addition experiments and used soil organic matter (SOM) as a proxy of integrated soil environmental conditions. Consistent with our hypothesis, we found that both the initial amount of SOM and the degree of change in SOM—in response to nutrient addition—influenced the relative contributions of different ecological assembly processes. These influences were most clearly observed at the regional scale, suggesting potential scale dependence. More specifically, nutrient additions homogenized bacterial community composition due to enhanced influences of homogenizing dispersal when SOM content was initially high. In contrast, nutrient additions led to divergence in community composition due to variable selection when initial SOM was low and/or when SOM increased significantly in response to nutrient additions. Our findings indicate important connections among initial conditions, degree of change in environmental variables and microbial community assembly processes that may influence ecosystem processes. These conceptual inferences highlight a need to strengthen connections between ecological theory and biogeochemical modelling.

Chemical nature of soil organic carbon under different long-term fertilization regimes is coupled with changes in the bacterial community composition in a Calcaric Fluvisol - Dandan Li; Lin Chen; Jisheng Xu; Lei Ma; Dan C. Olk; Bingzi Zhao; Jiabao Zhang; Xiuli Xin (Biology and Fertility of Soils, 2018)

Effect of Subject-Specific Vertebral Position and Head and Neck Size on Calculation of Spine Musculoskeletal Moments - Anita N. Vasavada; Ellis Hughes; Derek D. Nevins; Steven M. Monda; David C. Lin (Annals of Biomedical Engineering, 2018)

Gross primary productivity of a large metropolitan region in midsummer using high spatial resolution satellite imagery - David L. Miller; Dar A. Roberts; Keith C. Clarke; Yang Lin; Olaf Menzer; Emily B. Peters; Joseph P. McFadden (Urban Ecosystems, 2018)

Ras-Related C3 Botulinum Toxin Substrate 1 Promotes Axonal Regeneration after Stroke in Mice - Lin Liu; Hui Yuan; Yanhua Yi; Edward C. Koellhoffer; Yashasvee Munshi; Fan Bu; Yi Zhang; Zhenggang Zhang; Louise D. McCullough; Jun Li (Translational Stroke Research, 2018)

Flake selection and scraper retouch probability: an alternative model for explaining Middle Paleolithic assemblage retouch variability - Sam C. Lin (Archaeological and Anthropological Sciences, 2018)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

Cover Image - X Luo; G Liao; C Liu; X Jiang; M Lin; C Zhao; J Tao; Z Huang (Journal of Fish Diseases, 2018)

Characterization of bacteriophage HN 48 and its protective effects in Nile tilapia Oreochromis niloticus against Streptococcus agalactiae infections - X Luo; G Liao; C Liu; X Jiang; M Lin; C Zhao; J Tao; Z Huang (Journal of Fish Diseases, 2018)
Streptococcus agalactiae is a causative agent responsible for massive mortalities of tilapia that has led to catastrophic losses to tilapia culture globally. Bacteriophages represent a new class of antimicrobials against bacteria. In this study, we characterized the bacteriophage HN 48, which formed small and round‐transparent plaques on a double‐layer plate. With a hexagonal head and a long tail, this phage may belong to the Caudovirales according to the International Committee on Taxonomy of Viruses. HN 48 was found to have a relatively wide and highly specific host range, to be sensitive to high temperature (60–80°C) and low pH (3–5), and to be relatively stable at alkaline pH (8–10). Intraperitoneal injection with HN 48 had no adverse effects on tilapia and effectively inactivated the bacteria in the kidney. Fish that received phage therapy had 60% ± 3.3% survival rates and a delayed mean death time of about 3 days when compared to the control group. To the best of knowledge, this is the first study of tilapia streptococcal phage. Overall, the results indicated that phage HN 48 could prevent tilapia from experimental S. agalactiae infection, suggesting it has the potential to control this disease.

Enhancement of photocatalytic activity of titanium dioxide using non-metal doping methods under visible light: a review - M. Nasirian; Y. P. Lin; C. F. Bustillo-Lecompte; M. Mehrvar (International Journal of Environmental Science and Technology, 2018)

Resistance to neomycin ototoxicity in the extreme basal (hook) region of the mouse cochlea - Shelly C. Y. Lin; Peter R. Thorne; Gary D. Housley; Srdjan M. Vlajkovic (Histochemistry and Cell Biology, 2018)

Behavioural responses of an Australian colubrid snake (Dendrelaphis punctulatus) to a novel toxic prey item (the Cane Toad Rhinella marina) - John Llewelyn; Neil C. Choyce; Benjamin L. Phillips; Jonathan K. Webb; David J. Pearson; Lin Schwarzkopf; Richard Shine (Biological Invasions, 2018)

Effects of antiepileptic drugs on lipogenic gene regulation and hyperlipidemia risk in Taiwan: a nationwide population-based cohort study and supporting in vitro studies - Yi-Wen Li; Chung-Hsing Wang; Chao-Jung Chen; Charles C. N. Wang; Cheng-Li Lin; Wai-Kok Cheng; Hsin-Yi Shen; Yun-Ping Lim (Archives of Toxicology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Endocrine-Disrupting Activities and Organic Contaminants Associated with Oil and Gas Operations in Wyoming Groundwater - Christopher D. Kassotis; Danh C. Vu; Phuc H. Vo; Chung-Ho Lin; Jennifer N. Cornelius-Green; Sharyle Patton; Susan C. Nagel (Archives of Environmental Contamination and Toxicology, 2018)

Effects of acute morphine withdrawal on ultrasonic vocalizations in adult rats: unchanged 50-kHz call rate and altered subtype profile - YiQi C. Lin; Leah L. Zhao; Paul B. S. Clarke (Psychopharmacology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Short-chain fatty acids in control of energy metabolism - Jiamiao Hu; Shaoling Lin; Baodong Zheng; Peter C. K. Cheung (Critical Reviews in Food Science and Nutrition, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

Optical types of inland and coastal waters - Evangelos Spyrakos; Ruth O'Donnell; Peter D. Hunter; Claire Miller; Marian Scott; Stefan G. H. Simis; Claire Neil; Claudio C. F. Barbosa; Caren E. Binding; Shane Bradt; Mariano Bresciani; Giorgio Dall'Olmo; et al. (Limnology and Oceanography, 2018)
Inland and coastal waterbodies are critical components of the global biosphere. Timely monitoring is necessary to enhance our understanding of their functions, the drivers impacting on these functions and to deliver more effective management. The ability to observe waterbodies from space has led to Earth observation (EO) becoming established as an important source of information on water quality and ecosystem condition. However, progress toward a globally valid EO approach is still largely hampered by inconsistences over temporally and spatially variable in‐water optical conditions. In this study, a comprehensive dataset from more than 250 aquatic systems, representing a wide range of conditions, was analyzed in order to develop a typology of optical water types (OWTs) for inland and coastal waters. We introduce a novel approach for clustering in situ hyperspectral water reflectance measurements ( n = 4045) from multiple sources based on a functional data analysis. The resulting classification algorithm identified 13 spectrally distinct clusters of measurements in inland waters, and a further nine clusters from the marine environment. The distinction and characterization of OWTs was supported by the availability of a wide range of coincident data on biogeochemical and inherent optical properties from inland waters. Phylogenetic trees based on the shapes of cluster means were constructed to identify similarities among the derived clusters with respect to spectral diversity. This typification provides a valuable framework for a globally applicable EO scheme and the design of future EO missions.

The Benefits of Reduced Anthropogenic Climate changE (BRACE): a synthesis - Brian C. O’Neill; James M. Done; Andrew Gettelman; Peter Lawrence; Flavio Lehner; Jean-Francois Lamarque; Lei Lin; Andrew J. Monaghan; Keith Oleson; Xiaolin Ren; Benjamin M. Sanderson; Claudia Tebaldi; et al. (Climatic Change, 2018)

Microbial dolomite in the sabkha environment of the middle Cambrian in the Tarim Basin, NW China - X. L. You; S. Sun; C. S. Lin; J. Q. Zhu (Australian Journal of Earth Sciences, 2018)

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Co-altered functional networks and brain structure in unmedicated patients with bipolar and major depressive disorders - Hao He; Jing Sui; Yuhui Du; Qingbao Yu; Dongdong Lin; Wayne C. Drevets; Jonathan B. Savitz; Jian Yang; Teresa A. Victor; Vince D. Calhoun (Brain Structure and Function, 2017)

Enhancing Immiscible Fluid Displacement in Porous Media by Capillary Pressure Discontinuities - C. A. Chung; Hung-Yu Lin (Transport in Porous Media, 2017)

The VALiDATe29 MRI Based Multi-Channel Atlas of the Squirrel Monkey Brain - Kurt G. Schilling; Yurui Gao; Iwona Stepniewska; Tung-Lin Wu; Feng Wang; Bennett A. Landman; John C. Gore; Li Min Chen; Adam W. Anderson (Neuroinformatics, 2017)

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Helicobacter pylori infection increases the risk of adult-onset asthma: a nationwide cohort study - Y-C Wang; T-Y Lin; S-T Shang; H-J Chen; C-H Kao; C-C Wu; T-Y Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Formation of chlorite rims and the impact of pore-lining chlorite on reservoir quality: a case study from Shiqianfeng sandstones in upper Permian of Dongpu Depression, Bohai Bay Basin, eastern China - P. J. Ma; C. Y. Lin; S. Q. Zhang; C. M. Dong; Y. F. Xu (Australian Journal of Earth Sciences, 2017)

Evolution of landslide hotspots in Taiwan - S. C. Lin; M. C. Ke; C. M. Lo (Landslides, 2017)

Risk factors and outcome of levofloxacin-resistant Elizabethkingia meningoseptica bacteraemia in adult patients in Taiwan - Y.-C. Huang; Y.-W. Huang; Y.-T. Lin; F.-D. Wang; Y.-J. Chan; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Experimental Investigation of the Anisotropic Mechanical Properties of a Columnar Jointed Rock Mass: Observations from Laboratory-Based Physical Modelling - H. Ji; J. C. Zhang; W. Y. Xu; R. B. Wang; H. L. Wang; L. Yan; Z. N. Lin (Rock Mechanics and Rock Engineering, 2017)

The Asia-Pacific’s role in the emerging solar geoengineering debate - Masahiro Sugiyama; Shinichiro Asayama; Atsushi Ishii; Takanobu Kosugi; John C. Moore; Jolene Lin; Penehuro F. Lefale; Wil Burns; Masatomo Fujiwara; Arunabha Ghosh; Joshua Horton; Atsushi Kurosawa; et al. (Climatic Change, 2017)

Selective Isolation of a Eucalyptus spp. Woodchip Bacterial Community and Its Taxonomic and Metabolic Profiling - C. F. Nnadozie; J. Lin; R. Govinden (BioEnergy Research, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Prior Visual Experience Modulates Learning of Sound Localization Among Blind Individuals - Qian Tao; Chetwyn C. H. Chan; Yue-jia Luo; Jian-jun Li; Kin-hung Ting; Zhong-lin Lu; Susan Whitfield-Gabrieli; Jun Wang; Tatia M. C. Lee (Brain Topography, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Increased risk of chronic osteomyelitis after hip replacement: a retrospective population-based cohort study in an Asian population - D.-Z. Hung; N. Tien; C.-L. Lin; Y.-R. Lee; C. C. N. Wang; J.-J. Chen; Y.-P. Lim (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Soil priming effects following substrates addition to biochar-treated soils after 431 days of pre-incubation - Yu Luo; Qimei Lin; M. Durenkamp; A. J. Dungait; P. C. Brookes (Biology and Fertility of Soils, 2017)

Effects of dietary canthaxanthin on growth and body colour of blood parrot cichlid Amphilophus citrinellus × Paraneetroplus synspilus - M. Li; M. M. Rahman; B. Wu; Y.-C. Lin (Aquaculture International, 2017)

Internet Usage Trends in Thoracic Surgery Patients and Their Caregivers - Alisha D. Lussiez; Stephanie Burdick; Sindhura Kodali; Gustavo Rubio; Jacob A. Mack; Jules Lin; Andrew C. Chang; Rishindra M. Reddy (Journal of Cancer Education, 2017)

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Angiopoietins as serum biomarkers for lymphatic anomalies - Timothy D. Le Cras; Paula S. Mobberley-Schuman; Mary Broering; Lin Fei; Cameron C. Trenor; Denise M. Adams (Angiogenesis, 2017)

The effects of combinations of biochar, lime, and organic fertilizer on nitrification and nitrifiers - Kaile Zhang; Lin Chen; Yong Li; Philip C. Brookes; Jianming Xu; Yu Luo (Biology and Fertility of Soils, 2017)

Infectious bursal disease virus as a replication-incompetent viral vector expressing green fluorescent protein - Yung-Yi C. Mosley; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2017)

Fine mapping and candidate gene analysis of two loci conferring resistance to Phytophthora sojae in soybean - Linghong Li; Feng Lin; Weidong Wang; Jieqing Ping; Joshua C. Fitzgerald; Meixia Zhao; Shuai Li; Lianjun Sun; Chunmei Cai; Jianxin Ma (Theoretical and Applied Genetics, 2016)

The genus Fusariella - Chuan-Gen Lin; Yun Chen; Eric H. C. McKenzie; Darbhe J. Bhat; Hiran A. Ariyawansa; Kevin D. Hyde; Yong Wang (Mycological Progress, 2016)

Microwave drying characteristics of microalgae (Chlorella vulgaris) for biofuel production - Al Rey C. Villagracia; Andres Philip Mayol; Aristotle T. Ubando; Jose Bienvenido Manuel M. Biona; Nelson B. Arboleda; Melanie Y. David; Roy B. Tumlos; Henry Lee; Ong Hui Lin; Rafael A. Espiritu; Alvin B. Culaba; Hideaki Kasai (Clean Technologies and Environmental Policy, 2016)

Nonsteroidal anti-inflammatory drugs, statins, and pancreatic cancer risk: a population-based case–control study - Pik Fang Kho; Jonathan Fawcett; Lin Fritschi; Harvey Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2016)

Functional composition drives ecosystem function through multiple mechanisms in a broadleaved subtropical forest - Jyh-Min Chiang; Marko J. Spasojevic; Helene C. Muller-Landau; I-Fang Sun; Yiching Lin; Sheng-Hsin Su; Zueng-Sang Chen; Chien-Teh Chen; Nathan G. Swenson; Ryan W. McEwan (Oecologia, 2016)

Influence of Three Citrus Herbicides on Potential Production of Sorghum bicolor ‘Topper 76-6’ as a Bioenergy Crop - Patrick C. Wilson; Barrett Gruber; Youjian Lin; Prem Kumar; David Niebch; Sandra Wilson (Bulletin of Environmental Contamination and Toxicology, 2016)

A new region-based preparatory factor for landslide susceptibility models: the total flux - C. C. Liu; W. Luo; M. C. Chen; Y. T. Lin; H. L. Wen (Landslides, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

Urban high-resolution fossil fuel CO2 emissions quantification and exploration of emission drivers for potential policy applications - Risa Patarasuk; Kevin Robert Gurney; Darragh O’Keeffe; Yang Song; Jianhua Huang; Preeti Rao; Martin Buchert; John C. Lin; Daniel Mendoza; James R. Ehleringer (Urban Ecosystems, 2016)

The agranular and granular insula differentially contribute to gambling-like behavior on a rat slot machine task: effects of inactivation and local infusion of a dopamine D4 agonist on reward expectancy - P. J. Cocker; M. Y. Lin; M. M. Barrus; B. Le Foll; C. A. Winstanley (Psychopharmacology, 2016)

Infanticide in the Indo-Pacific humpback dolphin (Sousa chinensis) - Ruiqiang Zheng; Leszek Karczmarski; Wenzhi Lin; Stephen C. Y. Chan; Wei-Lun Chang; Yuping Wu (Journal of Ethology, 2016)

Genetic Diversity of Populations of Saccharum spontaneum with Different Ploidy Levels Using SSR Molecular Markers - X. L. Liu; X. J. Li; C. H. Xu; X. Q. Lin; Z. H. Deng (Sugar Tech, 2016)

Changes in Sulforaphane and Selenocysteine Methyltransferase Transcript Levels in Broccoli Treated with Sodium Selenite - K. Huang; J. C. Lin; Q. Y. Wu; J. Y. Yan; M. Y. Liu; S. Zhang; W. J. Xiao (Plant Molecular Biology Reporter, 2016)

Copper(II) binding properties of hepcidin - Kanokwan Kulprachakarn; Yu-Lin Chen; Xiaole Kong; Maria C. Arno; Robert C. Hider; Somdet Srichairatanakool; Sukhvinder S. Bansal (JBIC Journal of Biological Inorganic Chemistry, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Differentiation in development of benzimidazole resistance in Colletotrichum gloeosporioides complex populations from strawberry and grape hosts - T. Lin; X. F. Xu; D. J. Dai; H. J. Shi; H. D. Wang; C. Q. Zhang (Australasian Plant Pathology, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Spatial and Age-Dependent Hair Cell Generation in the Postnatal Mammalian Utricle - Zhen Gao; Michael C. Kelly; Dehong Yu; Hao Wu; Xi Lin; Fang-lu Chi; Ping Chen (Molecular Neurobiology, 2016)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Evaluating and Reporting the Immunogenicity Impacts for Biological Products—a Clinical Pharmacology Perspective - Yow-Ming C. Wang; Jie Wang; Yuen Yi Hon; Lin Zhou; Lanyan Fang; Hae Young Ahn (The AAPS Journal, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Identification and molecular mapping of Rps11, a novel gene conferring resistance to Phytophthora sojae in soybean - Jieqing Ping; Joshua C. Fitzgerald; Chunbao Zhang; Feng Lin; Yonghe Bai; Dechun Wang; Rajat Aggarwal; Maqsood Rehman; Oswald Crasta; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The impact of global budgeting on health service utilization, health care expenditures, and quality of care among patients with pneumonia in Taiwan - C.-Y. Lin; T. Ma; C.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Groundwater Molybdenum from Emerging Industries in Taiwan - Kuo-Sheng Tsai; Yu-Min Chang; Jimmy C. M. Kao; Kae-Long Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Evaluation of soil erosion risk for watershed management in Shenmu watershed, central Taiwan using USLE model parameters - B. S. Lin; K. Thomas; C. K. Chen; H. C. Ho (Paddy and Water Environment, 2016)

Three N-Glycosylation Sites of Human Acetylcholinesterase Shares Similar Glycan Composition - Miranda L. Xu; Wilson K. W. Luk; Kei M. Lau; Cathy W. C. Bi; Anthony W. M. Cheng; Amy G. W. Gong; Huangquan Lin; Karl W. K. Tsim (Journal of Molecular Neuroscience, 2015)

Pharmacodynamic Activity of Dapivirine and Maraviroc Single Entity and Combination Topical Gels for HIV-1 Prevention - Charlene S. Dezzutti; Sarah Yandura; Lin Wang; Bernard Moncla; Elizabeth A. Teeple; Brid Devlin; Jeremy Nuttall; Elizabeth R. Brown; Lisa C. Rohan (Pharmaceutical Research, 2015)

Fully automatic and nonparametric quantification of adipose tissue in fat–water separation MR imaging - Defeng Wang; Lin Shi; Winnie C. W. Chu; Miao Hu; Brian Tomlinson; Wen-Hua Huang; Tianfu Wang; Pheng Ann Heng; David K. W. Yeung; Anil T. Ahuja (Medical & Biological Engineering & Computing, 2015)

Cloning, expression, and characterization of Pseudomonas vesicularis MA103 β-1,3-xylanase in Escherichia coli ClearColi BL21(DE3) - Wen-Sing Liang; Tsuei-Yun Fang; Hong-Ting Lin; Tristan C. Liu; Wen-Jung Lu; Wen-Shyong Tzou; Shye-Jye Tang; Fu-Pang Lin; Shiu-Mei Liu; Chorng-Liang Pan (Fisheries Science, 2015)

Melatonin Ameliorates Arsenite-Induced Neurotoxicity: Involvement of Autophagy and Mitochondria - Y. C. Teng; Y. I. Tai; H. J. Huang; A. M. Y. Lin (Molecular Neurobiology, 2015)

Rapid generation and analysis of expressed sequence tags to uncovering inflorescence secondary metabolism of Bougainvillea spectabilis ‘Speciosas’ by pyrosequencing - S. X. Xu; Q. Y. Huang; C. S. Lin; F. C. Lin; L. X. Lin; Q. Y. Shen (Euphytica, 2015)

The influence of shelf-sea fronts on winter monsoon over East China Sea - L.-Y. Oey; M.-C. Chang; S.-M. Huang; Y.-C. Lin; M.-A. Lee (Climate Dynamics, 2015)

Identification and characterization of a late gene encoded by grouper iridovirus 2L (GIV‐2L) - H‐Y Lin; C‐F Cheng; P P Chiou; C‐J Liou; J‐C Yiu; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) belongs to the Ranavirus genus and is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. In this study, we identified and characterized the GIV‐2L gene, which encodes a protein of unknown function. GIV‐2L is 1242 bp in length, with a predicted protein mass of 46.2 kDa. It displayed significant identity only with members of the Ranavirus and Iridovirus genera. We produced mouse monoclonal antibodies against the GIV‐2L protein by immunizing mice with GIV‐2L‐His‐tag recombinant protein. By inhibiting de novo protein and DNA synthesis in GIV‐infected cells, we showed that GIV‐2L was a late gene during the viral replication. Finally, immunofluorescence microscopy revealed that GIV‐2L protein accumulated in both the nucleus and cytoplasm of infected cells. These results offer important insights into the pathogenesis of GIV.

Crustal thickening and extension induced by the Great Sumatra–Andaman earthquake of 26 December 2004: revealed by the seismic moment tensor element Mrr - J.-Y. Lin; C.-L. Lo; W.-N. Wu; J.-C. Sibuet; S.-K. Hsu; Y.-Y. Wen (Marine Geophysical Research, 2015)

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Neonatal urinary tract infection may increase the risk of childhood asthma - C.-H. Lin; Y.-C. Wang; W.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

The juxtamembrane sequence of the Hepatitis C virus polymerase can affect RNA synthesis and inhibition by allosteric polymerase inhibitors - Y. Wen; X. Lin; B. Fan; C. T. Ranjith-Kumar; C. C. Kao (Virus Genes, 2015)

Hyperglycemia down-regulates cGMP-dependent protein kinase I expression in first trimester cytotrophoblast cells - Tammy Nguyen; Saunders Lin; Ahmed F. Pantho; Belinda M. Kohl-Thomas; Madhava R. Beeram; David C. Zawieja; Thomas J. Kuehl; M. Nasir Uddin (Molecular and Cellular Biochemistry, 2015)

Statins can increase the risk of herpes zoster infection in Asia - H.-H. Chen; C.-L. Lin; C.-J. Yeh; S.-Y. Yeh; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Association between Helicobacter pylori and pancreatic cancer risk: a meta-analysis - Annaka Schulte; Nirmala Pandeya; Jonathan Fawcett; Lin Fritschi; Harvey A. Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2015)

Treating cutaneous aging with patented technologies - Wing-Fu Lai; Marie C Lin (Journal of Biosciences, 2015)

Balanitis is a risk factor for herpes zoster - C.-Y. Hsu; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Persistent organic pollutants in tropical coastal and offshore environment: part A—atmospheric polycyclic aromatic hydrocarbons - I.-C. Lai; C.-L. Lee; F.-C. Ko; J.-C. Lin; H.-C. Huang (International Journal of Environmental Science and Technology, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Clustering of Clinical and Environmental Escherichia coli O104 Isolates Using the DiversiLab™ Repetitive Sequence-Based PCR System - N. M. Herbold; L. M. Clotilde; K. M. Anderson; J. Kase; G. L. Hartman; S. Himathongkham; A. Lin; C. R. Lauzon (Current Microbiology, 2015)

Clinical manifestations and prognostic factors of Morganella morganii bacteremia - T.-Y. Lin; M.-C. Chan; Y.-S. Yang; Y. Lee; K.-M. Yeh; J.-C. Lin; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Establishment of a novel, eco-friendly transgenic pig model using porcine pancreatic amylase promoter-driven fungal cellulase transgenes - Y. S. Lin; C. C. Yang; C. C. Hsu; J. T. Hsu; S. C. Wu; C. J. Lin; W. T. K. Cheng (Transgenic Research, 2015)

Genome and physiology of the ascomycete filamentous fungus X eromyces bisporus , the most xerophilic organism isolated to date - Su‐lin L. Leong; Henrik Lantz; Olga V. Pettersson; Jens C. Frisvad; Ulf Thrane; Hermann J. Heipieper; Jan Dijksterhuis; Manfred Grabherr; Mats Pettersson; Christian Tellgren‐Roth; Johan Schnürer (Environmental Microbiology, 2015)
Summary X eromyces bisporus can grow on sugary substrates down to 0.61, an extremely low water activity. Its genome size is approximately 22 Mb . Gene clusters encoding for secondary metabolites were conspicuously absent; secondary metabolites were not detected experimentally. Thus, in its ‘dry’ but nutrient‐rich environment, X . bisporus appears to have relinquished abilities for combative interactions. Elements to sense/signal osmotic stress, e.g. HogA pathway, were present in X . bisporus . However, transcriptomes at optimal (∼ 0.89) versus low a w (0.68) revealed differential expression of only a few stress‐related genes; among these, certain (not all) steps for glycerol synthesis were upregulated. X eromyces bisporus increased glycerol production during hypo‐ and hyper‐osmotic stress, and much of its wet weight comprised water and rinsable solutes; leaked solutes may form a protective slime. X eromyces bisporus and other food‐borne moulds increased membrane fatty acid saturation as water activity decreased. Such modifications did not appear to be transcriptionally regulated in X . bisporus ; however, genes modulating sterols, phospholipids and the cell wall were differentially expressed. X eromyces bisporus was previously proposed to be a ‘chaophile’, preferring solutes that disorder biomolecular structures. Both X . bisporus and the closely related xerophile, X erochrysium xerophilum , with low membrane unsaturation indices, could represent a phylogenetic cluster of ‘chaophiles’.

Chelator-enhanced phytoextraction of copper and zinc by sunflower, Chinese cabbage, cattails and reeds - T. Y. Yeh; C. L. Lin; C. F. Lin; C. C. Chen (International Journal of Environmental Science and Technology, 2015)

Helicobacter pylori infection and the risk of acute coronary syndrome: a nationwide retrospective cohort study - C.-Y. Lai; T.-Y. Yang; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

High seroprevalence of human herpesvirus type 8 in patients with hepatocellular carcinoma - C.-C. Su; K.-C. Tseng; M.-N. Lin; T.-C. Hsieh; T.-Y. Chu (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

Transynaptic Changes Evident in Peripheral Axonal Function After Acute Cerebellar Infarct - William Huynh; Cindy S-Y. Lin; Arun V. Krishnan; Steve Vucic; Matthew C. Kiernan (The Cerebellum, 2014)

Description of a New Species of the Genus Macromotettixoides Zheng (Orthoptera: Tetrigoidea: Metrodorinae) from China - W A Deng; C-L Lei; Z M Zheng; X D Li; L L Lin; M P Lin (Neotropical Entomology, 2014)

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

The complex interplay among bacterial motility and virulence factors in different Escherichia coli infections - C. Y. Kao; W. H. Lin; C. C. Tseng; A. B. Wu; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Numerical modeling of a strong dust event over the south China region in March 2010 - Kim-Chiu Chow; Lin Su; Jimmy C. H. Fung; Hui Ma; Alexis K. H. Lau (Meteorology and Atmospheric Physics, 2014)

Trends in the susceptibility of commonly encountered clinically significant anaerobes and susceptibilities of blood isolates of anaerobes to 16 antimicrobial agents, including fidaxomicin and rifaximin, 2008–2012, northern Taiwan - F. D. Wang; C. H. Liao; Y. T. Lin; W. H. Sheng; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Effect of nano-hematite morphology on photocatalytic activity - Y. H. Chen; C. C. Lin (Physics and Chemistry of Minerals, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

The first record, tagging and release of a neonatal whale shark Rhincodon typus in Taiwan - H. H. Hsu; C. Y. Lin; S. J. Joung (Journal of Fish Biology, 2014)
On 27 October 2013, a Rhincodon typus was apparently chased by a group of Caranx ignobilis into nearshore waters near Green Island (Ludao), east of Taiwan. A fisherman brought it back to port where it was kept in a small sea pen until release. The R. typus was 78 cm total length, and was tagged and released on 29 October 2013.

A middle Cambrian shallow water trilobite fauna from the Comstock Formation, near Queenstown, western Tasmania - J. b. Jago; C. j. Bentley; Lin Tian-rui; K. d. Corbett (Australian Journal of Earth Sciences, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Parental occupational paint exposure and risk of childhood leukemia in the offspring: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Lin Fritschi; Catherine Metayer; Claire Infante-Rivard; Corrado Magnani; Eleni Petridou; Eve Roman; Logan G. Spector; Peter Kaatsch; Jacqueline Clavel; Elizabeth Milne; John D. Dockerty; et al. (Cancer Causes & Control, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of pulmonary tuberculosis among patients with appendectomy in Taiwan - S.-W. Lai; C.-L. Lin; K.-F. Liao; S.-M. Tsai (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Clinical and microbiological characteristics of Klebsiella pneumoniae from community-acquired recurrent urinary tract infections - W. H. Lin; C. Y. Kao; D. C. Yang; C. C. Tseng; A. B. Wu; C. H. Teng; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Erratum to: Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

Comparison of flucytosine and fluconazole combined with amphotericin B for the treatment of HIV-associated cryptococcal meningitis: a systematic review and meta-analysis - Z.-W. Yao; X. Lu; C. Shen; D.-F. Lin (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

An influenza A virus hemagglutinin (HA) epitope inserted in and expressed from several loci of the infectious bursal disease virus genome induces HA-specific antibodies - Yung-Yi C. Mosley; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Development of a selective and differential medium for capsulated L actococcus garvieae - C‐I Chang; C‐F Lee; J‐M Tsai; C‐C Wu; L‐H Chen; S‐C Chen; K‐J Lin (Journal of Fish Diseases, 2014)
A selective and differential medium termed ‘ LG agar’ was developed for the isolation and presumptive identification of L actococcus garvieae that results in black colonies with red halos. In this study, all 14 strains of L . garvieae and only 9 of the 148 strains representing 38 other species were able to grow on the LG agar. The nine viable strains on LG agar plates (including E nterococcus faecalis , E nterococcus faecium , L actococcus lactis , V ibrio fluvialis , V ibrio furnissii , V ibrio mimicus and V ibrio salmonicida ) were further differentiated from L . garvieae by various colours or colony features. Colonies isolated from the mixing culture and the infected giant sea perch using LG agar plates were all positively identified as L . garvieae by conventional tests and 16 S r DNA sequencing. Furthermore, LG agar discriminated capsulated strains of L . garvieae , which were believed to be correlated with pathogens of fish and shellfish, from non‐capsulated ones by colony appearances. The specificity and differentiating ability of LG agar suggest that this medium displays considerable potential for primary isolation and presumptive identification of L . garvieae from pathological and environmental samples.

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Mechanism-Based Pharmacokinetic Modeling to Evaluate Transporter-Enzyme Interplay in Drug Interactions and Pharmacogenetics of Glyburide - Manthena V. S. Varma; Renato J. Scialis; Jian Lin; Yi-An Bi; Charles J. Rotter; Theunis C. Goosen; Xin Yang (The AAPS Journal, 2014)

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Composition of bacterial communities in sand dunes of subtropical coastal forests - Yu-Te Lin; William B. Whitman; David C. Coleman; Tsai-Huei Chen; Chih-Yu Chiu (Biology and Fertility of Soils, 2014)

Identification of a stable molecular signature in mammary tumor endothelial cells that persists in vitro - Lin Xiao; J. Chuck Harrell; Charles M. Perou; Andrew C. Dudley (Angiogenesis, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

miRNA profiling in leaf and cork tissues of Quercus suber reveals novel miRNAs and tissue-specific expression patterns - Inês Chaves; Yao-Cheng Lin; C. Pinto-Ricardo; Yves Van de Peer; Célia Miguel (Tree Genetics & Genomes, 2014)

Two New Species of the Genus Xistra Bolivar (Orthoptera: Tetrigidae) from China - X D Li; W A Deng; Z M Zheng; M P Lin; C W Lu (Neotropical Entomology, 2014)

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Pressure-assisted cyclic washing of heavy-metal-contaminated sediments - C. E. Lin; P. K. A. Hong; H. Y. Chiu; R. Y. Surampalli; C. T. Lin; C. M. Kao (International Journal of Environmental Science and Technology, 2014)

Association between polymorphisms in the csrRS two-component regulatory system and invasive group A streptococcal infection - J.-N. Lin; L.-L. Chang; C.-H. Lai; H.-H. Lin; Y.-H. Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Effects of Parkinson’s disease on optic flow perception for heading direction during navigation - Cheng-Chieh Lin; Robert C. Wagenaar; Daniel Young; Elliot L. Saltzman; Xiaolin Ren; Sandy Neargarder; Alice Cronin-Golomb (Experimental Brain Research, 2014)

Detection of human JCPyV and BKPyV in diffuse large B-cell lymphoma of the GI tract - C. E. Tseng; C. M. Yeh; C. Y. Fang; J. Shay; P. L. Chen; M. C. Lin; D. Chang; M. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Blockade of the renin–angiotensin system inhibits growth of colorectal cancer liver metastases in the regenerating liver - Shir Lin Koh; E. I. Ager; P. L. N. Costa; C. Malcontenti-Wilson; V. Muralidharan; C. Christophi (Clinical & Experimental Metastasis, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Lasting neurobehavioral abnormalities in rats after neonatal activation of serotonin 1A and 1B receptors: possible mechanisms for serotonin dysfunction in autistic spectrum disorders - Nidhi Khatri; Kimberly L. Simpson; Rick C. S. Lin; Ian A. Paul (Psychopharmacology, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Using the VIKOR method to evaluate the design of a water quality monitoring network in a watershed - C.-L. Chang; Y.-T. Lin (International Journal of Environmental Science and Technology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Toxic effects of hexaflumuron on the development of Coccinella septempunctata - Caihong Yu; Maoran Fu; Ronghua Lin; Yan Zhang; Liu Yongquan; Hui Jiang; Theo C. M. Brock (Environmental Science and Pollution Research, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Evaluating the protective efficacy of antigen combinations against P hotobacterium damselae ssp. piscicida infections in cobia, Rachycentron canadum L. - L‐P Ho; C‐J Chang; H‐C Liu; H‐L Yang; J H‐Y Lin (Journal of Fish Diseases, 2014)
Cobia, Rachycentron canadum L., is a very important aquatic fish that faces the risk of infection with the bacterial pathogen P hotobacterium damselae ssp. piscicida , and there are few protective approaches available that use multiple antigens. In the present study, potent bivalent antigens from P . damselae ssp. piscicida showed more efficient protection than did single antigens used in isolation. In preparations of three antigens that included recombinant heat shock protein 60 ( rHSP 60), recombinant α‐enolase ( rENOLASE ) and recombinant glyceraldehyde‐3‐phosphate dehydrogenase ( rGAPDH ), we analysed the doses that elicited the best immune responses and found that this occurred at a total of 30 μg of antigen per fish. Subsequently, vaccination of fish with rHSP 60, rENOLASE and rGAPDH achieved 46.9, 52 and 25% relative per cent survival (RPS), respectively. In addition, bivalent subunit vaccines – combination I ( rHSP 60 + rENOLASE ), combination II ( rENOLASE + rGAPDH ) and combination III ( rHSP 60 + rGAPDH ) – were administered and the RPS in these groups (65.6, 64.0 and 48.4%, respectively), was higher than that achieved with single‐antigen administration. Finally, in combination IV , the trivalent vaccine rHSP 60 + rENOLASE + rGAPDH , the RPS was 1.6%. Taken together, our results suggest that combinations of two antigens may achieve a better efficiency than monovalent or trivalent antigens, and this may provide new insights into pathogen prevention strategies.

Motor Cortex Excitability in Acute Cerebellar Infarct - William Huynh; Arun V. Krishnan; Steve Vucic; Cindy S-Y. Lin; Matthew C. Kiernan (The Cerebellum, 2013)

The role of MrbHLH1 and MrMYB1 in regulating anthocyanin biosynthetic genes in tobacco and Chinese bayberry (Myrica rubra) during anthocyanin biosynthesis - Xiao-Fen Liu; Xue-Ren Yin; Andrew C. Allan; Kui Lin-Wang; Yan-Na Shi; Yu-Ji Huang; Ian B. Ferguson; Chang-Jie Xu; Kun-Song Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Older individuals with HIV infection have greater memory deficits than younger individuals - I. Lin Tan; B. R. Smith; Edward Hammond; Heidi Vornbrock-Roosa; Jason Creighton; O. Selnes; Justin C. McArthur; Ned Sacktor (Journal of NeuroVirology, 2013)

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

Role of HO-1 in the Arsenite-Induced Neurotoxicity in Primary Cultured Cortical Neurons - Y. C. Teng; Y. I. Tai; Y. H. Lee; A. M. Y. Lin (Molecular Neurobiology, 2013)

Volatile halocarbon emissions by three tropical brown seaweeds under different irradiances - Fiona Seh-Lin Keng; Siew-Moi Phang; Noorsaadah Abd Rahman; Emma C. Leedham; Claire Hughes; Andrew D. Robinson; Neil R. P. Harris; John A. Pyle; William T. Sturges (Journal of Applied Phycology, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Pushover analysis of reinforced concrete frames considering shear failure at beam-column joints - Y. C. Sung; T. K. Lin; C. C. Hsiao; M. C. Lai (Earthquake Engineering and Engineering Vibration, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Warming up to climate change: a participatory approach to engaging with agricultural stakeholders in the Southeast US - Wendy-Lin Bartels; Carrie A. Furman; David C. Diehl; Fred S. Royce; Daniel R. Dourte; Brenda V. Ortiz; David F. Zierden; Tracy A. Irani; Clyde W. Fraisse; James W. Jones (Regional Environmental Change, 2013)

Impacts of Dung Combustion on the Carbon Cycle of Alpine Grassland of the North Tibetan Plateau - Zengrang Xu; Shengkui Cheng; Lin Zhen; Ying Pan; Xianzhou Zhang; Junxi Wu; Xiuping Zou; G. C. Dhruba Bijaya (Environmental Management, 2013)

Prediction of the In Vivo Force–Velocity Relationship of Slow Human Skeletal Muscle from Measurements in Myofibers - Sampath K. Gollapudi; David C. Lin (Annals of Biomedical Engineering, 2013)

Identification of Streptomyces sp. nov. WH26 producing cytotoxic compounds isolated from marine solar saltern in China - Haizhou Liu; Lin Xiao; Jianteng Wei; John C. Schmitz; Ming Liu; Cuicui Wang; Linyou Cheng; Ning Wu; Lei Chen; Yuyan Zhang; Xiukun Lin (World Journal of Microbiology and Biotechnology, 2013)

Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2013)

Effect of two maximal isometric contractions on eccentric exercise-induced muscle damage of the elbow flexors - Trevor C. Chen; Hsin-Lian Chen; Ming-Ju Lin; Che-Hsiu Chen; Alan J. Pearce; Kazunori Nosaka (European Journal of Applied Physiology, 2013)

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

Quantitative exposure metrics for sleep disturbance and their association with breast cancer risk - Jennifer Girschik; Lin Fritschi; Thomas C. Erren; Jane Heyworth (Cancer Causes & Control, 2013)

Controlled Release of Simvastatin from In situ Forming Hydrogel Triggers Bone Formation in MC3T3-E1 Cells - Yoon Shin Park; Allan E. David; Kyung Min Park; Chia-Ying Lin; Khoi D. Than; Kyuri Lee; Jun Beom Park; Inho Jo; Ki Dong Park; Victor C. Yang (The AAPS Journal, 2013)

High-resolution profiles of iron, manganese, cobalt, cadmium, copper and zinc in the pore water of estuarine sediment - Z. Yang; W. Guo; Y. Fan; C. Lin; M. He (International Journal of Environmental Science and Technology, 2013)

Role of K1 capsule antigen in cirrhotic patients with Escherichia coli spontaneous bacterial peritonitis in southern Taiwan - M. C. Wang; W. H. Lin; C. C. Tseng; A. B. Wu; C. H. Teng; J. J. Yan; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Seismic health monitoring of RC frame structures using smart aggregates - Wen-I Liao; C. H. Lin; J. S. Hwang; G. Song (Earthquake Engineering and Engineering Vibration, 2013)

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

Climate trends in indices for temperature and precipitation across New York State, 1948–2008 - T. Z. Insaf; S. Lin; S. C. Sheridan (Air Quality, Atmosphere & Health, 2013)

Rural tourism development in China: Principles, models and the future - Ling-en Wang; Sheng-kui Cheng; Lin-sheng Zhong; Song-lin Mu; Bijaya G. C. Dhruba; Guo-zhu Ren (Journal of Mountain Science, 2013)

Feasibility Study on Quantitative Measurements of Singlet Oxygen Generation Using Singlet Oxygen Sensor Green - Huiyun Lin; Yi Shen; Defu Chen; Lisheng Lin; Brian C. Wilson; Buhong Li; Shusen Xie (Journal of Fluorescence, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Evaluation and QTL mapping of phosphorus concentration in soybean seed - Keith E. King; Nick Lauter; Shun Fu Lin; M. Paul Scott; Randy C. Shoemaker (Euphytica, 2013)

Selenoprotein P and Yunnan Endemic Sudden Cardiac Death—an Ecological Study - Q. Li; X. Z. Li; T. Wang; L. W. Zhou; H. Q. Feng; L. Gao; J. R. Pei; C. Lin; C. X. Jiang (Biological Trace Element Research, 2013)

A Survey of Applications of Biological Products for Drug Interference of Immunogenicity Assays - Yow-Ming C. Wang; Lanyan Fang; Lin Zhou; Jie Wang; Hae-Young Ahn (Pharmaceutical Research, 2012)

Escherichia coli Membranes Depleted of SecYEG Elicit SecA-Dependent Ion-Channel Activity but Lose Signal Peptide Specificity - Bor-Ruei Lin; Ying-Hsin Hsieh; Chun Jiang; Phang C. Tai (The Journal of Membrane Biology, 2012)

Comparison of point and array-computed rotations for the TAIGER explosions of 4 March 2008 - Lauren M. Kendall; Charles A. Langston; W. H. K. Lee; C. J. Lin; C. C. Liu (Journal of Seismology, 2012)

Effects of rotation motions on strong-motion data - H. C. Chiu; F. J. Wu; C. J. Lin; H. C. Huang; C. C. Liu (Journal of Seismology, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Inflamed tumor-associated adipose tissue is a depot for macrophages that stimulate tumor growth and angiogenesis - Marek Wagner; Rolf Bjerkvig; Helge Wiig; Juan M. Melero-Martin; Ruei-Zeng Lin; Michael Klagsbrun; Andrew C. Dudley (Angiogenesis, 2012)

Characterization of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream isolates at a Taiwanese hospital: clinical impacts of lowered breakpoints for carbapenems - N. Y. Lee; J. J. Wu; S. H. Lin; W. C. Ko; L. H. Tsai; J. J. Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Antigen capture ELISA system for henipaviruses using polyclonal antibodies obtained by DNA immunization - Yoshihiro Kaku; Akira Noguchi; Glenn A. Marsh; Jennifer A. Barr; Akiko Okutani; Kozue Hotta; Boldbaatar Bazartseren; Christopher C. Broder; Akio Yamada; Satoshi Inoue; Lin-Fa Wang (Archives of Virology, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Effects of the fungicide metiram in outdoor freshwater microcosms: responses of invertebrates, primary producers and microbes - Ronghua Lin; Laura Buijse; Mauricio R. Dimitrov; Peter Dohmen; Sujitra Kosol; Lorraine Maltby; Ivo Roessink; Jos A. Sinkeldam; Hauke Smidt; René P. A. Van Wijngaarden; Theo C. M. Brock (Ecotoxicology, 2012)

Phosphorus availability and rice grain yield in a paddy soil in response to long-term fertilization - Z. M. Lan; X. J. Lin; F. Wang; H. Zhang; C. R. Chen (Biology and Fertility of Soils, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Chronic traumatic encephalopathy: neurodegeneration following repetitive concussive and subconcussive brain trauma - Christine M. Baugh; Julie M. Stamm; David O. Riley; Brandon E. Gavett; Martha E. Shenton; Alexander Lin; Christopher J. Nowinski; Robert C. Cantu; Ann C. McKee; Robert A. Stern (Brain Imaging and Behavior, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Norway spruce (Picea abies L.) regeneration and growth of understory trees under single-tree selection silviculture in Finland - C. Julian Lin; Olavi Laiho; Erkki Lähde (European Journal of Forest Research, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Spatial dependence of alveolar angiogenesis in post-pneumonectomy lung growth - Moritz A. Konerding; Barry C. Gibney; Jan P. Houdek; Kenji Chamoto; Maximilian Ackermann; Grace S. Lee; Miao Lin; Akira Tsuda; Steven J. Mentzer (Angiogenesis, 2012)

Differential expression profiling of orange‐spotted grouper larvae, Epinephelus coioides (Hamilton), that survived a betanodavirus outbreak - M‐S Wu; C‐W Chen; C‐H Lin; C‐S Tzeng; C‐Y Chang (Journal of Fish Diseases, 2012)
Nervous necrosis virus (NNV), a piscine nodavirus, has caused serious viral nervous necrosis and viral encephalopathy and retinopathy in hatchery‐reared larvae and juveniles of a wide range of marine teleost species worldwide in the last two decades. Although the mortality of NNV‐infected larvae is nearly 100%, there are still some larvae that survive this catastrophe. To comprehensively understand the variations of these survivors at the molecular level, we collected orange‐spotted grouper larvae that survived an NNV outbreak in an indoor hatchery in southern Taiwan to study differential gene expression. Healthy larvae with high, medium and low levels of detected NNV were compared with morbid larvae using a 9600‐clone‐containing grouper larva cDNA microarray, and differential gene expression was further confirmed by a quantitative real‐time polymerase chain reaction. Significant variation exists in healthy larvae. The following genes were upregulated: adenylate kinase 1‐2, myosin binding protein H‐like, myosin light chain 2, myosin light chain 3, tropomyosin, fast/white muscle troponin T embryonic isoform, and parvalbumin 1 and 2 genes. The following genes were downregulated: apolipoprotein A‐I, trypsinogen, pyruvate kinase and astacin‐like metalloprotease. Moreover, immunoglobulin M heavy chain gene transcription was significantly higher in healthy larvae that had high virus levels, indicating that humoral immunity might protect organisms from viral infection. These results suggest that some non‐immune‐related genes may have played important roles in survival during the larval metamorphosis stage, after betanodavirus infection.

Analysis of quantitative disease resistance to southern leaf blight and of multiple disease resistance in maize, using near-isogenic lines - Araby R. Belcher; John C. Zwonitzer; Jose Santa Cruz; Mathew D. Krakowsky; Chia-Lin Chung; Rebecca Nelson; Consuelo Arellano; Peter J. Balint-Kurti (Theoretical and Applied Genetics, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Genetic diversity of ‘Cadidatus Liberibacter solanacearum’ strains in the United States and Mexico revealed by simple sequence repeat markers - Hong Lin; Md Sajedul Islam; Yang Bai; Amin Wen; Suque Lan; Neil C. Gudmestad; Edwin L. Civerolo (European Journal of Plant Pathology, 2012)

Arsenic content, fractionation, and ecological risk in the surface sediments of lake - S. L. Wang; C. Y. Lin; X. Z. Cao; X. Zhong (International Journal of Environmental Science and Technology, 2012)

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Correlating recurrent radon precursors with local earthquake magnitude and crust strain near the Chihshang fault of eastern Taiwan - T. Kuo; C. Lin; C. Su; C. Liu; C. H. Lin; C. Chang; C. Chiang (Natural Hazards, 2011)

Three new species of Lentinus from northern Thailand - Samantha C. Karunarathna; Zhu L. Yang; Rui-Lin Zhao; Else C. Vellinga; A. H. Bahkali; Ekachai Chukeatirote; Kevin D. Hyde (Mycological Progress, 2011)

Parental occupational exposure to exhausts, solvents, glues and paints, and risk of childhood leukemia - Alison Reid; Deborah C. Glass; Helen D. Bailey; Elizabeth Milne; Bruce K. Armstrong; Frank Alvaro; Lin Fritschi (Cancer Causes & Control, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

A Bayesian population analysis of the development of type 2 diabetes in the offspring of diabetic parents - C. W. Lin; J. H. Warram; P. Veng-Pedersen (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

A numerical simulation of the effect of the number concentration of cloud droplets on Typhoon Chanchu - WenShi Lin; Suishan Xu; C.-H. Sui (Meteorology and Atmospheric Physics, 2011)

Assessment of nitrogen contamination of groundwater in paddy and upland fields - Y. H. Kao; C.-W. Liu; C. S. Jang; S. W. Zanh; K. H. Lin (Paddy and Water Environment, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Decreased expression of Flightless I, a gelsolin family member and developmental regulator, in early-gestation fetal wounds improves healing - Cheng-Hung Lin; James M. Waters; Barry C. Powell; Ruth M. Arkell; Allison J. Cowin (Mammalian Genome, 2011)

Learning Through Service: Student Perceptions on Volunteering at Interprofessional Hepatitis B Student-run Clinics - Leslie C. Sheu; Patricia Zheng; Anabelle D. Coelho; Lisa D. Lin; Patricia S. O’Sullivan; Bridget C. O’Brien; Albert Y. Yu; Cindy J. Lai (Journal of Cancer Education, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Determining the subjective and physiological effects of BZP combined with TFMPP in human males - Joanne C. Lin; Reem K. Jan; HeeSeung Lee; Maree-Ann Jensen; Rob R. Kydd; Bruce R. Russell (Psychopharmacology, 2011)

Influence of indomethacin on the ventilatory and cerebrovascular responsiveness to hypoxia - Jui-Lin Fan; Keith R. Burgess; Kate N. Thomas; Karen C. Peebles; Samuel J. E. Lucas; Rebekah A. I. Lucas; James D. Cotter; Philip N. Ainslie (European Journal of Applied Physiology, 2011)

The controlled in vitro susceptibility of gastrointestinal pathogens to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Quantitative trait loci for temperature-sensitive resistance to Puccinia striiformis f. sp. tritici in wheat cultivar Flinor - J. Feng; L. L. Zuo; Z. Y. Zhang; R. M. Lin; Y. Y. Cao; S. C. Xu (Euphytica, 2011)

Contributions of dry and wet depositions of polychlorinated dibenzo-p-dioxins and dibenzofurans to a contaminated site resulting from a penetachlorophenol manufacturing process - Hwang J. Chang; Shizoom Wang; Ya F. Wang; Hsing W. Li; Lin C. Wang (Environmental Monitoring and Assessment, 2011)

Differential Proteomic Analysis of Temperature-Induced Autolysis in Mycelium of Pleurotus tuber-regium - Bifang Huang; Wenxiong Lin; Peter C. K. Cheung; Jinzhong Wu (Current Microbiology, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Comparison in eccentric exercise-induced muscle damage among four limb muscles - Trevor C. Chen; Kun-Yi Lin; Hsin-Lian Chen; Ming-Ju Lin; Kazunori Nosaka (European Journal of Applied Physiology, 2011)

Evaluation of potential integration of entrapped mixed microbial cell and membrane bioreactor processes for biological wastewater treatment/reuse - Jia Zhu; C. F. Lin; J. C. M. Kao; P. Y. Yang (Clean Technologies and Environmental Policy, 2011)

Long-term changes of dissolved oxygen, hypoxia, and the responses of the ecosystems in the East China Sea from 1975 to 1995 - X. Ning; C. Lin; J. Su; C. Liu; Q. Hao; F. Le (Journal of Oceanography, 2011)

Urban China in transformation: Hybrid economy, juxtaposed space, and new testing ground for geographical enquiries - George C S Lin (Chinese Geographical Science, 2011)

Probing Mechanical Adaptation of Neurite Outgrowth on a Hydrogel Material Using Atomic Force Microscopy - Frank Xue Jiang; David C. Lin; Ferenc Horkay; Noshir A. Langrana (Annals of Biomedical Engineering, 2011)

Dietary patterns and breast cancer risk among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Jian-Hua Fu; Shou-Zhen Cheng; Yu-Ming Chen; Fang-Yu Lin (Cancer Causes & Control, 2011)

Mobilization and transport of coarse woody debris to the oceans triggered by an extreme tropical storm - A. J. West; C.-W. Lin; T.-C. Lin; R. G. Hilton; S.-H. Liu; C.-T. Chang; K.-C. Lin; A. Galy; R. B. Sparkes; N. Hovius (Limnology and Oceanography, 2011)
A significant consequence of Typhoon Morakot in August 2009 was the production of vast volumes of driftwood in Pacific Asia. We have quantified the flux of this coarse woody debris (CWD) to the oceans from typhoon‐triggered landslides in Taiwan, where Morakot made landfall, by combining remote sensing (using FORMOSAT‐2 imagery and aerial photography), analysis of forest biomass, and field observations. A total of 3.8–8.4 Tg CWD was transported to the oceans, carrying 1.8–4.0 Tg of organic carbon. In addition to the local effects on the marine and coastal environment from such a highly concentrated flux of carbon and nutrients, storm‐driven mobilization of CWD may represent a significant, if infrequent, transfer of terrestrial biomass to the oceans. If the frequency of relatively rare, extreme storms such as Morakot increases in a changing climate, this transport mechanism may play an important role in feedbacks between global climate, storm intensity, and carbon cycling.

Global patterns in the biogeography of bacterial taxa - Diana R. Nemergut; Elizabeth K. Costello; Micah Hamady; Catherine Lozupone; Lin Jiang; Steven K. Schmidt; Noah Fierer; Alan R. Townsend; Cory C. Cleveland; Lee Stanish; Rob Knight (Environmental Microbiology, 2011)
Summary Bacteria control major nutrient cycles and directly influence plant, animal and human health. However, we know relatively little about the forces shaping their large‐scale ecological ranges. Here, we reveal patterns in the distribution of individual bacterial taxa at multiple levels of phylogenetic resolution within and between Earth's major habitat types. Our analyses suggest that while macro‐scale habitats structure bacterial distribution to some degree, abundant bacteria (i.e. detectable using 16S rRNA gene sequencing methods) are confined to single assemblages. Additionally, we show that the most cosmopolitan taxa are also the most abundant in individual assemblages. These results add to the growing body of data that support that the diversity of the overall bacterial metagenome is tremendous. The mechanisms governing microbial distribution remain poorly understood, but our analyses provide a framework with which to test the importance of macro‐ecological environmental gradients, relative abundance, neutral processes and the ecological strategies of individual taxa in structuring microbial communities.

QTL analysis and candidate gene mapping for skin and flesh color in sweet cherry fruit (Prunus avium L.) - Suneth S. Sooriyapathirana; Amjad Khan; Audrey M. Sebolt; Dechun Wang; Jill M. Bushakra; Kui Lin-Wang; Andrew C. Allan; Susan E. Gardiner; David Chagné; Amy F. Iezzoni (Tree Genetics & Genomes, 2010)

Groundwater Assessment at Manukan Island, Sabah: Multidisplinary Approaches - S. M. Praveena; C. Y. Lin; A. Z. Aris; M. H. Abdullah (Natural Resources Research, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Effects of dietary fat on spontaneous metastasis of Lewis lung carcinoma in mice - Lin Yan; Lana C. DeMars (Clinical & Experimental Metastasis, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Tikhonov adaptively regularized gamma variate fitting to assess plasma clearance of inert renal markers - Carl A. Wesolowski; Richard C. Puetter; Lin Ling; Paul S. Babyn (Journal of Pharmacokinetics and Pharmacodynamics, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.

Determining the subjective effects of TFMPP in human males - Reem K. Jan; Joanne C. Lin; HeeSeung Lee; Janie L. Sheridan; Rob R. Kydd; Ian J. Kirk; Bruce R. Russell (Psychopharmacology, 2010)

Phylogeny of Salsoleae s.l. (Chenopodiaceae) based on DNA sequence data from ITS, psbB–psbH, and rbcL, with emphasis on taxa of northwestern China - Zhi-Bin Wen; Ming-Li Zhang; Ge-Lin Zhu; Stewart C. Sanderson (Plant Systematics and Evolution, 2010)

In Vitro–In Vivo Correlations of Scalable PLGA-Risperidone Implants for the Treatment of Schizophrenia - Laura C. Amann; Michael J. Gandal; Robert Lin; Yuling Liang; Steven J. Siegel (Pharmaceutical Research, 2010)

Simultaneous declines in radon and methane precursory to 2008 M W 5.0 Antung earthquake: corroboration of in-situ volatilization - T. Kuo; W. Cheng; C. Lin; K. Fan; G. Chang; T. Yang (Natural Hazards, 2010)

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Clinical and microbiological characteristics of community-acquired thoracic empyema or complicated parapneumonic effusion caused by Klebsiella pneumoniae in Taiwan - Y.-T. Lin; T.-L. Chen; L. K. Siu; S.-F. Hsu; C.-P. Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Bacterial community of very wet and acidic subalpine forest and fire-induced grassland soils - Yu-Te Lin; Ching-Ping Lin; Shu-Miaw Chaw; William B. Whitman; David C. Coleman; Chih-Yu Chiu (Plant and Soil, 2010)

WRN mutations in Werner syndrome patients: genomic rearrangements, unusual intronic mutations and ethnic-specific alterations - Katrin Friedrich; Lin Lee; Dru F. Leistritz; Gudrun Nürnberg; Bidisha Saha; Fuki M. Hisama; Daniel K. Eyman; Davor Lessel; Peter Nürnberg; Chumei Li; María J. Garcia-F-Villalta; Carolien M. Kets; et al. (Human Genetics, 2010)

Therapeutic HPV DNA vaccines - Ken Lin; Elena Roosinovich; Barbara Ma; Chien-Fu Hung; T.-C. Wu (Immunologic Research, 2010)

Hypoxia increases Sca-1/CD44 co-expression in murine mesenchymal stem cells and enhances their adipogenic differentiation potential - M. G. Valorani; A. Germani; W. R. Otto; L. Harper; A. Biddle; C. P. Khoo; W. R. Lin; M. I. Hawa; P. Tropel; M. P. Patrizi; P. Pozzilli; M. R. Alison (Cell and Tissue Research, 2010)

Coupled weather research and forecasting–stochastic time-inverted lagrangian transport (WRF–STILT) model - Thomas Nehrkorn; Janusz Eluszkiewicz; Steven C. Wofsy; John C. Lin; Christoph Gerbig; Marcos Longo; Saulo Freitas (Meteorology and Atmospheric Physics, 2010)

Optimization of product line design for environmentally conscious technologies in notebook industry - K. H. Lin; L. H. Shih; S. C. Lee (International Journal of Environmental Science and Technology, 2010)

A Simple Allometric Diffusion-Based Biokinetic Model to Predict Cu(II) Uptake Across Gills of Freshwater Clam Corbicula fluminea - W.-Y. Chen; C.-M. Lin; Y.-R. Ju; C.-M. Liao (Bulletin of Environmental Contamination and Toxicology, 2010)

Estimation of aseismic crustal-strain using radon precursors of the 2003 M 6.8, 2006 M 6.1, and 2008 M 5.0 earthquakes in eastern Taiwan - T. Kuo; C. Lin; G. Chang; K. Fan; W. Cheng; C. Lewis (Natural Hazards, 2010)

Skin cooling aids cerebrovascular function more effectively under severe than moderate heat stress - Rebekah A. I. Lucas; Philip N. Ainslie; Jui-Lin Fan; Luke C. Wilson; Kate N. Thomas; James D. Cotter (European Journal of Applied Physiology, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Occurrence of Aliphatic Hydrocarbons in Water, Suspended Particulate Matter and Sediments of Daliao River System, China - W. Guo; M. C. He; Z. F. Yang; C. Y. Lin; X. C. Quan (Bulletin of Environmental Contamination and Toxicology, 2010)

Sun/shade adaptations of the photosynthetic apparatus of Hoya carnosa, an epiphytic CAM vine, in a subtropical rain forest in northeastern Taiwan - Craig E. Martin; Rebecca C.-C. Hsu; Teng-Chiu Lin (Acta Physiologiae Plantarum, 2010)

Molecular phylogeny of three ambiguous ciliate genera: Kentrophoros , Trachelolophos and Trachelotractus (Alveolata, Ciliophora) - Shan Gao; Michaela C. Strüder-Kypke; Khaled A. S. Al-Rasheid; Xiaofeng Lin; Weibo Song (Zoologica Scripta, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Coordinated regulation of anthocyanin biosynthesis in Chinese bayberry (Myrica rubra) fruit by a R2R3 MYB transcription factor - Shan-Shan Niu; Chang-Jie Xu; Wang-Shu Zhang; Bo Zhang; Xian Li; Kui Lin-Wang; Ian B. Ferguson; Andrew C. Allan; Kun-Song Chen (Planta, 2010)

The speed of mitochondrial movement is regulated by the cytoskeleton and myosin in Picea wilsonii pollen tubes - Maozhong Zheng; Qinli Wang; Yan Teng; Xiaohua Wang; Feng Wang; Tong Chen; Jozef Šamaj; Jinxing Lin; David C. Logan (Planta, 2010)

Velocity structure and gas hydrate saturation estimation on active margin off SW Taiwan inferred from seismic tomography - Win-Bin Cheng; S. S. Lin; T. K. Wang; C. S. Lee; C. S. Liu (Marine Geophysical Research, 2010)

Tri-directional shaking table tests of vibration sensitive equipment with static dynamics interchangeable-ball pendulum system - C. S. Tsai; Yung-Chang Lin; Wen-Shin Chen; H. C. Su (Earthquake Engineering and Engineering Vibration, 2010)

Effects of two species of inorganic arsenic on the nutrient physiology of rice seedlings - Hai Bin Wang; H. B. He; G. D. Yang; C. Y. Ye; B. H. Niu; W. X. Lin (Acta Physiologiae Plantarum, 2010)

Microbiological Endogenous Processes in Biological Wastewater Treatment Systems - Xiao-Di Hao; Qi-Lin Wang; Jing-Yi Zhu; Mark C. M. Van Loosdrecht (Critical Reviews in Environmental Science and Technology, 2010)

Artificial neural network analysis for reliability prediction of regional runoff utilization - S. C. Lee; H. T. Lin; T. Y. Yang (Environmental Monitoring and Assessment, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

Seroprevalence of Toxoplasma gondii infection in breeding sows in Western Fujian Province, China - C. Q. Huang; Y. Y. Lin; A. L. Dai; X. H. Li; X. Y. Yang; Z. G. Yuan; X. Q. Zhu (Tropical Animal Health and Production, 2010)

Effect of the climate shift around mid 1970s on the relationship between wintertime Ural blocking circulation and East Asian climate - Lin Wang; Wen Chen; Wen Zhou; Johnny C. L. Chan; David Barriopedro; Ronghui Huang (International Journal of Climatology, 2010)
Blocking variability over the Ural Mountain region in the boreal winter and its relationship with the East Asian winter climate is investigated. The climate shift around mid 1970s has been shown to exert a significant influence on the blocking pattern. In contrast with the years before 1976/1977, the Ural blocking signal after 1976/1977 is found to propagate less into the stratosphere and more eastward in the troposphere to East Asia, which therefore exerts more influence on the East Asian winter climate. This enhanced Ural blocking–East Asian climate relationship amplifies the impact of Ural blocking on East Asia and, with the background of decreasing Ural blocking, contributes to the higher frequency of warm winters in this region. Further analyses suggest that the NAM‐related stratospheric polar vortex strength and its modulation on the propagation of atmospheric stationary waves can account for this change, with the key area being located in the North Atlantic region. Copyright © 2009 Royal Meteorological Society

Determining the subjective and physiological effects of BZP on human females - Joanne C. Lin; Nisha Bangs; HeeSeung Lee; Rob R. Kydd; Bruce R. Russell (Psychopharmacology, 2009)

Meat and egg consumption and risk of breast cancer among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Yu-Ming Chen; Fang-Yu Lin; Jian-Hua Fu; Shou-Zhen Cheng (Cancer Causes & Control, 2009)

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Do otolith annular structures correspond to the first freshwater entry for yellow European eels Anguilla anguilla in the Baltic countries? - Y.‐J. Lin; J.‐C. Shiao; L. Ložys; M. Plikšs; A. Minde; Y. Iizuka; I. Rašals; W.‐N. Tzeng (Journal of Fish Biology, 2009)
To examine the relationship between freshwater entry and otolith annular structures, a total of 113 naturally recruited European eels Anguilla anguilla from Lithuania and Latvia that entered fresh water at least once were collected. In some individuals (8·3–11·3%), the first freshwater entry coincided with a dark check that was distinctly different from neighbouring annuli. In most individuals (81·7–84·9%), the first freshwater entry occurred on rings and increments indistinguishable from other annuli. For the remaining individuals (3·8–10%), the first freshwater entry did not correspond to any otolith ring, band or annulus. According to recent evidence, the observed high correspondence between the first freshwater entry and otolith annuli was more likely due to the movement into fresh water during winter when the annulus was deposited, rather than stress resulting from habitat change. Consequently, the age estimation based on otoliths might be less influenced by this habitat change during the yellow eel stage.

Application of integrated GIS and multimedia modeling on NPS pollution evaluation - C. E. Lin; C. M. Kao; Y. C. Lai; W. L. Shan; C. Y. Wu (Environmental Monitoring and Assessment, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

Effects of grape xylem sap and cell wall constituents on in vitro growth, biofilm formation and cellular aggregation of Xylella fastidiosa - Davis W. Cheng; Hong Lin; M. Andrew Walker; Drake C. Stenger; Edwin L. Civerolo (European Journal of Plant Pathology, 2009)

Coastal Aquaculture Development in Bangladesh: Unsustainable and Sustainable Experiences - A. Kalam Azad; Kathe R. Jensen; C. Kwei Lin (Environmental Management, 2009)

Atmospheric Aerosols over a Southwestern Region of Texas - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; Rafael Tadmor; T. C. Ho (Environmental Modeling & Assessment, 2009)

Spatio‐temporal variation in the elemental compositions of otoliths of southern bluefin tuna Thunnus maccoyii in the Indian Ocean and its ecological implication - C. H. Wang; Y. T. Lin; J. C. Shiao; C. F. You; W. N. Tzeng (Journal of Fish Biology, 2009)
The elements Na, Mg, Mn, Ca, Sr and Ba in otoliths of southern bluefin tuna Thunnus maccoyii , collected from their feeding ground in the central Indian Ocean and spawning ground between southern Java and north‐western Australia were measured by laser‐ablation inductively coupled plasma mass spectrometry (LA‐ICPMS) and compared among sampling locations and developmental stages. The Na, Mg and Mn to Ca concentration ratios were significantly higher at the larval stage than at the adult stage, and the ratio reached a peak at the first inflection point of the otolith, mean ± s.d. 43·3 ± 4·9 days after hatching and decreased sharply to a low level thereafter. The temporal change of the elements:Ca ratios in the first inflection point corresponded to the life stage transition from larva to juvenile, indicating that the uptake rate of elements from ambient waters was significantly influenced by the ontogenetic change in the fish. The elemental composition at the otolith edge differed significantly in sub‐adults on the feeding grounds and adults on the spawning grounds. Thus, the otolith elemental composition can be used as a biological tracer to study the time of the ontogenetic shift and to reconstruct the past migratory environmental history of T. maccoyii . In addition, the elemental composition of the otolith core of the adult was similar between feeding and spawning grounds, indicating that the fish in the Indian Ocean had the same larval origin, which is consistent with the single spawning population hypothesis.

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs - H. C. Lin; G. F. Liu; A. G. Wang; L. J. Kong; X. F. Wang; J. L. Fu (Molecular Biology Reports, 2009)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Accumulation of H2O2 in xylem fluids of cucumber stems during ASM-induced systemic acquired resistance (SAR) involves increased LOX activity and transient accumulation of shikimic acid - T. -C. Lin; H. Ishii (European Journal of Plant Pathology, 2009)

Mathematical modeling and full-scale shaking table tests for multi-curve buckling restrained braces - C. S. Tsai; Yungchang Lin; Wenshin Chen; H. C. Su (Earthquake Engineering and Engineering Vibration, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Study on the Relationship Between Meteorological Conditions and Acid Rain in Mid-Eastern Fujian - C. C. Lin; J. X. Liu; Y. Y. Cai; B. L. Li; Z. L. Wang; B. B. Chen (Bulletin of Environmental Contamination and Toxicology, 2009)

Relationship between cardiopulmonary mortality and cancer risk and quantitative exposure to polycyclic aromatic hydrocarbons, fluorides, and dust in two prebake aluminum smelters - Melissa C. Friesen; Geza Benke; Anthony Del Monaco; Martine Dennekamp; Lin Fritschi; Nick de Klerk; Jan L. Hoving; Ewan MacFarlane; Malcolm R. Sim (Cancer Causes & Control, 2009)

A study of the microphysical processes in a numerically simulated heavy snowfall event in North China: the sensitivity of different snow intercept parameters - Wenshi Lin; Jinping Meng; C.-H. Sui; Weiguang Meng; Jiangnan Li (Meteorology and Atmospheric Physics, 2009)

Atmospheric Aerosol over a Southeastern Region of Texas: Chemical Composition and Possible Sources - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; T. C. Ho (Environmental Modeling & Assessment, 2009)

Colour variation is incongruent with mitochondrial lineages: cryptic speciation and subsequent diversification in a Gulf of California reef fish (Teleostei: Blennioidei) - H‐C. LIN; C. SÁNCHEZ‐ORTIZ; P. A. HASTINGS (Molecular Ecology, 2009)
The Gulf of California endemic reef fish, Acanthemblemaria crockeri (Blennioidei, Chaenopsidae), reportedly has two colour morphs, one with melanic lateral spots (‘Gulf’ morph) and one with orange spots (‘Cape’ morph). In this study, we recorded colour morph in both males and females and collected mitochondrial DNA sequence data for cytochrome c oxidase I (COI) and tRNA‐Pro/D‐loop of specimens from throughout the Gulf to explore the genetic basis of the colour morphs. Two highly divergent (HKY + I distance = 11.9% for COI), reciprocally monophyletic lineages were identified, consistent with the presence of two parapatric species. A 30‐km gap between the distributions of mitochondrial lineages roughly corresponds to a hypothesized former seaway across the Baja California peninsula north of La Paz, although the estimated divergence time (1.84 million years ago) is more recent than the hypothetical seaway (3–4 million years ago). Surprisingly, the distribution of mitochondrial species is not congruent with the distribution of either male or female colour morphs. Our analysis also revealed significant population differentiation within both species and no shared haplotypes among populations. The northern Gulf species includes four populations (NB, CB, NM and CM) corresponding to northern and central Baja and northern and central mainland sites, while the Cape species includes two populations (SB and SM) corresponding to the Baja and mainland sides of the southern Gulf. The NB/CB division corresponds to a hypothesized Plio–Pleistocene mid‐peninsular seaway. The level of genetic divergence documented in this lineage is extraordinary for a marine fish with a pelagic larval stage within a semi‐enclosed basin.

A MYB transcription factor regulates anthocyanin biosynthesis in mangosteen (Garcinia mangostana L.) fruit during ripening - Yossapol Palapol; Saichol Ketsa; Kui Lin-Wang; Ian B. Ferguson; Andrew C. Allan (Planta, 2009)

Muscle damage responses of the elbow flexors to four maximal eccentric exercise bouts performed every 4 weeks - Trevor C. Chen; Hsin-Lian Chen; Ming-Ju Lin; Chang-Jun Wu; Kazunori Nosaka (European Journal of Applied Physiology, 2009)

EMMC technology for treatment/reuse of dilute dairy wastewater - Rhoda Luo-Ting Lin; Joshua Lelemia Irvine; J. C. M. Kao; P. Y. Yang (Clean Technologies and Environmental Policy, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Rotavirus infection increases the risk of bacteremia in children with nontyphoid Salmonella gastroenteritis - T.-Y. Hung; M.-C. Liu; C.-F. Hsu; Y.-C. Lin (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The in vitro susceptibility of Campylobacter spp. to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

A genomic island of the sulfate‐reducing bacterium Desulfovibrio vulgaris Hildenborough promotes survival under stress conditions while decreasing the efficiency of anaerobic growth - Shawna Johnston; Shiping Lin; Phoebe Lee; Sean M. Caffrey; Janine Wildschut; Johanna K. Voordouw; Sofia M. Da Silva; Ines A. C. Pereira; Gerrit Voordouw (Environmental Microbiology, 2009)
Summary A 47 kb genomic island (GEI) bracketed by 50 bp direct repeats, containing 52 annotated genes, was found to delete spontaneously from the genome of Desulfovibrio vulgaris Hildenborough. The island contains genes for site‐specific recombinases and transposases, rubredoxin:oxygen oxidoreductase‐1 (Roo1) and hybrid cluster protein‐1 (Hcp1), which promote survival in air and nitrite stress. The numbering distinguishes these from the Roo2 and Hcp2 homologues for which the genes are located elsewhere in the genome. Cells with and without the island (GEI + and GEI ‐ cells respectively) were obtained by colony purification. GEI ‐ cells arise in anaerobic cultures of colony‐purified GEI + cells, indicating that the site‐specific recombinases encoded by the island actively delete this region. GEI + cells survive better in microaerophilic conditions due to the presence of Roo1, whereas the Hcps appear to prevent inhibition by sulfur and polysulfide, which are formed by chemical reaction of sulfide and nitrite. Hence, the island confers resistance to oxygen and nitrite stress. However, GEI ‐ cells have a higher growth rate in anaerobic media. Microarrays and enzyme activity stains indicated that the GEI ‐ cells have increased expression of genes, which promote anaerobic energy conservation, explaining the higher growth rate. Hence, while lowering the efficiency of anaerobic metabolism, the GEI increases the fitness of D. vulgaris under stress conditions, a feature reminiscent of pathogenicity islands which allow more effective colonization of environments provided by the targeted hosts.

Hotelling Revisited: Oil Prices and Endogenous Technological Progress - C.-Y. Cynthia Lin; Haoying Meng; Tsz Yan Ngai; Valeria Oscherov; Yan Hong Zhu (Natural Resources Research, 2009)

Insights from a Simple Hotelling Model of the World Oil Market - C.-Y. Cynthia Lin (Natural Resources Research, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Raman spectroscopic study of K-lingunite at various pressures and temperatures - Lin-gun Liu; C.-C. Lin; Y. J. Yung; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

High-frequency direct somatic embryogenesis from leaf tissues of Drimiopsis kirkii Baker (giant squill) - T. H. Lan; P. I. Hong; C. C. Huang; W. C. Chang; C. S. Lin (In Vitro Cellular & Developmental Biology - Plant, 2009)

The Impact of Aqueous Solubility and Dose on the Pharmacokinetic Profiles of Resveratrol - Surajit Das; Hai-Shu Lin; Paul C. Ho; Ka-Yun Ng (Pharmaceutical Research, 2008)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Induction potential of clavulanic acid toward L1 and L2 β-lactamases of Stenotrophomonas maltophilia - C.-W. Lin; R.-M. Hu; S.-C. Huang; Y.-J. Hsiao; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Mapping chromosomal regions affecting flowering time in a spring wheat RIL population - F. Lin; S. L. Xue; D. G. Tian; C. J. Li; Y. Cao; Z. Z. Zhang; C. Q. Zhang; Z. Q. Ma (Euphytica, 2008)

Daidzein-metabolizing phenotypes in relation to serum hormones and sex hormone binding globulin, and urinary estrogen metabolites in premenopausal women in the United States - Charlotte Atkinson; Katherine M. Newton; Frank Z. Stanczyk; Kim C. Westerlind; Lin Li; Johanna W. Lampe (Cancer Causes & Control, 2008)

A role for planar cell polarity signaling in angiogenesis - Pasquale Cirone; Shengda Lin; Hilary L. Griesbach; Yi Zhang; Diane C. Slusarski; Craig M. Crews (Angiogenesis, 2008)

The Impact of Aqueous Solubility and Dose on the Pharmacokinetic Profiles of Resveratrol - Surajit Das; Hai-Shu Lin; Paul C. Ho; Ka-Yun Ng (Pharmaceutical Research, 2008)

The development of extremely dry surface air due to vertical exchanges under the exit region of a jet streak - Michael L. Kaplan; C. Huang; Y.-L. Lin; J. J. Charney (Meteorology and Atmospheric Physics, 2008)

Compositions and source apportionments of atmospheric aerosol during Asian dust storm and local pollution in central Taiwan - Man-Ting Cheng; Wei-Chun Chou; Chia-Pin Chio; Shih-Chieh Hsu; Yi-Ru Su; Pei-Hsuan Kuo; Ben-Jei Tsuang; Shuen-Hsin Lin; Charles C.-K. Chou (Journal of Atmospheric Chemistry, 2008)

The influence of mesoscale mountains on vortex tracks: shallow-water modeling study - C.-Y. Huang; Y.-L. Lin (Meteorology and Atmospheric Physics, 2008)

Expression and significance of PTEN and VEGF in canine mammary gland tumours - C. W. Qiu; D. G. Lin; J. Q. Wang; C. Y. Li; G. Z. Deng (Veterinary Research Communications, 2008)

DC-SIGN and L-SIGN: the SIGNs for infection - Ui-Soon Khoo; Kelvin Y. K. Chan; Vera S. F. Chan; C. L. Steve Lin (Journal of Molecular Medicine, 2008)

Sensitivity of future ozone concentrations in the northeast USA to regional climate change - K. E. Kunkel; H.-C. Huang; X.-Z. Liang; J.-T. Lin; D. Wuebbles; Z. Tao; A. Williams; M. Caughey; J. Zhu; K. Hayhoe (Mitigation and Adaptation Strategies for Global Change, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Analysis of Acropora muricata Calmodulin (CaM) Indicates That Scleractinian Corals Possess the Ancestral Exon/Intron Organization of the Eumetazoan CaM Gene - Chih-Yung Chiou; I-Ping Chen; Chienhsun Chen; Henry Ju-Lin Wu; Nuwei Vivian Wei; Carden C. Wallace; Chaolun Allen Chen (Journal of Molecular Evolution, 2008)

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Determination of Particulate-Bound Formaldehyde from Burning Incense by Solid Phase Microextraction - S. W. Liou; C. Y. Chen; T. T. Yang; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2008)

Expression and immunogenic comparison of VP2 and VP3 from marine birnavirus - H‐J Xu; J‐G Lin; C‐X Zhang; S Suzuki (Journal of Fish Diseases, 2008)
The coding regions for the major epitopes of structural protein VP2 ( vp2e ) and structural protein VP3 were amplified from marine birnavirus (MABV) cDNA and efficiently expressed as glutathione S‐transferase (GST) fusion proteins in Escherichia coli . Polyclonal antibodies against VP2e and VP3 were raised in rabbits and fish using the purified proteins of GST/VP2e and GST/VP3. The rabbit anti‐serum against VP3 was more sensitive than the rabbit anti‐VP2e serum in detecting virus in MABV‐infected fish, while fish anti‐VP2e serum showed a stronger neutralization response than fish anti‐VP3 serum.

BAC-end Sequence Analysis and a Draft Physical Map of the Common Bean (Phaseolus vulgaris L.) Genome - Jessica A. Schlueter; Jose Luis Goicoechea; Kristi Collura; Navdeep Gill; Jer-Young Lin; Yeisoo Yu; Dave Kudrna; Andrea Zuccolo; C. Eduardo Vallejos; Monica Muñoz-Torres; Matthew W. Blair; Joe Tohme; et al. (Tropical Plant Biology, 2008)

Using FANP approach on selection of competitive priorities based on cleaner production implementation: a case study in PCB manufacturer, Taiwan - M. L. Tseng; Y. H. Lin; A. S. F. Chiu; J. C. H. Liao (Clean Technologies and Environmental Policy, 2008)

Growth differences between naturally recruited and stocked European eel Anguilla anguilla from different habitats in Lithuania - Y.‐J. Lin; L. Ložys; J.‐C. Shiao; Y. Iizuka; W.‐N. Tzeng (Journal of Fish Biology, 2007)
European eels Anguilla anguilla from freshwater lakes in Lithuania had slower growth rates and lower backcalculated total lengths ( L T ) than those from lagoons and coastal waters, but no significant differences were found among fish with different migratory histories or between naturally recruited and stocked fish except a higher L T at age of stocked European eels at ages 5 to 8 years. The asymptotic L T did not differ among habitats or migratory histories, but the stocked eels in the lakes had smaller K (coefficient from the von Bertalanffy growth function) than did the both naturally recruited and stocked eels in the lagoon and coastal waters. The growth rate of European eels in Lithuania might be influenced mainly by different habitats rather than different migratory histories and stocking. The lower L T at age of naturally recruited fish at ages 5–8 years compared to stocked fish might result from the extra energy costs entailed in migration from the Atlantic and across the Baltic Sea.

Experiences of water transfer from the agricultural to the non-agricultural sector in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan; Y. L. Sung (Paddy and Water Environment, 2007)

Salmonellae and Campylobacters in Household and Stray Dogs in Northern Taiwan - H.-J. Tsai; H.-C. Huang; C.-M. Lin; Y.-Y. Lien; C.-H. Chou (Veterinary Research Communications, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

In vitro flowering of green and albino Dendrocalamus latiflorus - Choun-Sea Lin; C. J. Liang; H. W. Hsaio; M. J. Lin; W. C. Chang (New Forests, 2007)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Dissipation of Pendimethalin in the Garlic (Allium sativum L.) under Subtropical Condition - H. T. Lin; S. W. Chen; C. J. Shen; C. Chu (Bulletin of Environmental Contamination and Toxicology, 2007)

Functional morphology of scale hinges used to transport water: convergent drinking adaptations in desert lizards (Moloch horridus and Phrynosoma cornutum) - Wade C. Sherbrooke; Andrew J. Scardino; Rocky de Nys; Lin Schwarzkopf (Zoomorphology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Image processing of FORMOSAT‐2 data for monitoring the South Asia tsunami - C.‐C. Liu; J.‐G. Liu; C.‐W. Lin; A.‐M. Wu; S.‐H. Liu; C.‐L. Shieh (International Journal of Remote Sensing, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Quantitative traits for the tail suspension test: automation, optimization, and BXD RI mapping - Heena V. Lad; Lin Liu; José L. Payá-Cano; Cathy Fernandes; Leonard C. Schalkwyk (Mammalian Genome, 2007)

Characteristics of Carbonaceous Aerosol at Taichung Harbor, Taiwan during Summer and Autumn Period of 2005 - Guor-Cheng Fang; S. C. Lee; Wen-Jhy Lee; Yan Cheng; I-Cherng Lin (Environmental Monitoring and Assessment, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

The contents and forms of solid-phase species of radioactive strontium and cesium in Taiwan soils - S. W. Chang Chien; M. C. Wang; C. L. Chiu; Yu-Ming Lin; Shu-Ying Lai (Environmental Monitoring and Assessment, 2007)

Numerical comparison study of cloud microphysical parameterization schemes for a moderate snowfall event in North China - W. S. Lin; C.-H. Sui; C. Bueh; A. Wang; S. Fan; C. Wu; S. Fong; J. Li; J. Meng (Meteorology and Atmospheric Physics, 2007)

Characterization of Gas and Particle Emission from Smoldering Incenses with Various Diameters - T. T. Yang; C. C. Chen; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Multifunctionality of paddy fields in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan (Paddy and Water Environment, 2006)

Electrophysiological Studies in Xenopus Oocytes for the Opening of Escherichia coli SecA-Dependent Protein-Conducting Channels - Bor-Ruei Lin; Lila M. Gierasch; Chun Jiang; Phang C. Tai (The Journal of Membrane Biology, 2006)

Serum Heat Shock Protein (HSP70) and Its Antibody (Anti-HSP70) Levels in Male Foundry Workers in Taiwan - C.-J. Chen; H.-J. Wen; S.-H. Liu; M.-S. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Mechanical Response of a Calcified Plaque Model to Fluid Shear Force - Tiantian C. Lin; Yin Tintut; Althea Lyman; Wendy Mack; Linda L. Demer; Tzung K. Hsiai (Annals of Biomedical Engineering, 2006)

Scaling and organization of electroencephalographic background activity and alpha rhythm in healthy young adults - D. C. Lin; A. Sharif; H. C. Kwan (Biological Cybernetics, 2006)

Antizyme, a natural ornithine decarboxylase inhibitor, induces apoptosis of haematopoietic cells through mitochondrial membrane depolarization and caspases’ cascade - G.-Y. Liu; Y.-F. Liao; P.-C. Hsu; W.-H. Chang; M.-C. Hsieh; C.-Y. Lin; T.-C. Hour; M.-C. Kao; G. J. Tsay; H.-C. Hung (Apoptosis, 2006)

Novel polymorphic microsatellites for studying genetic diversity of red Asian arowanas - G. H. Yue; Z. Y. Zhu; G. Lin; L. C. Lo; F. Feng (Conservation Genetics, 2006)

Tissue Accumulation of Arsenic Compounds in Aquacultural and Wild Mullet (Mugil cephalus) - C.-W. Liu; K.-H. Lin; C.-S. Jang (Bulletin of Environmental Contamination and Toxicology, 2006)

Albino inflorescence proliferation of Dendrocalamus latiflorus - C. S. Lin; M. C. Tseng; P. I. Hong; W. C. Chang (In Vitro Cellular & Developmental Biology - Plant, 2006)

Identification of elongation factor 1α as a potential associated binding partner for Akt2 - Janet Lau; Laura A. Castelli; Emme C. K. Lin; S. Lance Macaulay (Molecular and Cellular Biochemistry, 2006)

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium - David D. Zhang; C. Y. Jim; George C-S Lin; Yuan-Qing He; James J. Wang; Harry F. Lee (Climatic Change, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Uncertainty and importance assessment using differential analysis: an illustration of corrosion depth of spent nuclear fuel canister - D. C.-F. Shih; G.-F. Lin (Stochastic Environmental Research and Risk Assessment, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Detection and characterisation of a second potyvirus from Thunberg fritillary in China - J. Chen; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; C.-B. Wei; L. Lin; J.-P. Chen (Archives of Virology, 2006)

Reference Values for Exposure to PAH Contaminants: Comparison of Fish from Ohio and Mid-Atlantic Streams - Susan M. Cormier; Edith L. C. Lin (Ecotoxicology, 2006)

The Complete Mitochondrial Genome Sequence and Characterization of Single-Nucleotide Polymorphisms in the Control Region of the Asian Seabass (Lates calcarifer) - G. Lin; L. C. Lo; Z. Y. Zhu; F. Feng; R. Chou; G. H. Yue (Marine Biotechnology, 2006)

Implicit solvent simulation models for biomembranes - Grace Brannigan; Lawrence C.-L. Lin; Frank L. H. Brown (European Biophysics Journal, 2006)

Use of a fluorescent membrane probe to identify zooxanthellae in hospite among dissociated endoderm cell culture from coral - C.-S. Chen; H.-P. Lin; C.-C. Yeh; L.-S. Fang (Protoplasma, 2005)

Potential Exposure to VOCs Caused by Dry Process Photocopiers: Results From a Chamber Study - D.-J. Hsu; H.-L. Huang; C.-H. Chien; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Industrial wideband noise reduction for hearing aids using a headset with adaptive-feedback active noise cancellation - J. -H. Lin; P. -C. Li; S. -T. Tang; P. -T. Liu; S. -T. Young (Medical & Biological Engineering & Computing, 2005)

Infectious bursal disease virus recovery from Vero cells transfected with RNA transcripts is enhanced by expression of the structural proteins in trans - M. A. Peters; T. L. Lin; C. C. Wu (Archives of Virology, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Adaptive filtering of evoked potentials using higher-order adaptive signal enhancer with genetic-type variable step-size prefilter - B. -S. Lin; B. -S. Lin; F. -C. Chong; F. Lai (Medical & Biological Engineering & Computing, 2005)

Risk Assessment of Arsenic Exposure from Consumption of Cultured Milkfish, Chanos chanos (Forsskål), from the Arsenic-Contaminated Area in Southwestern Taiwan - M.-C. Lin; H.-Y. Lin; H.-H. Cheng; Y.-C. Chen; C.-M. Liao; K.-T. Shao (Bulletin of Environmental Contamination and Toxicology, 2005)

Spatial Variations in Shear Stress in a 3-D Bifurcation Model at Low Reynolds Numbers - Mahsa Rouhanizadeh; Tiantian C. Lin; Diego Arcas; Juliana Hwang; Tzung K. Hsiai (Annals of Biomedical Engineering, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

Heavy Metals in Wastewater: The Effect of Electrolyte Composition on the Precipitation of Cadmium(II) Using Lime and Magnesia - Xiaomei Lin; Robert C. Burns; Geoffrey A. Lawrance (Water, Air, & Soil Pollution, 2005)

A new potyvirus from Thunberg fritillary (Fritillaria thunbergii Miq.) in Zhejiang, China - C.-B. Wei; J. Chen; Q.-Y. Zhang; Y.-H. Shi; L. Lin; H.-Y. Zheng; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

Surface air temperature records biased by snow-covered surface - X. Lin; K. G. Hubbard; C. B. Baker (International Journal of Climatology, 2005)

Mining the structural knowledge of high-dimensional medical data using isomap - S. Weng; C. Zhang; Z. Lin; X. Zhang (Medical & Biological Engineering & Computing, 2005)

Thallium in Whole Blood Samples from College Students in Taiwan - T.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Phylogenetic analysis of classical swine fever virus in Taiwan - C. H. Pan; M. H. Jong; T. S. Huang; H. F. Liu; S. Y. Lin; S. S. Lai (Archives of Virology, 2005)

Etoposide (VP-16) sensitizes p53-deficient human non-small cell lung cancer cells to caspase-7-mediated apoptosis - C.-C. Chiu; C.-H. M. Y. Lin; K. Fang (Apoptosis, 2005)

Automatic optimum order selection of parametric modelling for the evaluation of abnormal intra-QRS signals in signal-averaged electrocardiograms - C. -C. Lin; C. -M. Chen; I. -F. Yang; T. -F. Yang (Medical & Biological Engineering & Computing, 2005)

Evaluation of Genotoxicity of Combined Pollution by Cadmium and Atrazine - A. J. Lin; Y. G. Zhu; Y. P. Tong; C. N. Geng (Bulletin of Environmental Contamination and Toxicology, 2005)

Effect of Air Flow on Emission of Smoldering Incense - T. T. Yang; C. C. Chen; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Trace Elements in Cultured Tilapia (Oreochromis mossambicus): Results from a Farm in Southern Taiwan - T.-S. Lin; C.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Polymorphic variation of CYP1A1 is associated with the risk of gastric cardia cancer: a prospective case?cohort study of cytochrome P-450 1A1 and GST enzymes - Mark J. Roth; Christian C. Abnet; Laura Lee Johnson; Steven D. Mark; Zhi Wei Dong; Philip R. Taylor; Sanford M. Dawsey; You-Lin Qiao (Cancer Causes & Control, 2004)

Infectious bursal disease virus polyprotein expression arrests growth and mitogenic stimulation of B lymphocytes - M. A. Peters; T. L. Lin; C. C. Wu (Archives of Virology, 2004)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Gene cloning and characterization of a soybean (Glycine max L.) LEA protein, GmPM16 - Ming-der Shih; Shu-chin Lin; Jaw-shu Hsieh; Chi-hua Tsou; Teh-yuan Chow; Tsai-piao Lin; Yue-ie C. Hsing (Plant Molecular Biology, 2004)

Whole Blood Vanadium in Taiwanese College Students - T.-S. Lin; C.-L. Chang; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2004)

Identification of a 98-kb DNA segment containing the rice Eui gene controlling uppermost internode elongation, and construction of a TAC transgene sublibrary - Y.-H. Xu; Y.-Y. Zhu; H.-C. Zhou; Q. Li; Z.-X. Sun; Y.-G. Liu; H.-X. Lin; Z.-H. He (Molecular Genetics and Genomics, 2004)

Diversity of Degradation Pathways of Some Aromatic Compounds by Phenotype and Genotype Testing in Acinetobacter Strains - X.Q. Yu; A. Belhaj; C. Elmerich; M. Lin (World Journal of Microbiology and Biotechnology, 2004)

Acute Aquatic Toxicity of N-Methyl-2-Pyrrolidinone to Daphnia magna - C.-H. Lan; C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2004)

cDNA cloning and genomic structure of the duck (Anas platyrhynchos) MHC classI gene - C. Xia; C.Y. Lin; G.X. Xu; T.J. Hu; T.Y. Yang (Immunogenetics, 2004)

Short-rotation woody crops and phytoremediation: Opportunities for agroforestry? - D.L. Rockwood; C.V. Naidu; D.R. Carter; M. Rahmani; T.A. Spriggs; C. Lin; G.R. Alker; J.G. Isebrands; S.A. Segrest (Agroforestry Systems, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Adaptive processing bandwidth adjustment for laser Doppler flowmetry - Y. Y. Chen; Y. H. Lin; I. C. Jan; R. S. Liu; N. K. Chou; G. -J. Jan (Medical & Biological Engineering & Computing, 2004)

Stochastic analysis of spatial variability in unconfined groundwater flow - G.-F. Lin; C.-M. Chen (Stochastic Environmental Research and Risk Assessment, 2004)

A likelihood approach for mapping growth trajectories using dominant markers in a phase-unknown full-sib family - C.-X. Ma; M. Lin; R. C. Littell; T. Yin; R. Wu (Theoretical and Applied Genetics, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Nonlinear Time Series Analysis of Volcanic Tremor Events Recorded at Sangay Volcano, Ecuador - K. I. Konstantinou; C. H. Lin (Pure and Applied Geophysics, 2004)

Excavating Y-chromosome haplotype strata in Anatolia - Cengiz Cinnioglu; Roy King; Toomas Kivisild; Ersi Kalfoglu; Sevil Atasoy; Gianpiero L. Cavalleri; Anita S. Lillie; Charles C. Roseman; Alice A. Lin; Kristina Prince; Peter J. Oefner; Peidong Shen; et al. (Human Genetics, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

QSARs for Predicting the Toxicity of Mixtures Containing Polar Narcotic Chemicals - Z. Lin; K. Yin; C. Wu; L. Wang; H. Yu (Bulletin of Environmental Contamination and Toxicology, 2003)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Historical biogeography and phylogenetic relationships of the genus Chamaecyparis (Cupressaceae) inferred from chloroplast DNA polymorphism - W. P. Wang; C. Y. Hwang; T. P. Lin; S. Y. Hwang (Plant Systematics and Evolution, 2003)

Regulation of distinct biological activities of the NF-?B transcription factor complex by acetylation - Lin-Feng Chen; Warner C. Greene (Journal of Molecular Medicine, 2003)

Prospective study of serum retinol, β-carotene, β-cryptoxanthin, and lutein/zeaxanthin and esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Sanford M. Dawsey; Dennis W. Buckman; Chung S. Yang; William J. Blot; Zhi-Wei Dong; Philip R. Taylor; Steven D. Mark (Cancer Causes & Control, 2003)

General Toxicity Prediction Approach for Mixtures Containing Polar Narcotic Chemicals - Z. Lin; C. Wu; P. Shi; L. Wang; S. Gao (Bulletin of Environmental Contamination and Toxicology, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

A method for inflorescence proliferation - C.-S. Lin; C.-T. Chen; C.-C. Lin; W.-C. Chang (Plant Cell Reports, 2003)

Dissecting the pet18mutation in Saccharomyces cervisiae: HTL1encodes a 7-kDa polypeptide that interacts with components of the RSC complex - Y.-M. Lu; Y.-R. Lin; A. Tsai; Y.-S. Hsao; C.-c. Li; M. Y. Cheng (Molecular Genetics and Genomics, 2003)

The anabolic pyruvate oxidoreductase from Methanococcus maripaludis - Winston C. Lin; Yu-Ling Yang; William B. Whitman (Archives of Microbiology, 2003)

Genetic evidence for a role of phospholipase C at the budding yeast kinetochore - N. DeLillo; C. Romero; H. Lin; A. Vancura (Molecular Genetics and Genomics, 2003)

Genetic relationships among cold, salt and drought tolerance during seed germination in an interspecific cross of tomato - M.R. Foolad; P. Subbiah; C. Kramer; G. Hargrave; G.Y. Lin (Euphytica, 2003)

Effect of Cadmium(Ii) and Anion Type on the Ageing of Ferrihydrite and its Subsequent Leaching under Neutral and Alkaline Conditions - Xiaomei Lin; Robert C. Burns; Geoffrey A. Lawrance (Water, Air, & Soil Pollution, 2003)

Involvement of the terminus of grouper betanodavirus capsid protein in virus-like particle assembly - M. W. Lu; C. S. Lin (Archives of Virology, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.

Effect of rice-glycerol complex medium on the production of lovastatin byMonascus ruber - Y. N. Chang; Y. C. Lin; C. C. Lee; B. L. Liu; Y. M. Tzeng (Folia Microbiologica, 2002)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Biological Monitoring of Environment Exposure to Safrole and the Taiwanese Betel Quid Chewing - M. J. W. Chang; C. Y. Ko; R. F. Lin; L. L. Hsieh (Archives of Environmental Contamination and Toxicology, 2002)

Spectral analysis of water level fluctuations in aquifers - D. C.-F. Shih; G.-F. Lin (Stochastic Environmental Research and Risk Assessment, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Yield Surface of Mu-San Sandstone by Hollow Cylinder Tests - D.-H. Lee; C. H. Juang; H.-M. Lin (Rock Mechanics and Rock Engineering, 2002)

Animal-related occupations and the risk of leukemia, myeloma, and non-Hodgkin's lymphoma in Canada - Lin Fritschi; Kenneth C. Johnson; Erich V. Kliewer; Rick Fry (Cancer Causes & Control, 2002)

Adsorption of Copper in the Different Sorbent/Water Ratios of Soil Systems - T. W. Chang; M. K. Wang; C. Lin (Water, Air, & Soil Pollution, 2002)

Effect of Water Extract of Compost on the Adsorption of Arsenate by Two Calcareous Soils - Haw-Tarn Lin; M. C. Wang; Gwo-Chen Li (Water, Air, & Soil Pollution, 2002)

Insights into bactericidal action of surface-attached poly(vinyl-N-hexylpyridinium) chains - Jian Lin; Joerg C. Tiller; Sang Beom Lee; Kim Lewis; Alexander M. Klibanov (Biotechnology Letters, 2002)

Raman spectra of hydrous γ -Mg 2 SiO 4 at various pressures and temperatures - L. Liu; C.-C. Lin; T. P. Mernagh; T. Inoue (Physics and Chemistry of Minerals, 2002)

Modulation of calcium balance in tilapia larvae ( Oreochromis mossambicus ) acclimated to low-calcium environments - Chou M.-Y.; Lu F.-I.; Lin H.-C.; Hwang P.-P.; Yang C.-H. (Journal of Comparative Physiology B, 2002)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Prospective study of tooth loss and incident esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Cultures of equine respiratory epithelial cells and organ explants as tools for the study of equine influenza virus infection - C. Lin; R. E. Holland Jr; N. M. Williams; T. M. Chambers (Archives of Virology, 2001)

Rapid molecular analysis of the haemagglutinin gene of human influenza A H3N2 viruses isolated in Spain from 1996 to 2000 - M. T. Coiras; J. C. Aguilar; M. Galiano; S. Carlos; V. Gregory; Y. P. Lin; A. Hay; P. Pérez-Breña (Archives of Virology, 2001)

Nutritive quality and morphological development under partial shade of some forage species with agroforestry potential - C. H. Lin; M. L. McGraw; M. F. George; H. E. Garrett (Agroforestry Systems, 2001)

Environmental Exposure to Polycyclic Aromatic Hydrocarbons and Total Suspended Particulates in a Taiwanese Temple - T-C. Lin; F-H. Chang; J-H. Hsieh; H-R. Chao; M-R. Chao (Bulletin of Environmental Contamination and Toxicology, 2001)

Separation of different sized particles by inertial migration - S.R. Wickramasinghe; W.-C. Lin; D.S. Dandy (Biotechnology Letters, 2001)

RS-100642-198, a novel sodium channel blocker, provides differential neuroprotection against hypoxia/hypoglycemia, veratridine or glutamate-mediated neurotoxicity in primary cultures of rat cerebellar neurons - Jitendra R. Dave; Yu Lin; Haresh S. Ved; Michael L. Koenig; Larry Clapp; John Hunter; Frank C. Tortella (Neurotoxicity Research, 2001)

Bioaccumulation of Arsenic in Aquacultural Large-Scale Mullet Liza macrolepis from Blackfoot Disease Area in Taiwan - M.-C. Lin; C.-M. Liao; C.-W. Liu; S. Singh (Bulletin of Environmental Contamination and Toxicology, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

High-pressure Raman spectroscopic study of Co- and Ni-olivines - C. C. Lin (Physics and Chemistry of Minerals, 2001)

Pharmacokinetics of reboxetine in healthy volunteers with different ethnic descents - Pamela E. Hendershot; Joseph C. Fleishaker; Keh-Ming Lin; Inocencia D. Nuccio; Russell E. Poland (Psychopharmacology, 2001)

Toxicokinetics and Acute Toxicity of Waterborne Zinc in Abalone ( Haliotis diversicolor supertexta Lischke) - C.-M. Liao; M.-C. Lin (Bulletin of Environmental Contamination and Toxicology, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Translational Regulation as a Novel Mechanism for the Development of Cellular Drug Resistance - John C. Schmitz; Jun Liu; Xiukun Lin; Tian-min Chen; Wu Yan; Ningwen Tai; Ashwin Gollerkeri; Edward Chu (Cancer and Metastasis Reviews, 2001)

Characterization of grouper nervous necrosis virus (GNNV) - S C Chi; B J Lo; S C Lin (Journal of Fish Diseases, 2001)
Grouper nervous necrosis virus (GNNV) was isolated from moribund grouper larvae, Epinephelus sp., using a fish cell line GF‐1. The present study describes the biochemical and biophysical properties of GNNV and the expression of GNNV in diseased grouper larvae. Viral protein was detectable in most of the GNNV‐infected GF‐1 cells by the fluorescent antibody technique (FAT) after 12 h post‐infection (p.i.), although no cytopathic effect (CPE) appeared at that time. Clear CPE developed on the third day, and complete disintegration of the monolayer occurred over the subsequent two days. The infectivity of GNNV can be blocked following treatment at 60 °C for 1 h. GNNV was sensitive to pH 3 and pH 10–12 with a 4 log 10 drop in infectivity. Purified GNNV was analysed by SDS–PAGE, and then stained with periodic acid silver. The positive staining indicated that its two capsid proteins were glycoproteins. Genomic RNAs of GNNV were extracted from purified virions and analysed. The molecular weights of genomic RNAs were 1.02 × 10 6 and 0.50 × 10 6 Da. The T2 region of the coat protein gene of GNNV was amplified by polymerase chain reaction (PCR), and the multiple alignment of the T2 sequence of two GNNV isolates with four genotypes of fish nodaviruses revealed that these two isolates (GNNV9410 and GNNV9508) belong to the red‐spotted grouper nervous necrosis virus (RGNNV) genotype. The tissue distribution of GNNV in naturally infected grouper larvae was investigated by in situ hybridization using a dig‐labelled probe, which showed that GNNV was not only detected in the brain and retina, but also in the gill, skeletal muscle, liver, pyloric gland, intestine and blood cells in the heart.

Antibody responses to respiratory coronavirus infections of cattle during shipping fever pathogenesis - X. Q. Lin; K. L. O’Reilly; J. Storz; C. W. Purdy; R. W. Loan (Archives of Virology, 2000)

Surveys of Volatile Organic Compounds in Soil and Groundwater at Industrial Sites in Taiwan - M.-C. T. Kuo, C.-M. Chen, C. H. Lin, H. C (Bulletin of Environmental Contamination and Toxicology, 2000)

Differences in size and growth rates of male and female migrating Japanese eels in Pearl River, China - W. N. Tzeng; H. R. Lin; C. H. Wang; S. N. Xu (Journal of Fish Biology, 2000)
The Sr/Ca ratios in otoliths of silver Japanese eels Anguilla japonica , in Pearl River, China, indicated that both sexes did not stay in brackish water and grew in fresh water from the glass eel stage until spawning migration. This did not support the hypothesis that females tended to distribute upstream and males might be restricted to estuaries. The back‐calculated total length of males at glass eel stage was not significantly different from that of females, indicating that the hypothesis that small glass eels became males and larger ones became females may not be true. The mean (±S.D.) age and total length of males at migration were 6·4±1·6 years and 48·3±4·5 cm, which were significantly smaller than for females, 8·3±1·6 years and 61·4±4·1 cm. The age of migration was related inversely to growth rate for both sexes. Growth parameters of the von Bertalanffy growth equation were K =0·21 cm year°1, L ∞ =55·7 cm and t o =‐0·55 year for males and K =0·14 cm year −1 , L ∞ =77·5 cm and t o =‐0·60 year for females. The difference in asymptotic length ( L ∞ ) between males and females may be because females postpone migration to achieve larger size for maximizing reproductive success.

Sampling efficiency of a modified closed-face cassette sampler for airborne toluene diisocyanate determination - I.-F. Mao; M.-L. Chen; Y.-C. Lin (International Archives of Occupational and Environmental Health, 2000)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Maternal transfer of cadmium tolerance in larval Oreochromis mossambicus - H. C. Lin; S.C Hsu; P.P. Hwang (Journal of Fish Biology, 2000)
Exposing female tilapia to Cd did not affect reproduction and egg quality, nor the survival of their offspring. The LT 50 of Cd‐exposed larvae (within 24 h post hatching) from Cd‐treated female Oreochromis mossambicus (mean ±S.E.=10·9±0·5 days, n =4) was greater than that of Cd‐exposed larvae from control females (6·9± 1·2 days, n =4). A substantial amount of metallothionein mRNA (MT mRNA) was found in both oocytes and newly hatched larvae from Cd‐treated females, but MT mRNA levels were low in newly fertilized eggs. The amount of MT mRNA was very low in all these stages in the control group. Cadmium could not be detected at any stage for either control or Cd‐treated group, and metallothionein protein levels were also very low in both groups. The early appearance of MT mRNA in oocytes and newly hatched larvae from Cd‐treated females may result in early translation after hatching and explain their tolerance to Cd.

Photodegradation of the Herbicides Butachlor and Ronstar Using Natural Sunlight and Diethylamine - Y. J. Lin; C. Lin; K. J. Yeh; A. Lee (Bulletin of Environmental Contamination and Toxicology, 2000)

Raman spectroscopic study of hydroxyl-clinohumite at various pressures and temperatures - C.-C. Lin; L.-G. Liu; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2000)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Stability of Human Serum Albumin During Bioprocessing: Denaturation and Aggregation During Processing of Albumin Paste - Jen-Jen Lin; Jeffrey D. Meyer; John F. Carpenter; Mark C. Manning (Pharmaceutical Research, 2000)

Alcohol Consumption and Breast Cancer among Black and White Women in North Carolina (United States) - Anita Yeomans Kinney; Robert C. Millikan; Yu Hua Lin; Patricia G. Moorman; Beth Newman (Cancer Causes & Control, 2000)

Type-1c glycogen storage disease is not caused by mutations in the glucose-6-phosphate transporter gene - B. Lin; H. Hiraiwa; C.-J. Pan; R.C. Nordlie; J.Y. Chou (Human Genetics, 1999)

Flavonoids as inducers of extracellular proteins and exopolysaccharides of Sinorhizobium fredii - C. C. Lin; Y. C. Chen; S. C. Song; L. P. Lin (Biology and Fertility of Soils, 1999)

Type-1c glycogen storage disease is not caused by mutations in the glucose-6-phosphate transporter gene - B. Lin; H. Hiraiwa; C.-J. Pan; R.C. Nordlie; J.Y. Chou (Human Genetics, 1999)

Compression studies of gibbsite and its high-pressure polymorph - E. Huang; J.-F. Lin; J. Xu; T. Huang; Y.-C. Jean; H.-S. Sheu (Physics and Chemistry of Minerals, 1999)

Cadmium-Inducible Metallothionein in Tilapia ( Oreochromis mossambicus ) - S. M. Wu *, C. F. Weng; M. J. Yu; C. C. Lin; S. T. Chen; J. C. Hwang; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1999)

In vitro immunoregulatory effects of lithium in healthy volunteers - M. Maes; C. Song; A.-h. Lin; Rosaria Pioli; Gunter Kenis; Marta Kubera; Eugene Bosmans (Psychopharmacology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Mitochondrion‐rich cells in the embryonic yolk sac of Oreochromis mossambicus - H. C. Lin; P. P. Hwang; T. H. Lee (Journal of Fish Biology, 1999)
By removing a small amount of yolk, tilapia embryos were dechorionated successfully as early as 30 h after fertilization. Using DASPEI, a mitochondrion‐specific fluorescent stain, we were able to determine the first appearance of the mitochondrion rich cells on the surface of the yolk sac 26 h after fertilization ( c. 2 h after the beginning of gastrula stage). However, with scanning electron microscopy examination, no apical crypt could be found until 48 h after fertilization.

High-pressure Raman spectroscopic study of chondrodite - C.-C. Lin; L.-g. Liu; T. Irifune (Physics and Chemistry of Minerals, 1999)

Phenotypic plasticity in the growth of the self‐fertilizing hermaphroditic fish Rivulus marmoratus - H.‐C. Lin; W. A. Dunson (Journal of Fish Biology, 1999)
Temperature, salinity, food ration and interactions among them had significant effects on overall growth of hatchlings of the self‐fertilizing hermaphrodite Rivulus marmoratus . Low temperature (19° C) suppressed growth. At 26° C, the treatment groups at 12 and 40‰ salinity had higher final wet masses than the group at 1‰. When provided with high food ration, individuals whose parents were provided with low food had a significantly higher specific growth rate in the first month than those whose parents were provided with high food ration. This effect was also found in the final wet masses. It appears that genetic variation in this species occurs only between strains, yet within a strain there is considerable scope for phenotypic plasticity. The combination of a fixed genotype and plastic expression, along with a suite of specialized physiological characteristics, may explain how a self‐fertilizing hermaphrodite can thrive in such an abiotically stressful and variable habitat as an estuary.

Photoregulated expression of the PsPK3 and PsPK5 genes in pea seedlings - Rajnish Khanna; Xia Lin; John C. Watson (Plant Molecular Biology, 1999)

Vagal afferents from the uterus and cervix provide direct connections to the brainstem - J. J. Collins; C. E. Lin; H. R. Berthoud; R. E. Papka (Cell and Tissue Research, 1999)

Models of corundum origin from alkali basaltic terrains: a reappraisal - F. Lin Sutherland; Paul W. O. Hoskin; C. Mark Fanning; Robert R. Coenraads (Contributions to Mineralogy and Petrology, 1998)

Δ 9 -THC training dose as a determinant for ( R )-methanandamide generalization in rats - T. U. C. Järbe; R. J. Lamb; A. Makriyannis; S. Lin; A. Goutopoulos (Psychopharmacology, 1998)

Report on the First International Conference on the Mammalian Centromere - C. C. Lin (Chromosome Research, 1998)

Localizations of NS3 and E proteins in mouse brain infected with mutant strain of Japanese encephalitis virus - J. J. Wang; C. L. Liao; C. I. Yang; Y. L. Lin; C. T. Chiou; L. K. Chen (Archives of Virology, 1998)

Shade effects on forage crops with potential in temperate agroforestry practices - C. H. Lin; R. L. McGraw; M. F. George; H. E. Garrett (Agroforestry Systems, 1998)

Effects of recombinant lysostaphin on cytotoxicity and interleukin-8 level in normal human epidermal keratinocytes cell line - Err-Cheng Chan; C. Allen Chang; Tzong-Zeng Wu; Yuh-Ling Lin (Biotechnology Letters, 1998)

Fast integration of low orbiter's trajectory perturbed by the earth's non-sphericity - C. Hwang; M.-J. Lin (Journal of Geodesy, 1998)

A morphological study of cells isolated from the perfused gill of dab and Atlantic salmon - S.‐H. Lin; G. A. Davidson; C. J. Secombes; A. E. Ellis (Journal of Fish Biology, 1998)
Single cell suspensions were derived from the gills of dab Limanda limanda and Atlantic salmon Salmo salar which were free from blood cell contamination. Gills were perfused with heparinized saline before the cells were liberated from their resident position using a procedure employing chelating agents and collagenase digestion. Cells were characterized using light and electron microscopy as well as histochemical staining. The results indicate that the cell types resident in the gill tissue should be capable of expressing local immune competence. Small and large lymphocytes, macrophages, neutrophils, eosinophilic granule cells, goblet cells, chloride cells and cells of unusual morphology were identified especially the presence of goblet cells apparently within epithelial‐like cells.

Acute and Chronic Effects of Antimony Chloride (SbCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Acute and Chronic Effects of Indium Chloride (InCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Molecular cloning and chromosomal mapping of type one serine/threonine protein phosphatases in Arabidopsis thaliana - Qing Lin; Jia Li; Robert D. Smith; John C. Walker (Plant Molecular Biology, 1998)

Acute and Chronic Effects of Gallium Chloride (GaCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Micropropagation of Bambusa edulis through nodal explants of field-grown culms and flowering of regenerated plantlets - C.-S. Lin; W.-C. Chang (Plant Cell Reports, 1998)

Nucleotide sequence of canine fibroblast growth factor-8 (FGF-8) - Halit Canatan; Young C. Lin (In Vitro Cellular & Developmental Biology - Animal, 1998)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Transgenic peppermint ( Mentha × piperita L.) plants obtained by cocultivation with Agrobacterium tumefaciens - X. Niu; K. Lin; P. M. Hasegawa; R. A. Bressan; S. C. Weller (Plant Cell Reports, 1998)

Estimation of myocardial glucose utilisation with PET using the left ventricular time-activity curve as a non-invasive input function - X. Li; D. Feng; K. -P. Lin; S. -C. Huang (Medical & Biological Engineering & Computing, 1998)

αv Integrins mediate adhesion and migration of breast carcinoma cell lines - Nanette C. Wong; Barbara M. Mueller; Carlos F. Barbas; Pete Ruminski; Vito Quaranta; Emme C. K. Lin; Jeffrey W. Smith (Clinical & Experimental Metastasis, 1998)

Effects of cadmium on the kinetics of calcium uptake in developing tilapia larvae, Oreochromis mossambicus - M.-H. Chang; H.-C. Lin; P.P. Hwang (Fish Physiology and Biochemistry, 1997)

The pharmacokinetics and pharmacodynamics of adinazolam: multi-ethnic comparisons - Kotra Ajir; Michael Smith; Keh-Ming Lin; Dora Anderson; Inocencia Nuccio; Yanping Zheng; Russell E. Poland; Joseph C. Fleishaker; James H. Chambers (Psychopharmacology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The acetylcholine releaser linopirdine increases parietal regional cerebral blood flow in Alzheimer's disease - Christopher H. van Dyck; C. Huie Lin; Rhonda Robinson; Janet Cellar; Eileen O. Smith; J. Craig Nelson; Amy F. T. Arnsten; Paul B. Hoffer (Psychopharmacology, 1997)

Human centromeric DNAs - C. Lee; R. Wevrick; R. B. Fisher; M. A. Ferguson-Smith; C. C. Lin (Human Genetics, 1997)

Three-dimensional P-wave Velocity Structure of the Bear Valley Region of Central California - C.-H. Lin; S. W. Roecker (Pure and Applied Geophysics, 1997)

Regulation of lipoprotein metabolism by estrogen in inbred strains of mice occurs primarily by posttranscriptional mechanisms - Rai Ajit K. Srivastava; Elaine S. Krul; Renee C. Lin; Gustav Schonfeld (Molecular and Cellular Biochemistry, 1997)

Stimulation of testicular function by exogenous testosterone in male protandrous black porgy, Acanthopagrus schlegeli - E.‐L. Lau; B.‐Y. Lin; F.‐Y. Lee; L.‐T. Sun; S. Dufour; C.‐F. Chang (Journal of Fish Biology, 1997)
When 4 mg of testosterone (T) per kg food was given to 1‐year‐old protandrous male black porgy Acanthopagrus schlegeli for 7 months, gonadosomatic index was significantly higher than when the dose was 0.5 mg kg −1 food. Both doses of T prolonged the spawning season, and increased the number of spermiating fish and milt volume. Sperm concentrations were similar in spermiating black porgy from the treated and control groups. Low levels of oestradiol‐17β were observed during the experimental period while elevated levels of plasma T were observed only in March in both control and T‐treated groups. Significantly higher levels of plasma 11‐ketotestosterone (11‐KT) were observed in the 0.5‐ and 4.0‐mg T‐treated groups during the spawning season as compared to the control group. The present data suggest that both 0.5‐ and 4·0‐mg T doses stimulate testicular weight, increase numbers of spermiating males and milt volume without affecting the sperm concentrations. Plasma 11‐KT concentrations were elevated during T treatment and closely correlated with testicular development and spermiation.

Sweet potato (Ipomoea batatas) trypsin inhibitors expressed in transgenic tobacco plants confer resistance against Spodoptera litura - K.-W. Yeh; M.-I. Lin; S.-J. Tuan; Y.-M. Chen; C.-J. Lin; S.-S. Kao (Plant Cell Reports, 1997)

Transcription of genes for conglutin γ and a leginsulin-like protein in narrow-leafed lupin - Steven C. Ilgoutz; Nathalie Knittel; Jiang Min Lin; Shoukat Sterle; Kenwyn R. Gayler (Plant Molecular Biology, 1997)

Phylogenetic analysis of feline immunodeficiency virus isolated from cats in Taiwan - G. Inada; T. Miyazawa; Y. Inoshima; M. Kohmoto; Y. Ikeda; C. -H. Liu; J. A. Lin; T. -F. Kou; T. Mikami (Archives of Virology, 1997)

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

Assignment of DNA markers to Nicotiana sylvestris chromosomes using monosomic alien addition lines - D. F. Suen; C. K. Wang; R. F. Lin; Y. Y. Kao; F. M. Lee; C. C. Chen (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)

A preliminary study of the formation of precipitation systems under undisturbed conditions during TAMEX - C. -S. Chen; C. -Y. Lin (Meteorology and Atmospheric Physics, 1997)

A high resolution numerical study of Gulf of Mexico fronts and eddies - D. E. Dietrich; C. A. Lin; A. Mestas-Nunez; D. S. Ko (Meteorology and Atmospheric Physics, 1997)

Determination of urinary zinc, chromium, and copper in steel production workers - C. J. Horng; S. R. Lin (Biological Trace Element Research, 1996)

Capsid protein of cucumber mosaic virus accumulates in the nuclei and at the periphery of the nucleoli in infected cells - N. -S. Lin; C. -E. Hsieh; Y. -H. Hsu (Archives of Virology, 1996)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

Complete genomic RNA sequences of cucumber mosaic virus strain NT9 from Taiwan - Y. -H. Hsu; C. -W. Wu; B. -Y. Lin; H. -Y. Chen; M. -F. Lee; C. -H. Tsai (Archives of Virology, 1995)

Different sensitivities to cadmium in tilapia larvae (Oreochromis mossambicus; teleostei) - P. P. Hwang; S. W. Lin; H. C. Lin (Archives of Environmental Contamination and Toxicology, 1995)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)

Trace elements in hair of blackfoot disease - T. C. Pan; T. H. Lin; C. L. Tseng; M. H. Yang; C. W. Huang (Biological Trace Element Research, 1993)

Simultaneous determination of Zn, Cd, Pb, and Cu in urine of patients with blackfoot disease using anodic stripping voltammetry - T. C. Pan; C. J. Horng; S. R. Lin; T. H. Lin; C. W. Huang (Biological Trace Element Research, 1993)

A new immunostimulatory complex (PICKCa) in experimental rabies: antiviral and adjuvant effects - H. X. Lin; C. Gontier; M-F. Saron; P. Perrin (Archives of Virology, 1993)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Quantitative measurement of two-component pH-sensitive colorimetric spectra using multilayer neural networks - Chii-Wann Lin; Joseph C. LaManna; Yashiyasu Takefuji (Biological Cybernetics, 1992)

Electron microscopic evidence for the association of M 2 protein with the influenza virion - D. C. Jackson; Xi-Lin Tang; K. Gopal Murti; R. G. Webster; G. W. Tregear; W. J. Bean (Archives of Virology, 1991)

A parallel algorithm for estimating the secondary structure in ribonucleic acids - Y. Takefuji; C. W. Lin; K. C. Lee (Biological Cybernetics, 1990)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)

Hyphal wall chemistry in Apodachlya - C. C. Lin; R. C. Sicher; J. M. Aronson (Archives of Microbiology, 1976)

Chitin and cellulose in the cell walls of the oomycete, Apodachlya sp. - C. C. Lin; Jerome M. Aronson (Archives of Microbiology, 1970)